Adhesion and interfacial characterization of biomimetically texturized lithium disilicate - Zorzin, José Ignacio; Beck, Simon; Belli, Renan; Petschelt, Anselm; Boccaccini, Aldo R.; Lohbauer, Ulrich (International Journal of Adhesion and Adhesives, 2019)
Lithium disilicate glass-ceramic (LS2) can be biomimetically textured by crystal orientation, mimicking the microstructure of dental enamel and inducing anisotropic mechanical responses to crack growth. The deliberate texturization of LS2 plays to the clinical advantage of reinforcing weak sites of typical fracture initiation in dental prosthetic constructs. Similar to enamel, adhesion of biomimetically textured LS2 could also show anisotropic behavior. Therefore, tensile bond strength (TBS) before and after thermocycling (TC) and interfacial characterization of biomimetically textured LS2 (parallel (PAR) or perpendicular (PER) crystal orientation) after different pre-treatment modes (hydrofluoric acid etching (HFE), grit blasting (GBL) and self-etching glass-ceramic primer (SGP)) were investigated. TC reduced significantly TBS for all specimens except for GBL. Biomimetic textured LS2 after HFE showed anisotropic behavior regarding adhesion. Crystal orientation reduced TBS for the PER HFE specimens after TC significantly. In general, the TBS of HFE specimens was still higher or not significantly lower compared to other pre-treatment modes like GBL or SGP. For the GBL and SGP specimens, crystal orientation had no influence on TBS and interfacial characteristics. In contrast HFE specimens showed different interfacial characteristics depending if they were PAR or PER texturized. Based on these findings, HFE of biomimetic textured LS2 can be recommended. For bonding, the PAR orientation is recommended as its adhesion potential is less prone to degrade.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Anisotropic; Biomimetic material; Grit blasting; Hydrofluoric acid etching; Interfacial characterization; Lithium disilicate ceramics; Self-etching glass-ceramic primer; Tensile bond strength

Adhesive Failure of Lava Ultimate and Lithium Disilicate Crowns Bonded to Zirconia Abutments: A Prospective Within-Patient Comparison - Schepke, Ulf; Lohbauer, Ulrich; Meijer, Henny J.; Cune, Marco S. (International Journal of Prosthodontics, 2018)
PURPOSE: To demonstrate the influence of restorative material on the success of clinical bonding to zirconia. MATERIALS AND METHODS: A total of 50 participants with a single implant received screw-retained restorations; ie, Lava Ultimate (LU) crowns extraorally bonded to zirconia abutments. After 1 year, lithium disilicate (LDS) was used as an alternative restorative material. These restorations were also followed for 1 year. RESULTS: Forty LU restorations (80%) debonded within 1 year of clinical service, whereas no bonding failures occurred with LDS restorations. CONCLUSION: The choice of restorative material for single crowns luted to zirconia implant abutments strongly influences the incidence of bonding failures.
EVALuna2:34641

ADM guidance-Ceramics: all-ceramic multilayer interfaces in dentistry - Lohbauer, Ulrich; Scherrer, Susanne S.; Della Bona, Alvaro; Tholey, Michael; Van Noort, Richard; Vichi, Alessandro; Kelly, J. Robert; Cesar, Paulo F. (Dental Materials, 2017)
This guidance document describes the specific issues involved in dental multilayer ceramic systems. The material interactions with regard to specific thermal and mechanical properties are reviewed and the characteristics of dental tooth-shaped processing parameters (sintering, geometry, thickness ratio, etc.) are discussed. Several techniques for the measurement of bond quality and residual stresses are presented with a detailed discussion of advantages and disadvantages. In essence no single technique is able to describe adequately the all-ceramic interface. Invasive or semi-invasive methods have been shown to distort the information regarding the residual stress state while non-invasive methods are limited due to resolution, field of focus or working depth. This guidance document has endeavored to provide a scientific basis for future research aimed at characterizing the ceramic interface of dental restorations. Along with the methodological discussion it is seeking to provide an introduction and guidance to relatively inexperienced researchers.
EVALuna2:24694

ADM guidance-ceramics: Fatigue principles and testing - Kelly, J. R.; Cesar, P. F.; Scherrer, S. S.; Della Bona, A.; Van Noort, R.; Tholey, M.; Vichi, A.; Lohbauer, Ulrich (Dental Materials, 2017)
Clinical failure of dental ceramics is usually reported as partial fracture of the restoration (chipping) or as catastrophic fracture of the whole structure. In contrast to metals, ceramics are linear-elastic, brittle materials exhibiting extremely low damage tolerance to failure. Well documented clinical and lab reports have shown this fracture event often occurs at loads far below their fracture strength due to intrinsic fatigue degradation via slow crack growth or cyclic fatigue mechanisms. The presence and development of surface flaws have a dominant role in damage accumulation and lifetime reduction of ceramic structures.This ADM guidance document aims to summarize the aspects related to fatigue degradation of dental ceramics, reviewing the concepts of fatigue testing and furthermore aims to provide practical guidance to young scientists entering into fatigue related research. The description of fatigue strength is always accompanied by a clear understanding of the underlying fracture mechanisms.
EVALuna2:24698

ADM guidance-Ceramics: Fracture toughness testing and method selection - Cesar, Paulo Francisco; Della Bona, Alvaro; Scherrer, Susanne S.; Tholey, Michael; Van Noort, Richard; Vichi, Alessandro; Kelly, Robert; Lohbauer, Ulrich (Dental Materials, 2017)
The objective is within the scope of the Academy of Dental Materials Guidance Project, which is to provide dental materials researchers with a critical analysis of fracture toughness (FT) tests such that the assessment of the FT of dental ceramics is conducted in a reliable, repeatable and reproducible way.Fracture mechanics theory and FT methodologies were critically reviewed to introduce basic fracture principles and determine the main advantages and disadvantages of existing FT methods from the standpoint of the dental researcher.The recommended methods for FT determination of dental ceramics were the Single Edge "V" Notch Beam (SEVNB), Single Edge Precracked Beam (SEPB), Chevron Notch Beam (CNB), and Surface Crack in Flexure (SCF). SEVNB's main advantage is the ease of producing the notch via a cutting disk, SEPB allows for production of an atomically sharp crack generated by a specific precracking device, CNB is technically difficult, but based on solid fracture mechanics solutions, and SCF involves fracture from a clinically sized precrack. The IF test should be avoided due to heavy criticism that has arisen in the engineering field regarding the empirical nature of the calculations used for FT determination.Dental researchers interested in FT measurement of dental ceramics should start with a broad review of fracture mechanics theory to understand the underlying principles involved in fast fracture of ceramics. The choice of FT methodology should be based on the pros and cons of each test, as described in this literature review.
EVALuna2:24690

ADM guidance-Ceramics: guidance to the use of fractography in failure analysis of brittle materials - Scherrer, Susanne S.; Lohbauer, Ulrich; Della Bona, Alvaro; Vichi, Alessandro; Tholey, Michael J.; Kelly, J. Robert; Van Noort, Richard; Cesar, Paulo Francisco (Dental Materials, 2017)
To provide background information and guidance as to how to use fractography accurately, a powerful tool for failure analysis of dental ceramic structures.An extended palette of qualitative and quantitative fractography is provided, both for in vivo and in vitro fracture surface analyses. As visual support, this guidance document will provide micrographs of typical critical ceramic processing flaws, differentiating between pre- versus post sintering cracks, grinding damage related failures and occlusal contact wear origins and of failures due to surface degradation.The documentation emphasizes good labeling of crack features, precise indication of the direction of crack propagation (dcp), identification of the fracture origin, the use of fractographic photomontage of critical flaws or flaw labeling on strength data graphics. A compilation of recommendations for specific applications of fractography in Dentistry is also provided.This guidance document will contribute to a more accurate use of fractography and help researchers to better identify, describe and understand the causes of failure, for both clinical and laboratory-scale situations. If adequately performed at a large scale, fractography will assist in optimizing the methods of processing and designing of restorative materials and components. Clinical failures may be better understood and consequently reduced by sending out the correct message regarding the fracture origin in clinical trials.
EVALuna2:24699

ADM research guidance papers - Cesar, Paulo; Hickel, Reinhard; Kelly, J. Robert; Lohbauer, Ulrich; Watts, David C. (Dental Materials, 2017)
EVALuna2:24702

Aerophilic Surfaces for Sustained Corrosion Protection of Metals Underwater - Prado, Lucia; Hayek, Samer; Mazare, Anca Valentina; Erceg, Ina; Sarau, George; Christiansen, Silke; Kamaleev, Maksim; Wurmshuber, Michael; Lohbauer, Ulrich; Goldmann, Wolfgang; Virtanen, Sannakaisa; Tesler, Alexander (Advanced Functional Materials, 2024)
Corrosion and biofouling are wetting-related phenomena that limit the effective use of metals in aqueous media. Nonwettable surfaces can mitigate the adverse effects of wetting by minimizing contact with water. However, current achievements in this field fall short of meeting industrial requirements due to the short lifetime of plastrons. This study proposes a method to measure the protective sustainability of plastron. Superhydrophobic (SHS) and aerophilic (APhS) surfaces are constructed on lightweight aluminum and are initially analyzed by conventional goniometry, which show comparable values. However, the plastron that develops underwater is substantially different. While SHS exhibit unevenly broken plastron, APhS show uniform, continuous plastron. As an example of the sustained protective performance of plastron, the corrosion resistance of SHS and APhS is presented. Potentiodynamic polarization, impedance spectroscopy, and long-term immersion in seawater show a drastic enhancement in corrosion resistance, exclusively for APhS. In fact, almost no electrochemical signals are measurable, and no pitting corrosion is observed after 415 days of immersion in seawater. Conversely, SHS show no noticeable improvement and corrode faster than bare Al due to plastron loss. Since goniometric measurements do not provide information on plastron, it is essential to analyze the plastron for any non-wettable surface utilized underwater.<br
Keywords: air plastron; aluminum; Cassie–Baxter wetting; corrosion; superhydrophobic surfaces; underwater

Antagonistenverschleiß durch polierte zirkonoxidkronen pilotstudie über einen zeitraum von 24 monaten, ausgewertet auf basis der digitalen intraoralen abformung Antagonist wear by polished zirconia crowns A 24 months pilot study using the intraoral digital impression technique - Hartkamp, Oliver; Lohbauer, Ulrich; Reich, Sven (International Journal of Computerized Dentistry, 2017)
Aim: The aim of this in vivo study was to measure antagonist wear caused by polished monolithic posterior zirconia crowns over a 24-month period using the intraoral digital impression (IDI) technique. Materials and methods: Thirteen zirconia crowns were placed in nine patients. The crowns and adjacent teeth were captured using an intraoral scanner (Lava C.O.S.). The corresponding antagonist teeth and the respective neighboring teeth were also scanned. Scanning was performed immediately after the restoration (baseline) as well as 12 and 24 months after crown placement. Geomagic Qualify software was used to superimpose the follow-up data sets onto the corresponding baseline data set, identify wear sites, and measure maximum vertical height loss in each individual wear site. Overall antagonist wear was then determined as the mean of wear rates measured in all of the individual antagonist units. In addition, wear rates in enamel and ceramic antagonists were analyzed as part of the scope of this study. Results: The maximum mean wear with standard deviation (SD) in the overall sample with a total of nine patients, 13 antagonist units, and 98 evaluable wear sites was 86 ± 23 μm at 12 months, and 103 ± 39 μm at 24 months. The maximum mean wear in the enamel antagonist subgroup was 87 ± 41 μm at 12 months, and 115 ± 71 μm at 24 months; and in the ceramic antagonist subgroup 107 ± 22 μm at 12 months, and 120 ± 27 μm at 24 months. Conclusions: The wear rates determined in this study are comparable to those of existing studies. The IDI technique of wear analysis can be carried out in a practical manner and produces useful results.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Antagonist; Clinical; Digital; Intraoral scan; Monolithic; Wear; Zirconia

Antagonist wear by polished zirconia crowns - Hartkamp, O.; Lohbauer, Ulrich; Reich, S. (International Journal of Computerized Dentistry, 2017)
The aim of this in vivo study was to measure antagonist wear caused by polished monolithic posterior zirconia crowns over a 24-month period using the intraoral digital impression (IDI) technique.Thirteen zirconia crowns were placed in nine patients. The crowns and adjacent teeth were captured using an intraoral scanner (Lava C.O.S.). The corresponding antagonist teeth and the respective neighboring teeth were also scanned. Scanning was performed immediately after the restoration (baseline) as well as 12 and 24 months after crown placement. Geomagic Qualify software was used to superimpose the follow-up data sets onto the corresponding baseline data set, identify wear sites, and measure maximum vertical height loss in each individual wear site. Overall antagonist wear was then determined as the mean of wear rates measured in all of the individual antagonist units. In addition, wear rates in enamel and ceramic antagonists were analyzed as part of the scope of this study.The maximum mean wear with standard deviation (SD) in the overall sample with a total of nine patients, 13 antagonist units, and 98 evaluable wear sites was 86 ± 23 µm at 12 months, and 103 ± 39 µm at 24 months. The maximum mean wear in the enamel antagonist subgroup was 87 ± 41 µm at 12 months, and 115 ± 71 µm at 24 months; and in the ceramic antagonist subgroup 107 ± 22 µm at 12 months, and 120 ± 27 µm at 24 months.The wear rates determined in this study are comparable to those of existing studies. The IDI technique of wear analysis can be carried out in a practical manner and produces useful results.
EVALuna2:24693

Antagonist wear of monolithic zirconia crowns after 2 years - Lohbauer, Ulrich; Reich, Sven (Clinical Oral Investigations, 2017)
The aim of this study was to evaluate the amount of wear on the antagonist occlusal surfaces of clinically placed monolithic zirconia premolar and molar crowns (LAVA Plus, 3M ESPE).Fourteen in situ monolithic zirconia crowns and their opposing antagonists (n = 26) are the subject of an ongoing clinical trial and have been clinically examined at baseline and after 24 months. Silicone impressions were taken and epoxy replicas produced for qualitative SEM analysis and quantitative analysis using optical profilometry. Based on the baseline replicas, the follow-up situation has been scanned and digitally matched with the initial topography in order to calculate the mean volume loss (in mm3) as well as the mean maximum vertical loss (in mm) after 2 years in service.The mean volume loss for enamel antagonist contacts (n = 7) was measured to 0.361 mm3 and the mean of the maximum vertical loss to 0.204 mm. The mean volume loss for pure ceramic contacts (n = 10) was measured to 0.333 mm3 and the mean of the maximum vertical loss to 0.145 mm. The wear rates on enamel contacts were not significantly different from those measured on ceramic antagonists.Based on the limitations of this study, it can be concluded for the monolithic zirconia material LAVA Plus that the measured wear rates are in consensus with other in vivo studies on ceramic restorations. Further, that no significant difference was found between natural enamel antagonists and ceramic restorations as antagonists. The monolithic zirconia restorations do not seem to be affected by wear within the first 2 years.The monolithic zirconia crowns (LAVA Plus) show acceptable antagonist wear rates after 2 years in situ, regardless of natural enamel or ceramics as antagonist materials.
EVALuna2:24689

Antibacterial properties of metal and metalloid ions in chronic periodontitis and peri-implantitis therapy - Goudouri, Ourania Menti; Kontonasaki, Eleana; Lohbauer, Ulrich; Boccaccini, Aldo R. (Acta Biomaterialia, 2014)
Periodontal diseases like periodontitis and peri-implantitis have been linked with Gram-negative anaerobes. The incorporation of various chemotherapeutic agents, including metal ions, into several materials and devices has been extensively studied against periodontal bacteria, and materials doped with metal ions have been proposed for the treatment of periodontal and peri-implant diseases. The aim of this review is to discuss the effectiveness of materials doped with metal and metalloid ions already used in the treatment of periodontal diseases, as well as the potential use of alternative materials that are currently available for other applications but have been proved to be cytotoxic to the specific periodontal pathogens. The sources of this review included English articles using Google Scholar™, ScienceDirect, Scopus and PubMed. Search terms included the combinations of the descriptors "disease", "ionic species" and "bacterium". Articles that discuss the biocidal properties of materials doped with metal and metalloid ions against the specific periodontal bacteria were included. The articles were independently extracted by two authors using predefined data fields. The evaluation of resources was based on the quality of the content and the relevance to the topic, which was evaluated by the ionic species and the bacteria used in the study, while the final application was not considered as relevant. The present review summarizes the extensive previous and current research efforts concerning the use of metal ions in periodontal diseases therapy, while it points out the challenges and opportunities lying ahead. © 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Antibacterial properties; Metal and metalloid ions; Peri-implantitis; Periodontitis

A photoelastic assessment of residual stresses in zirconia-veneer crowns - Belli, Renan; Monteiro, S.; Baratieri, L. N.; Katte, H.; Petschelt, Anselm; Lohbauer, Ulrich (Journal of Dental Research, 2012)
Residual stresses within the veneer are linked to the high prevalence of veneer chipping observed in clinical trials of zirconia prostheses. We hypothesized that the thermal mismatch between the zirconia infrastructure and the veneer porcelain, as well as the rate used for cooling zirconia-veneer crowns, would be directly proportional to the magnitude of residual stresses built within the veneer layer. Two porcelains with different coefficients of thermal expansion were used to veneer zirconia copings, to create high or low thermal mismatches. The crowns were cooled according to a fast- or a slow-cooling protocol. The retardation of polarized light waves was used to calculate the residual stress magnitude and distribution across the veneer, according to the photoelasticity principle, in 1.0-mm-thick crown sections. While thermal mismatch was an important factor influencing the maximum stress development in the veneer, cooling rate had a minor role. Curved surfaces were preferential sites for stress concentration regardless of thermal mismatch or cooling rate. © 2012 International & American Associations for Dental Research.
CRIS-Team Scopus Importer:2023-01-23
Keywords: birefringence; cooling rate; internal stress; photoelastic effect; thermal mismatch; veneered zirconia restorations

Apical debris removal of CanalBrushes with different tip modifications - Roggendorf, Matthias Johannes; Kraus, Florian; Lohbauer, Ulrich; Frankenberger, Roland; Petschelt, Anselm; Ebert, Johannes (Quintessence International, 2015)
In this study the apical debris score regarding the rotary use of the CanalBrush (Coltène-Whaledent) with three different tip variations was compared to that of sole needle irrigation.Sixty straight roots of human teeth with one canal were instrumented to size 45/.04. Roots were split into halves, reassembled, and embedded in model resin to form separable tooth models. Artificially manufactured dentin debris was packed into the apical 2 mm of the roots to form a relatively consistent debris challenge to be assessed. Then, the debris of each root half was evaluated apically using a modified Hülsmann-score under a light microscope. After remounting the models, root canals were irrigated with NaOCl 3% (2 mL): group 1 with sole needle irrigation, in groups 2 to 4 additionally agitated with different versions of the CanalBrush for 30 s at 600 rpm; group 2, one straight bristle ("old"); group 3, two additional diagonal bristles ("new"); group 4, central straight bristle of the new version removed ("experimental"). Following this, all root halves were reevaluated.Irrigation reduced debris scores in all groups (Wilcoxon tests, P < .001). Mean debris scores were reduced from a pre-irrigation score of about 4 for all groups to a score of around 2 to 3 in groups 1 and 2, and to scores around 1 in groups 3 and 4. Samples of groups 3 and 4 were significantly cleaner than of groups 1 and 2 (Mann-Whitney tests, P < .05).CanalBrushes with diagonal bristles achieved an improved apical cleaning ability.
EVALuna2:24673

Are linear elastic material properties relevant predictors of the cyclic fatigue resistance of dental resin composites? - Belli, Renan; Petschelt, Anselm; Lohbauer, Ulrich (Dental Materials, 2014)
The aim of this study was to measure the linear elastic material properties of direct dental resin composites and correlate them with their fatigue strength under cyclic loading.Bar specimens of twelve resin composites were produced according to ISO 4049 and tested for elastic modulus (Emod) in 3-point bending (n=10), flexural strength (FS) (n=15) and single-edge-notch-beam fracture toughness (FT) (n=15), both in 4-point bending. Using the same specimen geometry, the flexural fatigue strength (FFS) was determined using the staircase approach after 10(4) cycles at 0.5 Hz in 4-point bending (n=25). The observation of the fracture surface and fracture profiles was conducted using a scanning electron microscope in order to evaluate the respective fracture mechanisms according to the two different loading conditions.Materials were ranked differently according to the tested parameters. Only weak correlations were found between any of the initial properties and FFS or strength loss. The best correlation to FFS was found to be the Emod (r(2)=0.679), although only slightly. Crack path in both loading conditions was mainly interparticle, with the crack propagating mainly within the matrix phase for fatigued specimens and eventually through the filler/matrix interface for statically loaded specimens. Fracture of large particles or prepolymerized fillers was only observed in specimens of FS and FT. Initial properties were better associated with microstructural features, whereas the fatigue resistance showed to be more dependent on aspects relating to the matrix phase.Our results show that linear elastic properties such as elastic modulus, flexural strength and fracture toughness are not good descriptors of the fatigue resistance of dental resin composite under cyclic bending, and may therefore have limited clinical relevance.
EVALuna2:24662

Are resin composites suitable replacements for amalgam? A study of two-body wear - Lazaridou, Dimitra; Belli, Renan; Petschelt, Anselm; Lohbauer, Ulrich (Clinical Oral Investigations, 2015)
Wear resistance is an important property of the dental materials, particularly for large restorations in the posterior regions and for the patients suffering from parafunctional activities. Additionally, the wear resistance of flowable composite resin materials is a clinical concern, although they are popular among dentists because of their easy handling. The aims of the present study were to evaluate the wear resistance of nine composite resins both condensable (G-aenial posterior, Venus, GrandioSO, Tetric EvoCeram, Ceram X duo, Filtek Supreme XTE) and new-generation flowable resin composites (G-aenial Universal Flo, GrandioSO Flow and GrandioSO Heavy Flow) and to compare these results with amalgam.Eight specimens of each material were subjected to two-body wear tests, using a chewing simulator. The wear region of each material was examined under profilometer, measuring the vertical loss (?m) and the volume loss (mm(3)) of the materials. Additionally, SEM analysis was performed to assess surfaces irregularities.The results showed significant difference of the vertical loss and the volume loss of the examined materials (p < 0.001). Although amalgam had the best wear resistance, two condensable resin composites (GrandioSO, Ceram X duo) and all flowable materials had no significant difference with amalgam. GrandioSO had the highest wear resistance and Filtek Supreme XTE the lowest wear resistance.The majority of resin composites had good wear resistance and similar to amalgam.Based on the in vitro measurements of two-body wear resistance, the new resin composites could replace amalgam for restorations placed in occlusal stress-bearing regions. New-generation flowable resin materials may also be used in occlusal contact restorations.
EVALuna2:24672

A split-Chevron-Notched-Beam sandwich specimen for fracture toughness testing of bonded interfaces - Lubauer, Julia; Belli, Renan; Lorey, Tony; Max, Stefanie; Lohbauer, Ulrich; Zorzin, José Ignacio (Journal of the Mechanical Behavior of Biomedical Materials, 2022)
The realization that the use of strength tests as a means to probe the bonding performance of adhesive systems to dental restorative materials suffers from inherent drawbacks has shifted efforts towards devising viable and valid fracture toughness test for that purpose. Here we introduce a new procedure to produce split-Chevron-Notched-Beam specimens that need not undergo sawing or notching after bonding, thus sparing the interface from pre-stresses. We evaluate the formal geometric factor considering the influence of the use of different materials having different elastic properties, and show that the results obtained fall within reasonable ranges measured by other established compliance calibrated methods. We demonstrate the application of this new approach for dentin-luting composite and zirconia-luting composite interfaces for different adhesive systems and pre-treatment procedures in order to probe the sensitivity of the method to different bond qualities.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Adhesion; Bonding; Chevron-notched-beam; Dentin; Fracture toughness; Zirconia

A step toward bio-inspired dental composites - Tiu, Janine; Belli, Renan; Lohbauer, Ulrich (Biomaterial Investigations in Dentistry, 2023)
This feasibility study aimed to develop a new composite material of aligned glass flakes in a polymer resin matrix inspired by the biological composite nacre. The experimental composite was processed by an adapted method of pressing a glass flake and resin monomer system. By pressing and allowing the excess monomer to flow out, the long axis of the flakes was aligned. The resultant anisotropic composite with silanized and non-silanized glass flakes were subjected to fracture toughness tests. We observed increasing fracture toughness with increasing crack extension (Δa) known as resistance curve (R-curve) behavior. Silanized specimens had higher stress intensity KR-Δa over non-silanized specimens, whereas non-silanized specimens had a much lower Young's modulus, and higher nonlinear plastic-elastic JR-Δa R-curve. In comparison with conventional composites, flake-reinforced composites can sustain continued crack growth for more significant extensions. The primary toughening mechanism seen in flake-reinforced composites was crack deviation and crack branching. We produced an anisotropic model of glass flake-reinforced composite showing elevated toughening potential and a prominent R-curve effect. The feasibility of flake reinforcement of dental composites has been shown using a relatively efficient method. The use of a biomimetic, nacre-inspired reinforcement concept might guide further research toward improvement of dental restorative materials.
EVALuna2:560302
Keywords: Composite materials; biomaterials; dentalmaterials; mechanicalproperties; bioinspiration; R-curve

Atomic structure of ZrO2-doped Li2O–SiO2-based multi-component glasses revealed by molecular dynamics–reverse Monte Carlo modeling - Toyoda, R.; Usui, K.; Hirota, T.; Kimura, K.; Onodera, Y.; Cicconi, Maria Rita; Belli, Renan; Brehl, Martin; Lubauer, Julia; Lohbauer, Ulrich; Tajiri, H.; Ikeda, K.; et al. (Journal of Non-Crystalline Solids, 2023)
Structural model of ZrO2-doped Li2O–SiO2-based multi-component glass, which is developed as a mother material for high-strength glass-ceramics, is constructed by the molecular dynamics–reverse Monte Carlo (MD–RMC) method based on anomalous X-ray and neutron scattering data. In particular, we have succeeded in extracting reliable local structural information around Zr from the MD–RMC model. It was found that a significant fraction of edge-sharing structural units was formed around Zr–O and Li–O polyhedra, resulting in a densely packed configuration of O atoms. This configuration was manifested by a very sharp principal peak in the neutron scattering data. Our model suggested that both the Zr and Li ions are incorporated in the glass as distorted ZrO6 octahedra and distorted LiO4 tetrahedra, respectively. These structural features are discussed in terms of the crystallization behavior of this material.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Anomalous X-ray scatteirng; Glass-ceramics; Molecular dynamics simulation; Neutron scattering; Reverse Monte Carlo

Biaxial flexural strength of zirconia: A round robin test with 12 laboratories - Spintzyk, Sebastian; Geis-Gerstorfer, Jürgen; Bourauel, Christoph; Keilig, Ludger; Lohbauer, Ulrich; Brune, Annike; Greuling, Andreas; Arnold, Christin; Rues, Stefan; Adjiski, Ranko; Sawada, Tomofumi; Lümkemann, Nina; et al. (Dental Materials, 2021)
Objective: The aim of this interlaboratory round robin test was to prove the robustness of the DIN EN ISO 6872:2019 and to identify the influence of processing and testing variations. Methods: Each of the 12 laboratories participated (A–L) received 60 (n = 720) assigned zirconia specimens. All participants seperated the specimens from the blanks, sintered them, polished half of all specimens and performed the biaxial flexural test (DIN EN ISO 6872:2019). The surface roughness was determined by using tactile measuring device. Fractographic examination was performed under scanning-electron-microscopy (SEM). Data was analysed using Kolmogorov–Smirnov-, Kruskal–Wallis-, Mann–Whitney-U-test and two-parametric Weibull statistic (p < 0.05). Results: The results for both preparation methods (as-fired and polished) showed significant differences for some participants. The values for as-fired groups ranged between 513 (I) and 659 (E) MPa. H showed higher Weibull modulus than C, E and I. Within polished groups flexural strengths values from 465 (L) to 1212 (E) MPa were observed, with a tendency to clustered groups A, I, J, L (465–689 MPa) and remaining groups (877–1212 MPa). E presented the highest and H the lowest Weibull modulus. Within A and J, no impact of the preparation method on flexural strength values was observed. Within L, as-fired specimens showed higher flexural strength than polished ones. The flexural strength increase did only associate to a certain extent with measured surface roughness. Fractography showed defect populations depending on polishing techniques, associated to the strength level, especially for polished groups. Reduced strength is related to machining defects, regardless of the surface state. Significance: DIN EN ISO 6872:2019 can be seen as guidance to biaxial flexural strength testing but additional effort is necessary to ensure interlaboratory comparability. Calibrated furnaces and reliable sintering conditions are mandatory requirements together with detailed specifications on finishing or polishing procedures. Biaxial flexural testing is really a matter of understanding specimen preparation, alignment and mechanical testing by itself. DIN EN ISO 6872:2019 should further recommend reporting of mean surface roughness along with any biaxial flexural strength data. Fractography is a mandatory tool in interpretation and understanding of strength data.
CRIS-Team Scopus Importer:2021-01-29
Keywords: 5Y-PSZ; Flexural strength; ISO 6872; Surface quality; Translucent zirconia; Weibull statistics

Biomimetically-and hydrothermally-grown HAp nanoparticles as reinforcing fillers for dental adhesives - Wagner, Andrea; Belli, Renan; Stoetzel, Christian; Hilpert, Andrea; Mueller, Frank A.; Lohbauer, Ulrich (Journal of Adhesive Dentistry, 2013)
Purpose: Differently prepared hydroxyapatite (HAp) nanoparticles were incorporated into the adhesive solution of a commercial adhesive system in order to evaluate the effect on microtensile bond strength to dentin. Materials and Methods: HAp nanoparticles (20 to 70 nm) were prepared by different processes (biomimetic and hydrothermal) and incorporated into the adhesive of the Adper Scotchbond Multi-Purpose (SBMP) system at various concentrations. Control (unfilled) and experimental groups (filled) were applied onto flat mid-coronal human dentin. Composite crowns were built up and cut into beams with a cross-sectional area of 0.65 ± 0.05 mm2. Specimens were fractured in tension and examined with a scanning electron microscope (SEM) for fractographic analysis. Microtensile bond strength (µTBS) data were analyzed using a two-way ANOVA and modified LSD test at α= 0.05. Analysis of the nanofiller distribution and ultramorphological characterization of the interface was performed by transmission electron microscopy (TEM). Results: HAp nanoparticle incorporation into the adhesive of SBMP significantly influenced µTBS to dentin depending on the fillers and the concentration used. A significant increase of the mechanical strength was obtained for the adhesives containing 1% (wt/vol) biomimetic and 5% hydrothermal silanized HAp particles, while the other particle fractions did not influence µTBS significantly. 10% (wt/vol) HAp particles significantly lowered the µTBS irrespective of the particle type used. TEM micrographs revealed nanoparticle dispersion through the adhesive layer but no deposition on or penetration into the hybrid layer. Conclusions: HAp nanoparticle incorporation into SBMP increased bond strength to dentin by cohesively reinforcing the interface adhesive layer. At a concentration of 10% (wt/vol), nanofiller incorporation had a negative effect on bond strength. © 2013 by Quintessence Publishing Co Inc.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Adhesion; Biomimetic and hydrothermal HAp preparation; Dentin bonding; HAp; Nanoparticle filler; Silanization; Tensile bond strength

Bonding performance of universal adhesives in different etching modes - Wagner, Anna; Wendler, Michael; Petschelt, Anselm; Belli, Renan; Lohbauer, Ulrich (Journal of Dentistry, 2014)
The aim of this study was to compare the microtensile bond strength (?TBS) and resin penetration into dentine of three universal adhesives (UAs) applied in two different etching modes (i.e. self-etch or etch-and-rinse). The effect of thermocycling on the ?TBS was also evaluated.The occlusal third of sound human molars was removed and the exposed surfaces were treated with three UAs (Futurabond Universal, Scotchbond Universal Adhesive and All-Bond Universal) in self-etch or etch-and-rinse mode. Two one-step self-etch adhesives (Futurabond DC and Futurabond M) were applied on additional teeth as reference. After composite build up, the specimens were stored for 24 h in distilled water at 37 °C or thermocycled for 5000 cycles. Composite/dentine beams were prepared (1 mm(2)) and ?TBS test was performed. Data was analyzed using three-way ANOVA and Tukey's test (?=0.05). One additional tooth was prepared for each group for evaluation of infiltration ability into dentine by dyeing the adhesives with a fluorochrome (Rhodamine B). After longitudinal sectioning, the generated interfaces were examined under confocal laser scanning microscopy.The addition of an etching step did not significantly affect the ?TBS of none of the UAs, when compared to their self-etch application mode. All pre-etched specimens showed considerably longer resin tags and thicker hybrid layers. Thermocycling had no significant effect on the ?TBS of the UAs.Application of an etching step prior to UAs improves their dentine penetration, but does not affect their bond strength to dentine after 24h or after thermocycling for 5000 cycles.Similar bond strength values were observed for the UAs regardless of application mode, which makes them reliable for working under different clinical conditions.
EVALuna2:24659

Bond strength of adhesive cements to root canal dentin tested with a novel pull-out approach - Ebert, Johannes; Leyer, Andrea; Günther, Oliver; Lohbauer, Ulrich; Petschelt, Anselm; Frankenberger, Roland; Roggendorf, Matthias Johannes (Journal of Endodontics, 2011)
Introduction: A novel approach to the pull-out test using silica-coated and silanized steel spreaders was designed to avoid influence from the post-cement interface. In this study, this test was applied to compare the post retention of adhesive versus conventional cements. Methods: Canals of 90 single-rooted human teeth were prepared to size 60 taper.02; trimmed to an 8-mm root canal length; irrigated with 40% citric acid, 3% NaOCl, and 70% ethanol; and randomly divided into 9 groups (n = 10). Steel spreaders (size 55, taper.02) were silica coated and silanized with the Rocatec system (3M-Espe, Seefeld, Germany), except for a control group using GCem, and cemented with one of these adhesive luting materials (RelyX Unicem [3M-Espe], Clearfil SA Cement [Kuraray Medical, Okayama, Japan], Bifix SE [Voco GmbH, Cuxhaven, Germany], NX3 [Kerr, Orange, CA], GCem [GC Corp, Tokyo, Japan], or SmartCem2 [Dentsply De Trey GmbH, Konstanz, Germany]) or conventional cements (Hoffmann's cement [Hoffmann Dental Manufaktur GmbH, Berlin, Germany] or Ketac Cem [3M-Espe]). After storage in distilled water (24 h/37°C), the spreaders were pulled out in a universal testing machine at a crosshead speed of 2 mm/min. Results: The failure mode was cohesive or adhesive at the cement-dentin interface in more than 80% of the experimental samples (control group: adhesive to the post: 9/10 samples). Adhesive luting materials retained posts better than conventional cements (t test, P <.001) but with a wide range in variation. RelyX Unicem displayed significantly higher values except when compared with Bifix SE and Clearfil SA (analysis of variance/Student-Newman-Keuls, P <.05). NX3, SmartCem2, and GCem showed no significant differences to Hoffmann's cement and Ketac Cem. Conclusions: The novel pull-out approach served well in testing the bond strength of different cements to root canal dentin. The bonding effectiveness of adhesive cements varied significantly and was material specific. Copyright © 2011 American Association of Endodontists.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Adhesive luting; conventional cementation; endodontic posts; pull-out resistance; Rocatec; self-adhesive cements

Bulk-fill resin composites: Polymerization properties and extended light curing - Zorzin, José Ignacio; Maier, Eva; Harre, Sarah; Fey, Tobias; Belli, Renan; Lohbauer, Ulrich; Petschelt, Anselm; Taschner, Michael (Dental Materials, 2015)
Signcance. All investigated bulk-fill composites obtained sufficient polymerization properties at 4 mm depth. Enhanced curing time improved the investigated polymerization properties of bulk-fills and Z250. (C) 2014 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Bulk-fill; Resin composites; Shrinkage stress; Volume shrinkage; Degree of conversion; Irradiance; Vickers hardness; FTIR spectroscopy

Chairside CAD/CAM materials. Part 1: Measurement of elastic constants and microstructural characterization - Belli, Renan; Wendler, Michael; de Ligny, Dominique; Cicconi, Maria Rita; Petschelt, Anselm; Peterlik, Herwig; Lohbauer, Ulrich (Dental Materials, 2017)
Significance. Here different methodologies are compared for the measurement of elastic constants and microstructural characterization of CAD/CAM restorative materials. The elastic properties and crystal phases of eight materials are herein fully characterized. (C) 2016 The Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Ceramic; Resin composite; CAD/CAM; Chairside; Elastic modulus; Poisson's ratio; Microstructure

Chairside CAD/CAM materials. Part 2: Flexural strength testing - Wendler, Michael; Belli, Renan; Petschelt, Anselm; Mevec, Daniel; Harrer, Walter; Lube, Tanja; Danzer, Robert; Lohbauer, Ulrich (Dental Materials, 2017)
Strength is one of the preferred parameters used in dentistry for determining clinical indication of dental restoratives. However, small dimensions of CAD/CAM blocks limit reliable measurements with standardized uniaxial bending tests. The objective of this study was to introduce the ball-on-three-ball (B3B) biaxial strength test for dental for small CAD/CAM block in the context of the size effect on strength predicted by the Weibull theory.Eight representative chairside CAD/CAM materials ranging from polycrystalline zirconia (e.max ZirCAD, Ivoclar-Vivadent), reinforced glasses (Vitablocs Mark II, VITA; Empress CAD, Ivoclar-Vivadent) and glass-ceramics (e.max CAD, Ivoclar-Vivadent; Suprinity, VITA; Celtra Duo, Dentsply) to hybrid materials (Enamic, VITA; Lava Ultimate, 3M ESPE) have been selected. Specimens were prepared with highly polished surfaces in rectangular plate (12×12×1.2mm3) or round disc (Ø=12mm, thickness=1.2mm) geometries. Specimens were tested using the B3B assembly and the biaxial strength was determined using calculations derived from finite element analyses of the respective stress fields. Size effects on strength were determined based on results from 4-point-bending specimens.A good agreement was found between the biaxial strength results for the different geometries (plates vs. discs) using the B3B test. Strength values ranged from 110.9MPa (Vitablocs Mark II) to 1303.21MPa (e.max ZirCAD). The strength dependency on specimen size was demonstrated through the calculated effective volume/surface.The B3B test has shown to be a reliable and simple method for determining the biaxial strength restorative materials supplied as small CAD/CAM blocks. A flexible solution was made available for the B3B test in the rectangular plate geometry.
EVALuna2:24692

Chairside CAD/CAM materials. Part 3: Cyclic fatigue parameters and lifetime predictions - Wendler, Michael; Belli, Renan; Valladares, Diana; Petschelt, Anselm; Lohbauer, Ulrich (Dental Materials, 2018)
OBJECTIVES: Chemical and mechanical degradation play a key role on the lifetime of dental restorative materials. Therefore, prediction of their long-term performance in the oral environment should base on fatigue, rather than inert strength data, as commonly observed in the dental material's field. The objective of the present study was to provide mechanistic fatigue parameters of current dental CAD/CAM materials under cyclic biaxial flexure and assess their suitability in predicting clinical fracture behaviors. METHODS: Eight CAD/CAM materials, including polycrystalline zirconia (IPS e.max ZirCAD), reinforced glasses (Vitablocs Mark II, IPS Empress CAD), glass-ceramics (IPS e.max CAD, Suprinity PC, Celtra Duo), as well as hybrid materials (Enamic, Lava Ultimate) were evaluated. Rectangular plates (12×12×1.2mm3) with highly polished surfaces were prepared and tested in biaxial cyclic fatigue in water until fracture using the Ball-on-Three-Balls (B3B) test. Cyclic fatigue parameters n and A* were obtained from the lifetime data for each material and further used to build SPT diagrams. The latter were used to compare in-vitro with in-vivo fracture distributions for IPS e.max CAD and IPS Empress CAD. RESULTS: Susceptibility to subcritical crack growth under cyclic loading was observed for all materials, being more severe (n≤20) in lithium-based glass-ceramics and Vitablocs Mark II. Strength degradations of 40% up to 60% were predicted after only 1 year of service. Threshold stress intensity factors (Kth) representing the onset of subcritical crack growth (SCG), were estimated to lie in the range of 0.37-0.44 of KIc for the lithium-based glass-ceramics and Vitablocs Mark II and between 0.51-0.59 of KIc for the other materials. Failure distributions associated with mechanistic estimations of strength degradation in-vitro showed to be useful in interpreting failure behavior in-vivo. The parameter Kth stood out as a better predictor of clinical performance in detriment to the SCG n parameter. SIGNIFICANCE: Fatigue parameters obtained from cyclic loading experiments are more reliable predictors of the mechanical performance of contemporary dental CAD/CAM restoratives than quasi-static mechanical properties.
EVALuna2:34638

Chairside vs. labside ceramic inlays: Effect of temporary restoration and adhesive luting on enamel cracks and marginal integrity - Frankenberger, Roland; Kraemer, Norbert; Appelt, Andreas; Lohbauer, Ulrich; Naumann, Michael; Roggendorf, Matthias J. (Dental Materials, 2011)
Objectives: To assess the influence of different temporary restorations and luting techniques of labside and chairside ceramic inlays on enamel defects and marginal integrity. Methods: 120 extracted human third molars received MOD preparations with one proximal box each limited in either enamel or dentin. 64 Cerec 2 inlays and 56 IPS Empress I inlays were randomly assigned to the following groups (fabrication mode: chairside (CS) = no temporary restoration (TR), labside (LS) = TR with Luxatemp (L) inserted with TempBond NE, or Systemp.inlay (SI) without temporary cement), luting technique: SV = Syntac/Variolink II, RX = RelyX Unicem: A: Cerec inlays were luted with (1) CS/SV. (2) CS/SV/Heliobond separately light-cured. (3) CS/RX. (4) LS/L/SV. (5) LS/L/RX. (6) LS/SI/SV. (7) LS/SI/RX. (8) LS/SI/RX with selective enamel etching. B: Empress. (9) L/SV. (10) L/SV/Heliobond separately light-cured. (11) L/RX. (12) SI/SV. (13) SI/SV, Heliobond separately lightcured. (14) SI/RX. (15) SI/RX after selective enamel etching. Before and after thermomechanical loading (TML: loading time of TR 1000 × 50 N + 25 thermocycles (TC) between +5 °C and +55 °C; clinical simulation: 100,000 × 50 N + 2500 TC) luting gaps, enamel cracks, and marginal adaptation to enamel and dentin were determined under an SEM microscope (200×) using replicas. Results: Loading time of temporary restorations negatively affected enamel integrity and enamel chipping (p < 0.05). Luxatemp resulted in less enamel cracks than Systemp.inlay (p < 0.05). Syntac/Variolink achieved better marginal enamel quality than RelyX Unicem in all groups (p < 0.05). Marginal quality in dentin revealed no differences when no temporary cement was used (p > 0.05). Temporary cement negatively affected dentin margins when RelyX Unicem was used (p < 0.05). Significance: Chairside-fabricated Cerec inlays reduce the risk of enamel cracks and marginal enamel chipping due to omitted temporary restorations. Syntac/Variolink revealed a significantly better performance than RelyX Unicem. © 2011 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Adhesives; Ceramics; Cerec; Composite; Empress; Enamel crack; Marginal gap; Self-adhesive

Characterization of heat-polymerized monomer formulations for dental infiltrated ceramic networks - Tiu, Janine; Belli, Renan; Lohbauer, Ulrich (Applied Sciences, 2021)
(1) Objectives: This work examined properties of dental monomer formulations of an aromatic dimethacylate (BisGMA), aliphatic urethane dimethacrylate (UDMA), and triethylene glycol dimethacrylate (TEGDMA). The monomers were combined in different ratio formulations and heat-polymerized containing the initiator benzoyl peroxide (BPO) specifically for the purpose of infil-tration into polymer-infiltrated composite structures. (2) Methods: The monomers were combined in different weight ratios and underwent rheological analysis (viscosity and temperature dependence), degree of conversion, and mechanical properties (elastic modulus, hardness, fracture toughness). (3) Results: Rheological properties showed Newtonian behavior for monomers with a large dependence on temperature. The addition of BPO allowed for gelation in the range of 72.0–75.9◦ C. Degree of conversion was found between 74% and 87% DC, unaffected by an increase of TEGDMA (up to 70 wt%). Elastic modulus, hardness, and fracture toughness were inversely proportional to an increase in TEGDMA. Elastic modulus and hardness were found slightly increased for UDMA versus BisGMA formulations, while fracture toughness ranged between 0.26 and 0.93 MPa.m0.5 for UDMA-and 0.18 and 0.68 MPa.m0.5 for BisGMA-based formulations. (4) Significance: Heat-polymerization allows for greater range of monomer formulations based on viscosity and degree of conversion when selecting for infiltrated composite structures. Therefore, selection should be based on mechanical properties. The measured data for fracture toughness combined with the reduced viscosity at higher UDMA:TEGDMA ratios favor such formulations over BisGMA:TEGDMA mixtures.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Heat polymerization; Mechanical properties; Methacrylate monomer; Resin infiltration

Characterization of residual stresses in zirconia veneered bilayers assessed via sharp and blunt indentation - Wendler, Michael; Belli, Renan; Petschelt, Anselm; Lohbauer, Ulrich (Dental Materials, 2015)
The present study evaluated the effect of the coefficient of thermal expansion (CTE) mismatch and the cooling protocol on the distribution of residual stresses and crack propagation in veneered zirconia bilayers.Ceramic discs with two different CTEs (Vita VM9 and Lava Ceram) were fired onto zirconia plates and cooled following a slow (0.5°C/s) or a fast (45°C/s) cooling protocol. The residual stress distribution throughout the veneer thickness was assessed by means of depth-wise Vickers indentation after sequentially sectioning the bilayers parallel compared to normal to the interface. A mathematical solution for the residual stress distribution was used as reference. Additionally, Hertzian cone crack propagation in the veneers was induced by cyclic contact loading and measured at different number of cycles to estimate the crack growth rate.The higher CTE mismatch of the VM9 group generated an important stress gradient with high compressive residual stresses near the interface, hindering the crack propagation. The low CTE mismatch group (Lava Ceram) developed only a slight stress gradient and higher cone crack growth rates. No differences were observed between the two cooling protocols applied regarding stress magnitude and crack propagation behavior.The CTE mismatch has a predominant role in the generation of residual stress gradients within the veneer, which directly influences contact-induced crack propagation. Based on the results, the cooling protocol had no significant effect on the residual stress distribution in zirconia-veneer bilayers.
EVALuna2:24676

Concurrent kinetics of crystallization and toughening in multicomponent biomedical SiO2-Li2O-P2O5-ZrO2 glass-ceramics - Lubauer, Julia; Belli, Renan; Petschelt, Anselm; Cicconi, Maria Rita; Hurle, Katrin; Lohbauer, Ulrich (Journal of Non-Crystalline Solids, 2021)
We investigate here the crystallization kinetics of two pre-crystallized multicomponent dental glass-ceramics (IPS e.max® CAD, Ivoclar-Vivadent; Suprinity® PC, Vita Zahnfabrik) by interrupting the heat treatment at different periods of the non-isothermal and isothermal stage at 840°C. Differential scanning calorimetry (DSC) was used to characterize the crystallization peaks of the pre-crystallized and the base glass, and dilatometry was used to determine the coefficient of thermal expansion and Tg after different times at the maximum temperature. The evolution of crystallinity was tracked by XRD, while the evolution of fracture toughness was obtained by the ball-on-three-balls surface crack in flexure method. The change in microstructural features was made visible using FE-SEM. We show that the isothermal stage is dominated by the transformation of Li2SiO3 in Li2Si2O5, inducing the impingement of nanocrystals into clusters. The residual glass became thereby less polymerized. The kinetics of toughening followed closely the evolution of crystallinity in both systems.
CRIS-Team Scopus Importer:2021-02-12

Contemporary CAD/CAM Materials in Dentistry - Tiu, Janine; Belli, Renan; Lohbauer, Ulrich (Current Oral Health Reports, 2019)
Purpose of Review: To present an update on the current CAD/CAM materials in restorative dentistry. Recent Findings: Important contributions are seen in updated mechanical properties of CAD/CAM materials, new insights in lithium silicate systems, and development in translucent zirconia. Many materials are arriving at optimized processing procedures and further development will come from new strategies and systems. Increasing our understanding of CAD/CAM materials will improve their use and indications and drive innovation. Summary: A general update was provided by classifications, mechanical properties, and clinical considerations by providing commentary on recent significant contributions.
CRIS-Team Scopus Importer:2021-04-20
Keywords: CAD/CAM; Dental restorative materials; Glass-ceramics; Mechanical properties; Zirconia

Coulometric titration of water content and uptake in CAD/CAM chairside composites - Faria-e-Silva, Andre; Heckel, Lea; Belli, Renan; Lohbauer, Ulrich (Dental Materials, 2022)
Objectives: This study aimed to evaluate the water content and uptake of CAD/CAM chairside composites over 60 days using coulometric Karl Fischer (KF) titration. Methods: Rectangular plates (10 ×10×1 mm3 of thickness) were cut from the blocks of composites Cerasmart 270 (CS), Katana Avencia (KA), Grandio Blocs (GB), and Lava Ultimate (LU). Specimens were stored in distilled water for up to 60 days at 37 °C, and non-stored specimens were used as a control (n = 5). Specimens were isothermally heated at 200 °C, and the water content was evaporated and transferred to the titration cell throughout a nitrogen gas flow. The KF coulometer determined the percentage of water in each specimen. Data were analyzed by 2-way ANOVA and Tukey`s test (α = 0.05). Results: The water content of non-stored specimens ranged from 0.29 to 1.66 wt% (6.9–32.9 μg/mm3) for GB and LU, respectively. The water content increased underwater storage (0.82–2.96 wt% after 60 days). The extend of water sorption (11.9–26.1 μg/mm3) among the materials was directly related to their base water content. No additional water content increase was observed after 7 (LU and KA) or 21 (GB and CS) days. Measuring the water content in wt% or μg/mm3 affected the ranking of materials when KA and CS were analyzed. Significance: Composites with higher base water content also presented higher water sorption. KF titrationshowed to be a reliable method to measure the water sorption of composites, including their base water content.
CRIS-Team Scopus Importer:2022-05-06
Keywords: CAD/CAM; Karl Fischer titration; Resin composite; Water sorption

Crack growth behavior of a biomedical polymer-ceramic interpenetrating scaffolds composite in the subcritical regimen - Belli, Renan; Zorzin, José Ignacio; Petschelt, Anselm; Lohbauer, Ulrich; Tommaso Rocca, Giovanni (Engineering Fracture Mechanics, 2020)
We subjected a commercial dental composite formed by interconnecting polymer-ceramic scaffolds to extensive quasi-static, static and cyclic experiments under biaxial flexure. By this we meant to obtain static and cyclic subcritical crack growth exponents that, based on established relationships describing the degradation of frictional bridging mechanisms, challenging the notion of a suggested R-curve behavior. By exploring the fracture statistics of specimens with increasing effective volumes and effective areas, we demonstrated the presence of a bi-modal defect size distribution in disaccord with the Weibull behavior across length scales. Lifetime distributions seemed to follow the strength distributions, and were used to derive crack growth velocity diagrams for combined levels of applied stress. Ultimately, the claim of an R-curve behavior could not be supported based on the absence of any significant cyclic fatigue effect, i.e. bridging degradation.
CRIS-Team Scopus Importer:2020-04-03

Crack growth rates in lithium disilicates with bulk (mis)alignment of the Li2Si2O5 phase in the [001] direction - Kirsten, Julia; Belli, Renan; Wendler, Michael; Petschelt, Anselm; Hurle, Katrin; Lohbauer, Ulrich (Journal of Non-Crystalline Solids, 2020)
Processing-induced alignment of Li2Si2O5 crystals in biomedical lithium disilicate glass-ceramics have been shown to increase the monotonic resistance to fracture and better simulate the mechanical behavior of natural dental tissues. The (mis)orientation of the [001] direction in the Li2Si2O5 crystal phase relative to the crack growth plane was induced by injection-molding of a high aspect ratio composition in order to determine the effect of crystal alignment. The role of particulate geometry was assessed by comparing two compositions having randomly oriented Li2Si2O5 crystals of similar phase fraction but dissimilar crystal aspect ratios. Static and cyclic fatigue experiments in varying frequencies and R-ratios were conducted to clarify the degradation of crack bridging mechanisms induced by the crystal phase during repetitive opening and closure of the crack faces. Both crystal alignment and aspect ratio showed to play important roles in affecting the subcritical crack growth resistance the lifetime of lithium disilicate biomedical components.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Anisotropy; Crystal alignment; Cyclic fatigue; Lithium disilicate; Static fatigue

Crack-healing during two-stage crystallization of biomedical lithium (di)silicate glass-ceramics - Belli, Renan; Lohbauer, Ulrich; Götz-Neunhoeffer, Friedlinde; Hurle, Katrin (Dental Materials, 2019)
Objective: The study is aimed to evaluate the two single commercially available two-step lithium-(di)silicate systems by analyzing their parent glass composition and studying the quantitative crystalline and glass phase evolution during the second stage heat-treatment. The mechanical repercussions of the crystallization firing were evaluated using strength and fracture toughness tests. Methods: XRF and ICP-OES were used to determine the oxide composition of the parent glasses in Suprinity PC (Vita Zahnfabrik) and IPS e.max CAD (Ivoclar-Vivadent). The crystalline phase of both materials was determined by quantitative XRD and the G-factor method in the partially and post-crystallization states. The oxide composition of the residual glass phase was derived by subtracting the chemistry of the crystalline phase fractions from the parent glass composition. Mechanical testing of biaxial flexural strength and fracture toughness were used to demonstrate how crack-like defects behave during crystallization. Results: The two tested lithium (di)silicate systems showed strong differences in oxide composition of the parent glass. This showed to influence the transformation of lithium metasilicate in lithium disilicate, with the former remaining in high vol.% fraction in the post-crystallization Suprinity PC. In IPS e.max CAD cristobalite precipitated at the surface during the second-heat treatment. Strength and fracture toughness tests revealed that crack in both materials, whether introduced by grinding or indentation, heal during the crystallization firing. Cristobalite seemed to have contributed to a surface strengthening effect in IPS e.max CAD. Significance: Accurate crystalline phase quantification aids in the determination of the residual glass composition in dental glass-ceramics. For both systems crystallization firing induced healing of cracks generated by CAM grinding.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Dental; Fracture toughness; Glass-ceramic; Lithium disilicate; Lithium silicate; X-ray diffraction

Cytocompatibility of siloxane-containing vaterite/Poly(L-lactic acid) composite coatings on metallic magnesium - Yamada, Shinya; Maeda, Hirotaka; Obata, Akiko; Lohbauer, Ulrich; Yamamoto, Akiko; Kasuga, Toshihiro (Materials, 2013)
Poly(L-lactic acid)-based films which include 60 wt % of vaterite (V) or siloxane-containing vaterite (SiV) were coated on a pure magnesium substrate, denoted by PLLA/V or PLLA/SiV, respectively, to suppress early corrosion and improve its cytocompatibility. Both coating films adhered to the Mg substrate with 2.3-2.8 MPa of tensile bonding strength. Soaking test for 7 days in α-modified minimum essential medium revealed that the morphological instability of the PLLA/V film caused a higher amount of Mg2+ ion to be released from the coating sample. On the other hand, in the case of the coating with the PLLA/SiV film, no morphological change even after the soaking test was observed, owing to the suppression of the degradation rate. In cell culture tests, the proliferation of mouse osteoblast-like cell (MC3T3-E1) was significantly enhanced by both coatings, in comparison with the uncoated magnesium substrate. The cell morphology revealed that a few less-spread cells were observed on the PLLA/V film, while more elongated cells were done on the PLLA/SiV film. The cells on the PLLA/SiV film exhibited an extremely higher alkaline phosphatase activity after 21 days of incubation than that on the PLLA/V one. The PLLA/SiV film suppressed the early corrosion and enhanced cytocompatibility on metallic magnesium. © 2013 by the authors; licensee MDPI, Basel, Switzerland.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Coating; Composite; Magnesium; Poly(L-lactic acid); Vaterite (calcium carbonate)

Degree of conversion of luting resins around ceramic inlays in natural deep cavities: A micro-raman spectroscopy analysis - Lohbauer, Ulrich; Pelka, Matthias; Belli, Renan; Schmitt, J.; Mocker, E.; Jandt, K. D.; Müller, Frank (Operative Dentistry, 2010)
This study evaluated the degree of conversion (Ü) of luting agents around ceramic inlays placed in deep natural cavities. Thirty-six cylindrical Class I cavities (diameter = 4 mm, depth = 4 mm) were prepared in freshly extracted human teeth and randomly divided according to the luting materials used for luting CAD/CAM fabricated inlays (Empress CAD). The dual-cure resin cements Clearfil Esthetic Cement and Variolink II Low and the light-cure composites Grandio Flow and Grandio were luted using the total-etch technique. The self-adhesive dual-cure cements RelyX Unicem and Maxcem Elite were used as recommended by the manufacturer. All of the restorations were photo-activated using a quartz halogen unit (Elipar TriLight; 750 mW/cm2) for 40 seconds. After 24 hour dry-storage in the dark, all the teeth were vertically sectioned into two halves (n=12 per group) using a slow-speed diamond-saw in the bucco-vestibular direction under constant water lubrication to avoid specimen heating. The DC of the luting materials was measured by vibrational spectroscopy using a μ-Raman spectrometer at depths of 1, 3 and 4 mm on each side of the tooth halves (n=24). Disc-shaped samples were produced for measurement of the maximum Ü of each material. Two-way ANOVA and the StudentNewman-Keuls post-hoc test were used in the statistical analysis (α=0.05). All the materials showed no statistical differences in degree of conversion at all tested depths, except for Grandio Flow and Maxcem Elite. Dual-cure and light-cure luting materials showed polymerization homogeneity around ceramic inlays, although dual-cure conventional resin cements tended to show an overall higher conversion.
CRIS-Team Scopus Importer:2023-01-23

Dental ceramics: a review of new materials and processing methods - da Silva, Lucas Hian; de Lima, Erick; Miranda, Ranulfo Benedito de Paula; Favero, Stéphanie Soares; Lohbauer, Ulrich; Cesar, Paulo Francisco (Brazilian Oral Research, 2017)
The evolution of computerized systems for the production of dental restorations associated to the development of novel microstructures for ceramic materials has caused an important change in the clinical workflow for dentists and technicians, as well as in the treatment options offered to patients. New microstructures have also been developed by the industry in order to offer ceramic and composite materials with optimized properties, i.e., good mechanical properties, appropriate wear behavior and acceptable aesthetic characteristics. The objective of this literature review is to discuss the main advantages and disadvantages of the new ceramic systems and processing methods. The manuscript is divided in five parts: I) monolithic zirconia restorations; II) multilayered dental prostheses; III) new glass-ceramics; IV) polymer infiltrated ceramics; and V) novel processing technologies. Dental ceramics and processing technologies have evolved significantly in the past ten years, with most of the evolution being related to new microstructures and CAD-CAM methods. In addition, a trend towards the use of monolithic restorations has changed the way clinicians produce all-ceramic dental prostheses, since the more aesthetic multilayered restorations unfortunately are more prone to chipping or delamination. Composite materials processed via CAD-CAM have become an interesting option, as they have intermediate properties between ceramics and polymers and are more easily milled and polished.
EVALuna2:24701

Dental Ceramics: Fracture Mechanics and Engineering Design - Lohbauer, Ulrich; Belli, Renan (Springer International Publishing, 2022)
This book is an evidence-based update on recent most significant advances in dental ceramics, specifically related to the relationships between composition, microstructure and mechanical behavior. Readers will find an introduction to the chemistry of dental ceramics as well as information about the technological progress and practical requirements restorative materials need to satisfy for long-lasting structural integrity. The book uses mechanistic approaches to address failure mechanisms from controlled experiments thus providing the tools for the application of sound research methodologies in the field. It is targeted for researcher and dentists interested in the field of dental ceramic materials and fracture mechanics.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Brittle failure; Dental ceramics; Long-lasting dental esthetics; Microstrucutre of dental ceramics; Restorative dental materials

Dental glass ionomer cements as permanent filling materials? -Properties, limitations and future trends - Lohbauer, Ulrich (Materials, 2010)
Glass ionomer cements (GICs) are clinically attractive dental materials that have certain unique properties that make them useful as restorative and luting materials. This includes adhesion to moist tooth structures and base metals, anticariogenic properties due to release of fluoride, thermal compatibility with tooth enamel, biocompatibility and low toxicity. The use of GICs in a mechanically loaded situation, however, has been hampered by their low mechanical performance. Poor mechanical properties, such as low fracture strength, toughness and wear, limit their extensive use in dentistry as a filling material in stress-bearing applications. In the posterior dental region, glass ionomer cements are mostly used as a temporary filling material. The requirement to strengthen those cements has lead to an ever increasing research effort into reinforcement or strengthening concepts. © 2010 by the authors.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Brittleness; Clinical; Coating; Fatigue; Glass fibers; Glass ionomer cement; Porosity; Resin modification; Restoration; Strength; Wear

Dental materials for primary dentition: are they suitable for occlusal restorations? A two-body wear study - Lazaridou, Dimitra; Belli, Renan; Krämer, N.; Petschelt, Anselm; Lohbauer, Ulrich (European archives of paediatric dentistry : official journal of the European Academy of Paediatric Dentistry, 2015)
This was to evaluate the wear resistance of different materials, compomers, resin-modified glass ionomer cements (RMGICs), glass ionomer cements (GICs), used for posterior restorations in primary teeth and to compare the results with the reference material, amalgam.Eight specimens of each material were subjected to two-body wear test, using a chewing simulator. The wear region of each material was examined under a profilometer, measuring the vertical loss (?m) and the volume loss (mm(3)) of the materials.The results showed significant differences of vertical loss and volume loss of the test materials (p < 0.001). Amalgam had the highest wear resistance. Twinky Star (compomer) had the lowest vertical loss and volume loss. There was no significant difference of vertical loss among compomers, Dyract Extra, Dyract Flow and Dyract Posterior. Riva Self Cure (GIC) had no statistically significant difference compared with the compomers (except Twinky Star). No statistically significant difference was found also between Equia (GIC) and Ketac Moral (GIC) with Dyract Extra (Compomer). RMGICs were found to have the lowest wear resistance.For the statistical analysis, the PASW 20.0 (SPSS Statistics, IBM, Chicago) package was used. Means and standard deviations were measured with descriptive statistics and analyzed using one-way ANOVA.Compomers and some GICs, that have moderate wear resistance, may be sufficient for occlusal restorations in primary dentitions.
EVALuna2:24677

Descriptions of crack growth behaviors in glass-ZrO2 bilayers under thermal residual stresses - Belli, Renan; Wendler, Michael; Zorzin, José Ignacio; Petschelt, Anselm; Tanaka, Carina B.; Meira, Josete; Lohbauer, Ulrich (Dental Materials, 2016)
This study was intended to separate residual stresses arising from the mismatch in coefficients of thermal expansion between glass and zirconia (ZrO2) from those stresses arising solely from the cooling process. Slow crack growth experimentes were undertaken to demonstrate how cracks grow in different residual stress fields.Aluminosilicate glass discs were sintered onto ZrO2 to form glass-ZrO2 bilayers. Glass discs were allowed to bond to the ZrO2 substrate during sintering or prevented from bonding by means of coating the ZrO2 with a thin boron nitrade coating. Residual stress gradients on "bonded" and "unbonded" bilayers were assessed using birefringence measurements. Unbonded glass discs were further tested under biaxial flexure in dynamic fatigue conditions in order to evaluate the effect of residual stress on the slow crack growth behavior.When fast-ccoling was induced, residual tensile stresses on the glass increased significantly on the side toward the ZrO2 substrate. By allowing the bond between glass and ZrO2, those tensile stresses observed in unbonded specimens are overwhelmed by the contraction mismatch stresses between the ZrO2 substrate and the glassy overlayer. Specimens containing residual tensile stresses on the bending surface showed a time-dependent strength increase in relation to stress-free annealed samples in the dynamic biaxial bending test, with this effect being dependent on the magnitude of the residual tensile stress. The phenomenon observed is explained here on the basis of the water toughening effect, in which water diffuses into the glass promoting local swelling. An additional residual tensile stress at the crack tip adds an applied-stress-independent (Kres) term to the total tip stress intensity factor (Ktip), increasing the stress-enhanced diffusion and the shielding of the crack tip through swelling of the crack faces.Residual stresses in the glass influence the crack growth behavior of veneered-ZrO2 bilayered dental prostheses. The role of water in crack growth might be of higher complexity when residual stresses are present in the glass layer.
EVALuna2:24680

Determination of Water Content in Direct Resin Composites Using Coulometric Karl Fischer Titration - Faria-e-Silva, André; Heckel, Lea; Belli, Renan; Lohbauer, Ulrich (Materials, 2022)
This study evaluated the water content and sorption of direct composites over 60 days using coulometric Karl Fischer titration (KFT). Plate-shaped specimens (10 × 10 × 1 mm3 of thickness) were built up using the composites Clearfil Majesty Posterior (CM), Grandio SO (GS), and Filtek Supreme XT (FS). Water contents were determined in non-stored specimens (control) or after storage in distilled water for up to 60 days (n = 5). The amount of water transferred from the specimens heated at 200 °C (isothermal mode) was measured in the Coulometer. The water content of non-stored specimens ranged from 0.28 to 1.69 wt% (5.6 to 31.2 μg/mm3) for GS and FS, respectively. The highest values of water sorption were observed for FS (25.3 μg/mm3 after 60 days). GS and CM showed similar water sorption after 60 days (≈9 μg/mm3), but an ultimate higher water content was observed for CM (0.9 wt%; 22.0 μg/mm3) than GS (0.7 wt%; 14.8 μg/mm3). Except for CM, no significant water sorption was observed between 21 and 60 days of storage. Since all composites presented some base water content, water sorption data alone do not account for the ultimate water content in direct resin-based composites.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Karl Fischer titration; resin composite; water sorption

Development of a hoop-strength test for model sphero-cylindrical dental ceramic crowns: FEA and fractography - Belli, Renan; Völkl, Harald; Csato, Stefan; Tremmel, Stephan; Wartzack, Sandro; Lohbauer, Ulrich (Journal of the European Ceramic Society, 2020)
Here we describe the development of a mechanical test that simulates a circumferential “hoop-stress” at the margins of model dental ceramic crowns. A simplified sphero-cylindrical geometry was modelled in two thicknesses and machined out of two glass-ceramic materials. The specimens were loaded by a conical metallic piston to induce circumferential hoop-stresses at the margins until fracture. Broken specimens were fractographically analyzed to determine the location of the fracture origin and to measure the dimensions of the critical defect, allowing the calculation of the stress at failure from fracture mechanics relations. For thick specimens, machining defects at the outer margins barely played a role in fracture initiation. For thin specimens, outer defects started to dominate the failure mode. CAD/CAM machining showed to predispose thinner margins to early fracture. Crowns should be designed with increased thickness in order to minimize the effect of marginal damage in the circumferential stress field inducing fracture.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Dental; Finite element analysis; Fractography; Glass-ceramic; Mechanical test

Development of Y-TZP/MWCNT-SiO2 nanocomposite for dental protheses - da Silva, Lucas Hian; Rinaldi, Laura Ajamil; Lazar, Dolores Ribeiro Ricci; Ussui, Valter; Tango, Rubens Nisie; Belli, Renan; Lohbauer, Ulrich; Cesar, Paulo Francisco (Journal of the Mechanical Behavior of Biomedical Materials, 2023)
Y-TZP/MWCNT-SiO2 nanocomposite was synthesized by co-precipitation and hydrothermal treatment methods. After the characterization of the MWCNT-SiO2 powder, specimens were obtained from the synthesized material Y-TZP/MWCNT-SiO2 by uniaxial pressing for a second characterization and later comparison of its optical and mechanical properties with the conventional Y-TZP. The MWCNT-SiO2 was presented in bundles of carbon nanotubes coated by silica (mean length: 5.10 ± 1.34 μm /D90: 6.9 μm). The composite manufactured was opaque (contrast ratio: 0.9929 ± 0.0012) and had a white color with a slightly difference from the conventional Y-TZP (ΔE00: 4.4 ± 2.2) color. The mechanical properties of Y-TZP/MWCNT-SiO2: vickers hardness (10.14 ± 1.27 GPa; p = 0.25) and fracture toughness (4.98 ± 0.30 MPa m1/2; p = 0.39), showed no significant difference from the conventional Y-TZP (hardness: 8.87 ± 0.89; fracture toughness: 4.98 ± 0.30 MPa m1/2). However, for flexural strength (p = 0.003), a lower value was obtained for Y-TZP/MWCNT-SiO2 (299.4 ± 30.5 MPa) when compared to the control Y-TZP (623.7 ± 108.8 MPa). The manufactured Y-TZP/MWCNT-SiO2 composite presented satisfactory optical properties, however the co-precipitation and hydrothermal treatment methods need to be optimized to avoid the formation of porosities and strong agglomerates, both from Y-TZP particles and MWCNT-SiO2 bundles, which lead to a significant decrease in the material flexural strength.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Co-precipitation of mixed hydroxides; Hydrothermal treatment; Multi-walled carbon nanotube; Yttria-stabilized tetragonal zirconia polycrystals

Dimensional changes of CAD/CAM polymer crowns after water aging – An in vitro experiment - Schepke, U.; Filius, D.; Lohbauer, Ulrich; la Bastide-van Gemert, S.; Gresnigt, M. M.M.; Cune, M. S. (Journal of the Mechanical Behavior of Biomedical Materials, 2022)
Computer-Aided Design/Computer-Aided Manufacturing (CAD/CAM) polymers can potentially replace traditional materials used for manufacturing indirect restorations. In 2012, Lava Ultimate (LU) was introduced as a highly suitable material for implant-supported single crowns. Three years after its introduction, the manufacturer issued a change in indication for the material, implying that they no longer considered the material to be suitable for crown indications due to debonding issues. A clinical trial with implant-borne Lava Ultimate crowns bonded to zirconia abutments revealed that 80 percent of the LU crowns showed debonding from the abutment within one year, whereas no debonding occurred when an alternative full-ceramic restoration material was used. These results suggest that the material itself had been the cause of the debonding. However, the exact reason for the debonding remained unclear. Water uptake in resin methacrylates like LU is known to cause dimensional changes resulting in mechanical stress on the RelyX Ultimate (RU) cement. The purpose of this study is to quantify the dimensional changes in LU caused by water uptake and relate these dimensional changes to the failure of the RU cement. Twenty-five identical LU-crowns were divided into three groups. 10 LU-crowns with abutment and 10 crowns without abutments were stored in water for 23 days and were only removed for measurement. Five crowns served as a control to calibrate the measurements. The internal diameter was measured eight times with a TS 460 Heidenhain touch probe. For visualization purposes, one crown was also 3D scanned before and after water treatment. The results showed that after 23 days in water the mean increase in diameter for the groups with and without abutment was 36.6 μm (SD = 35,1) and 36.7 μm (SD = 26,5) respectively. Mixed effects modelling indicated no significant between-group differences at any time point. Exposure of LU to water results in dimensional changes causing mechanical stress on the crown-abutment complex. It can be estimated that RU cement fails after an expansion of more than 4 μm. Within the limitations of this in vitro study, it can be concluded that the dimensional changes induced by water uptake can cause debonding issues. As more CAD/CAM polymers for restorative purposes are expected to be developed, the results of this study should stimulate manufacturers to quantify their products’ dimensional changes in a wet environment before market release.
CRIS-Team Scopus Importer:2022-03-18
Keywords: CAD/CAM polymer; Lava ultimate; Premature market release; Water uptake

Do Contaminating Substances Influence the Rheological Properties of Root Canal Sealers? - de Freitas, Jéssica Vavassori; Ebert, Johannes; Mazzi-Chaves, Jardel Francisco; de Sousa-Neto, Manoel Damião; Lohbauer, Ulrich; Baratto-Filho, Flares (Journal of Endodontics, 2019)
Introduction: This study evaluated the effect of residual substances derived from irrigant solutions and intracanal medications on the rheological properties of a silicone, gutta-percha, and bioactive glass–based sealer in comparison with an epoxy resin–based sealer. Methods: Thin films of contaminants (0.5 μL) (3% sodium hypochlorite [NaOCl], chlorhexidine digluconate [CHX], 17% EDTA, calcium hydroxide, 40% citric acid, or distilled water [DW]) were applied along with freshly mixed GuttaFlow Bioseal (GFB; Coltene/Whaledent, Langenau, Germany) or AH Plus Jet (Dentsply DeTrey, Konstanz, Germany) on the lower plate of a dynamic rheometer. Rheological measurements were performed in oscillating mode at the strain amplitude, angular frequency, and constant temperature of 0.01%, 10 rad/s, and 37°C, respectively. Samples without contaminants served as controls. All measurements were performed 5 times. The Kolmogorov-Smirnov test and 1-way analysis of variance followed by the Student-Newman-Keuls test were performed to analyze the results (P < .05). Results: The contaminants did not alter the setting time of GFB compared with the controls; however, CHX and calcium hydroxide decreased its complex viscosity (ƞ*) (P < .05). The setting time of AH Plus Jet was increased by DW, CHX, citric acid, and EDTA (P < .05). All contaminants decreased its ƞ* at the setting point (P < .05). NaOCl led to the greatest alteration of its rheological parameters. Conclusions: Irrigant solutions and intracanal medications adversely affected at least 1 of the tested rheological properties of both sealers, except for DW and 3% NaOCl, which did not alter any rheological property of GFB.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Epoxy resin–based sealer; intracanal medicament; irrigation solution; rheological property; silicon-based sealer

Edge chipping damage in lithium silicate glass-ceramics induced by conventional and ultrasonic vibration-assisted diamond machining - Juri, Afifah Z.; Belli, Renan; Lohbauer, Ulrich; Ebendorff-Heidepriem, Heike; Yin, Ling (Dental Materials, 2023)
Objectives: Diamond machining of lithium silicate glass-ceramics (LS) induces extensive edge chipping damage, detrimentally affecting LS restoration functionality and long-term performance. This study approached novel ultrasonic vibration-assisted machining of pre-crystallized and crystallized LS materials to investigate induced edge chipping damage in comparison with conventional machining. Methods: The vibration-assisted diamond machining was conducted using a five-axis ultrasonic high-speed grinding/machining machine at different vibration amplitudes while conventional machining was performed using the same machine without vibration assistance. LS microstructural characterization and phase development were performed using scanning electron microscopy (SEM) and x-ray diffraction (XRD) techniques. Machining-induced edge chipping depths, areas and morphology were also characterized using the SEM and Java-based imaging software. Results: All machining-induced edge chipping damages resulted from brittle fractures. The damage scales, however, depended on the material microstructures; mechanical properties associated with the fracture toughness, critical strain energy release rates, brittleness indices, and machinability indices; and ultrasonic vibration amplitudes. Pre-crystallized LS with more glass matrix and lithium metasilicate crystals yielded respective 1.8 and 1.6 times greater damage depths and specific damage areas than crystallized LS with less glass matrix and tri-crystal phases in conventional machining. Ultrasonic machining at optimized amplitudes diminished such damages by over 50 % in pre-crystallized LS and up to 13 % in crystallized LS. Significance: This research highlights that ultrasonic vibration assistance at optimized conditions may advance current dental CAD/CAM machining techniques by significant suppression of edge chipping damage in pre-crystallized LS.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Diamond machining; Edge chipping damage; Lithium silicate glass-ceramics; Microstructure; Ultrasonic vibration assistance

Effect of double-layer application on dentin bond durability of one-step self-etch adhesives - Taschner, Michael; Kümmerling, M.; Lohbauer, Ulrich; Breschi, Lorenzo; Petschelt, Anselm; Frankenberger, R. (Operative Dentistry, 2014)
The aim of this in vitro study was 1) to analyze the influence of a double-layer application technique of four one-step self-etch adhesive systems on dentin and 2) to determine its effect on the stability of the adhesive interfaces stored under different conditions.Four different one-step self-etch adhesives were selected for the study (iBondSE, Clearfil S(3) Bond, XenoV(+), and Scotchbond Universal). Adhesives were applied according to manufacturers' instructions or with a double-layer application technique (without light curing of the first layer). After bonding, resin-dentin specimens were sectioned for microtensile bond strength testing in accordance with the nontrimming technique and divided into 3 subgroups of storage: a) 24 hours (immediate bond strength, T0), b) six months (T6) in artificial saliva at 37°C, or c) five hours in 10 % NaOCl at room temperature. After storage, specimens were stressed to failure. Fracture mode was assessed under a light microscope.At T0, iBond SE showed a significant increase in microtensile bond strength when the double-application technique was applied. All adhesive systems showed reduced bond strengths after six months of storage in artificial saliva and after storage in 10% NaOCl for five hours; however at T6, iBond SE, Clearfil S(3) Bond, and XenoV(+) showed significantly higher microtensile bond strength results for the double-application technique compared with the single-application technique. Scotchbond Universal showed no difference between single- or double-application, irrespective of the storage conditions.The results of this study show that improvements in bond strength of one-step self-etch adhesives by using the double-application technique are adhesive dependent.
EVALuna2:24657

Effect of sintering parameters on phase evolution and strength of dental lithium silicate glass-ceramics - Lohbauer, Ulrich; Belli, Renan; Abdalla Alonso, Alexandre; Götz-Neunhoeffer, Friedlinde; Hurle, Katrin (Dental Materials, 2019)
Objective: With the establishment of CAD/CAM technology, competing lithium silicate based formulations have been introduced for clinical use, but little is known about their phase composition. Here we investigate a commercially available SiO2-Al2O3-K2O-Li2O-P2O5-ZrO2 system to evaluate the crystal phase evolution during the second heat treatment by changing the main crystallization parameters. Methods: With a focus on the final stage of crystallization, we characterized the dimensional changes in the crystallographic structure of the residual Li2SiO3 and the lithium orthophosphate (Li3PO4) phases with variations in crystallization parameters, i.e. time, temperature and cooling rate over the range of the glass transition temperature Tg. The phase fractions (crystalline and glass) and the sizes of coherent scattering domains (CSDs) were resolved by means of quantitative X-Ray Diffraction using Rietveld refinement combined with an external standard method (G-factor). Biaxial flexure testing was conducted to evaluate the influence of crystallization parameters on the characteristic strength and natural defect distribution. Results: An increase in crystallization temperature from 840 to 880 °C resulted in a significant reduction of the Li2Si2O5 content, which indicated a reversion of the Li2SiO3 to Li2Si2O5 phase transformation. Reduction to 800 °C had no significant effect. Furthermore, the CSD sizes of Li2SiO3 and Li3PO4 continuously increased with increasing temperature, which was accompanied by an increase in strength parameters. Reducing the cooling rate over the range of Tg resulted in an increased strength at low failure probabilities. Significance: These findings help to establish recommendations for adjustment of the crystallization protocol, which has potential to increase the clinical reliability of the material investigated.
CRIS-Team Scopus Importer:2019-08-09
Keywords: Ceramics; Crystallization; Materials science; Restorative materials; X-ray Crystallography

Erratum: Mechanical fatigue degradation of ceramics versus resin composites for dental restorations (Dental Materials (2014) 30:4 (424-432)) - Belli, Renan; Geinzer, Eva; Muschweck, Anna; Petschelt, Anselm; Lohbauer, Ulrich (Dental Materials, 2014)
CRIS-Team Scopus Importer:2023-01-23

Evaluation of wear behavior of dental restorative materials against zirconia in vitro - Maier, Eva; Grottschreiber, Christine-Maria; Knepper, Ines; Opdam, Niek; Petschelt, Anselm; Loomans, Bas; Lohbauer, Ulrich (Dental Materials, 2022)
Objectives: To evaluate two-body wear (2BW) and three-body wear (3BW) of different CAD/CAM and direct restorative materials against zirconia using a dual-axis chewing simulator and an ACTA wear machine. Methods: 3 CAD-CAM resin-based composite or polymer infiltrated ceramic network blocs, 1 lithium disilicate CAD-CAM ceramic (LS2), 3 direct resin composites, amalgam and bovine enamel were tested. For 2BW, 8 flat specimens per material were produced, grinded, polished, stored wet (37 °C, 28d) and tested (49 N, 37 °C, 1,200,000 cycles) against zirconia. For 3BW, specimens (n = 10) were stored accordingly, and tested against a zirconia antagonist wheel (3Y-TZP, d = 20 mm, h = 6 mm; 200,000 cycles, F = 15 N, f = 1 Hz, 15% slip) in millet seed suspension. Wear resistance was analysed in a 3D optical non-contact profilometer, measuring vertical wear depth and volume loss for 2BW and mean wear depth and roughness (Ra) for 3BW. Vickers hardness (15 s, HV2) was measured. Statistical analysis was performed using non-parametric tests (Mann-Whitney-U test, p < 0.05). Results: 2BW and 3BW have a different impact on material surfaces. Similar wear resistance was observed for direct and indirect resin based materials with analogous filler configurations in both methods. Bovine enamel exhibited the best wear resistance in 2BW, but the least wear resistance in 3BW against zirconia. Regarding 2BW, a direct/indirect composite material pair of the same manufacturer showed the significantly highest mean volume losses (2.72/2.85 mm³), followed by LS2 (1.41 mm³). LS2 presented the best wear resistance in 3BW (mean wear depth 2.85 µm), combined with the highest mean Vickers hardness (598 MPa). No linear correlation was found between Vickers hardness and both wear testing procedures. The zirconia antagonists showed no recordable signs of wear. Significance: Dental restorative materials behave differently in 2BW and 3BW laboratory testing. Vickers hardness testing alone cannot hold for a correlation with wear behavior of materials. Micromorphological investigation of material composition can reveal insights in wear mechanisms related to variations in filler technologies.
CRIS-Team Scopus Importer:2022-05-06
Keywords: Abrasion; ACTA wear machine; CAD-CAM; Chewing simulator; Dental materials; Resin-based composite; Three-body wear; Two-body wear; Vickers hardness; Zirconia

Factors influencing development of residual stresses during crystallization firing in a novel lithium silicate glass-ceramic - Wendler, Michael; Belli, Renan; Lohbauer, Ulrich (Dental Materials, 2019)
Objective: Development of residual stresses is a potential source of premature fractures in glassy materials, being of special interest in novel lithium silicate glass-ceramics that require a crystallization firing to achieve their final mechanical properties. The aim of this work was to assess the influence of various firing tray systems and the application of different cooling protocols on the development of residual stresses in Suprinity PC crowns. Their effect on the in vitro lifetime of the restorations was also studied. Methods: Thirty crowns were milled out of Suprinity PC blocks and crystallized using one of five different commercial firing tray systems (n = 6). Samples in each group were cooled following a fast (FC = 5.5 °C/s), a slow (SC = 0.4 °C/s)or the manufacturer's reference cooling (REF). Obtained crowns were sagittally or transversally sectioned and the magnitude and distribution of residual stresses was determined using the light birefringence method. Extra crowns of three of the subgroups (n = 8)were produced and submitted to chewing simulation for 10 6 cycles or until fracture ensued. Results: Average residual stresses ranged between 0 and 1.5 MPa (peaks of 5 MPa). Highest stress magnitudes were observed at the support areas of groups using firing pins, leading to thermal cracks in FC samples and premature failures in the REF subgroup. The use of fibrous pads and firing pastes limited the development of residual stresses, whereas application of SC regimes extended the lifetime of the restorations. Significance: Development of residual stresses during crystallization firing in lithium silicate glass-ceramics results critical for their mechanical performance and should be therefore avoided by ensuring a homogenous cooling of the structures.
CRIS-Team Scopus Importer:2019-05-16
Keywords: Cooling protocol; Crystallization; Firing tray; Glass-ceramic; Lifetime; Lithium silicate; Residual stress

Factors involved in mechanical fatigue degradation of dental resin composites - Lohbauer, Ulrich; Belli, Renan; Ferracane, J. L. (Journal of Dental Research, 2013)
The design of clinical trials allows for limited insights into the fatigue processes occurring in resin composites and the factors involved therein. In vitro studies, in contrast, can fundamentally narrow study interests to focus on particular degradation mechanisms and, to date, represent the major contributors to the state of knowledge on the subject. These studies show that microstructural features are important in determining strength and fracture toughness, whereas fatigue resistance is mainly related to the susceptibility of the matrix and the filler/matrix interface to mechanical and chemical degradation. In this review, we focus on fracture mechanisms occurring during fatigue, on the methods used to assess them, and on additional phenomena involved in the degradation of initial mechanical properties of resin composites. © International & American Associations for Dental Research.
CRIS-Team Scopus Importer:2023-01-23
Keywords: composite resins; crack propagation; cyclic loading; fracture toughness; hydrolysis; viscoelasticity

Fatigue behavior of dental resin composites: Flexural fatigue in vitro versus 6 years in vivo - Garcia-Godoy, Franklin; Frankenberger, Roland; Lohbauer, Ulrich; Feilzer, Albert J.; Kraemer, Norbert (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2012)
Objectives: To evaluate fatigue behavior of direct resin composite restorations (Tetric Ceram vs. Grandio) in vitro and in vivo over an observation period of 6 years. Methods: For the in vitro part, Young's moduli (YM) were calculated and both initial (FS: flexural strength) and fatigue flexural strength (FFL: flexural fatigue limit) were evaluated in a four-point bending setup (n = 15) in distilled water at 37°C. For the in vivo part, 30 patients received 68 direct resin composite restorations of the same materials (Grandio bonded with Solobond M; Tetric Ceram bonded with Syntac). Patients revealed a minimum of two different class II restorations in different quadrants. Epoxy replicas of restored teeth were analyzed under a scanning electron microscope (SEM) at 30Ã - magnification for fatigue characteristics, and 11 selected restorations per group were assessed for marginal fatigue characteristics at 200Ã - . Results: In vitro, YM was 15.7 GPa (Grandio) and 8.7 GPa (Tetric Ceram; p < 0.05), FS was 115.0 MPa (Grandio) versus 101.5 MPa (Tetric Ceram; p > 0.05), and FFL was 63.0 MPa (Grandio) versus 44.3 MPa (Tetric Ceram; p < 0.05). In vivo, no significant difference in fatigue behavior (cracks, chippings) was evaluated for the different materials under investigation. However, marginal breakdown was more pronounced under the SEM for Tetric Ceram (7.9% vs. 4.8% for Grandio; p < 0.05), but without being clinically relevant. SEM analysis exhibited distinct wear patterns after 6 years with no significant differences among materials as well. Significances: Despite higher in vitro values for YM, FS, and FFL for Grandio, clinical outcome for both resin composite materials over 6 years of clinical service was similar. Higher FFLs in vitro seem to be related to less marginal composite fractures in vivo but without any influence on clinical outcome until the 6 years recall. © 2012 WILEY PERIODICALS, INC.
CRIS-Team Scopus Importer:2023-01-23
Keywords: clinical study; flexural fatigue; fracture; marginal fractureIntroduction; resin composites

Fatigue behavior of Y-TZP ceramic after surface treatments - Amaral, Marina; Cesar, Paulo Francisco; Bottino, Marco Antonio; Lohbauer, Ulrich; Valandro, Luiz Felipe (Journal of the Mechanical Behavior of Biomedical Materials, 2016)
The aim of this study was to evaluate the effect of three surface treatments on the biaxial flexural strength before and after mechanical cycling, and fatigue limit of a Y-TZP ceramic.Disc-shaped specimens were produced and three surface conditions were tested: CT (as-sintered, untreated), GL (thin layer of porcelain glaze), and AA (air abrasion with 30µm silica particles). Profilometric and phase transformation analyses were performed. Disks were submitted to biaxial flexural strength (BFS) before and after mechanical cycling (100N, 2×10(6) cycles) and staircase approach (n=20). The flexural fatigue limits (FFLs) were obtained at 10(2), 10(3), 10(4) and 10(5) cycles.Tetragonal to monoclinic transformation was only observed for AA group (9.46% of monoclinic phase). Glazed group presented the highest Ra values. Flexural strength was higher for AA group; CT and GL groups were similar. The reliability was similar between groups. The mechanical cycling at 100N did not affected flexural strength. FFLs were higher for AA group, and the three surface treatments presented decrease in strength according to the increase in number o cycles.
EVALuna2:24682

Fatigue strength of bilayer yttria-stabilized zirconia after low-temperature degradation - Pereira, Raíssa Monteiro; Belli, Renan; Lohbauer, Ulrich; Hurle, Katrin; Campos, Tiago Moreira Bastos; Thim, Gilmar Patrocínio (Journal of the Mechanical Behavior of Biomedical Materials, 2024)
This study examined the impact of interfacial interactions on bilayer yttria-stabilized zirconia (YSZ) used in dental restorations. In-house bilayer structures of 3YSZ and 5YSZ composition underwent hydrothermal degradation to compare the properties of control and low-temperature degradation (LTD) treated groups. Biaxial flexural strength via piston-on-three-balls, staircase fatigue strength over 106 cycles at 15 Hz, phase characterization and quantification through XRD and Rietveld refinement, and fractography were conducted. Weibull analysis was employed to determine the Weibull modulus and characteristic strength. Results demonstrated an enhancement in the mechanical performance of 3YSZ composition after LTD treatment, whereas the mechanical properties of 5YSZ remained largely unaffected post-degradation. Fractographic analysis revealed that failure originated at the surface tensile location across all specimen groups. These findings offer insights into the mechanical behavior of bilayer zirconia structures and reinforce the significance of hydrothermal treatment in enhancing their performance, particularly in the case of 3Y compositions.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Biaxial flexural strength; Bilayer; Fatigue; Low-temperature degradation; Mechanical properties; Zirconia

Fatigue Threshold R-Curves for Dental Lithium Disilicate Glass–Ceramics - Lubauer, Julia; Lohbauer, Ulrich; Belli, Renan (Journal of Dental Research, 2023)
Chemical and mechanical fatigue degradation in ceramic materials is generally inconspicuous yet ubiquitous, to the effect that clinical fractures still consist of the main cause of failure in all-ceramic restorations. Implications of this span wide, from a reduced survival prognosis for the affected teeth, including more frequent and increasingly invasive procedural interventions, to the financial burden borne by individuals and health care systems. To suffice as an effective corrective, restoration lifetimes need only to be extended so to outlive the patient. That opens a box of problems from a materials science standpoint, entailing inherent deficiencies of brittle materials to resist mechanical and environmental challenges. Efforts in developing more damage-tolerant and fatigue-resistant restoratives go thus hand in hand with understanding intrinsic mechanisms of crack growth behavior under conditions that simulate the oral environment. Here we developed experiments using size-relevant sharp precracked specimens with controlled size and geometry (truncated semielliptical crack in the surface-crack-in-biaxial-flexure method) to establish a relationship between crack size and strength. The tangent method was used to construct envelopes for the quasi-static resistance curves (R-curves), which served as template for deriving residual cyclic R-curve analogs. By means of experimentally obtained stress–cycle curves, lifetime and fatigue parameters were employed within a mechanistic framework to reveal constitutive toughening mechanisms during subcritical growth under cyclic loading in a wet environment. Using 3 modern dental lithium disilicate glass–ceramics, we demonstrate the extent of R-curve degradation up to a threshold of 10 million cycles ( 30 y in service) and draw parallels between the scope of fatigue degradation and the size of the microstructural units responsible for toughening mechanisms in glass–ceramic materials. Our results indicate that larger microstructural elements endow glass–ceramics with a higher reaching quasi-static R-curve at the onset but degrading more rapidly to comparable levels of lithium disilicates having submicrometric and nanometric crystal phases.
CRIS-Team Scopus Importer:2023-07-28
Keywords: CAD–CAM; ceramics; flexural strength; lithia disilicate; mechanical tests; stress fracture

Filling of small oval root canals: influence of sealer placement and filling technique - Schunemann, Fernanda Haverroth; Canani, Soraia Hopfner; Lohbauer, Ulrich; Petschelt, Anselm; Metzger, Zvi; Ebert, Johannes (Quintessence International, 2021)
Objectives: The aim of this study was to carry out a morphometric analysis of small oval root canals filled with GuttaFlow 2 sealer (Coltene/Whaledent) using different methods of sealer placement and different root canal filling techniques. Method and materials: Eighty extracted mandibular incisors with small oval root canals were instrumented with the Self-Adjusting File (Redent Nova). GuttaFlow 2 was placed using a lentulo spiral, paper point, master point, or sonically activated CanalBrush (Coltene/Whaledent), followed by the placement of a master point and accessory points (MP+) (part 1). GuttaFlow 2 was placed using a lentulo spiral without a gutta-percha point, together with a single point, with a chloroform-dipped master point, or the latter with accessory points (ChMP+) (part 2). Serial cuts were made at 1-mm intervals up to 10 mm. The percentages of gutta-percha filled area (PGFA), sealer, voids, and debris were evaluated using interactive image analysis software. Results: For part 1 of the study (sealer placement), significant differences regarding PGFA at 2 and 5 mm from the apex were found, whereas for part 2 (filling technique), significant differences were found at all levels besides 2 and 4 mm (Kruskal-Wallis test, P <=.05). ChMP+ reached 85% PGFA at 3 mm from the apex, but only 30% near the apex. The MP+ groups showed a relatively equal distribution of PGFA by 60% to 80% at different levels. GuttaFlow 2 without a gutta-percha point exhibited significantly more voids and debris than the other groups (Kruskal-Wallis test, P <= .05). Conclusion: Within the limits of this study, MP+ could be recommended for clinical use. The presence of voids and debris for the group without a gutta-percha point needs further investigation.
CRIS-Team WoS Importer:2021-03-19

Fluorescent Labeling and 2-Photon Imaging of Mouse Tooth Pulp Nociceptors - Kadala, A.; Sotelo-Hitschfeld, Pamela; Ahmad, Ziad; Tripal, Philipp; Schmid, Benjamin; Mueller, A.; Bernal, L.; Winter, Zoltan; Brauchi, S.; Lohbauer, Ulrich; Meßlinger, Karl; Lennerz, J. K.; et al. (Journal of Dental Research, 2017)
Retrograde fluorescent labeling of dental primary afferent neurons (DPANs) has been described in rats through crystalline fluorescent DiI, while in the mouse, this technique was achieved with only Fluoro-Gold, a neurotoxic fluorescent dye with membrane penetration characteristics superior to the carbocyanine dyes. We reevaluated this technique in the rat with the aim to transfer it to the mouse because comprehensive physiologic studies require access to the mouse as a model organism. Using conventional immunohistochemistry, we assessed in rats and mice the speed of axonal dye transport from the application site to the trigeminal ganglion, the numbers of stained DPANs, and the fluorescence intensity via 1) conventional crystalline DiI and 2) a novel DiI formulation with improved penetration properties and staining efficiency. A 3-dimensional reconstruction of an entire trigeminal ganglion with 2-photon laser scanning fluorescence microscopy permitted visualization of DPANs in all 3 divisions of the trigeminal nerve. We quantified DPANs in mice expressing the farnesylated enhanced green fluorescent protein (EGFPf) from the transient receptor potential cation channel subfamily M member 8 (TRPM8EGFPf/+) locus in the 3 branches. We also evaluated the viability of the labeled DPANs in dissociated trigeminal ganglion cultures using calcium microfluorometry, and we assessed the sensitivity to capsaicin, an agonist of the TRPV1 receptor. Reproducible DiI labeling of DPANs in the mouse is an important tool 1) to investigate the molecular and functional specialization of DPANs within the trigeminal nociceptive system and 2) to recognize exclusive molecular characteristics that differentiate nociception in the trigeminal system from that in the somatic system. A versatile tool to enhance our understanding of the molecular composition and characteristics of DPANs will be essential for the development of mechanism-based therapeutic approaches for dentine hypersensitivity and inflammatory tooth pain.
EVALuna2:24704

Fractographic analysis of a dental zirconia framework: A case study on design issues - Lohbauer, Ulrich; Amberger, Gudrun; Quinn, George D.; Scherrer, Susanne S. (Journal of the Mechanical Behavior of Biomedical Materials, 2010)
Fractographic analysis of clinically failed dental ceramics can provide insights as to the failure origin and related mechanisms. One anterior 6-unit all-ceramic zirconia fixed partial denture (FPD) (Cercon®) has been clinically recovered and examined using qualitative fractography. The purpose was to identify the fracture origin and to state the reasons for failure. The recovered parts of the zirconia FPD were microscopically examined to identify classic fractographic patterns such as arrest lines, hackle, twist hackle and wake hackle. The direction of crack propagation was mapped and interpreted back to the origin of failure at the interface of the occlusal-palatal tip of the core and the veneering ceramic. An inappropriate core drop design favoring localized stress concentration combined with a pore cluster in the veneering ceramic at the core tip interface were the reasons for this premature through-the-core thickness failure. © 2010 Elsevier Ltd.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Ceramic restoration; Dental ceramic; Failure analysis; Fixed partial denture; Fractography; Zirconia

Fractographic analysis of broken ceramic dental restorations - Quinn, George D.; Hoffman, Kathleen; Scherrer, S.; Lohbauer, Ulrich; Amberger, G.; Karl, Matthias; Kelly, J. R. (Ceramic Transactions, 2012)
Three in vivo fractured multiunit all-ceramic restorations were analyzed as part of an ongoing project to characterize fracture mechanisms in dental restorations. The overall breakage patterns were evaluated and stereoptical and scanning electron microscopy used to find the origins of fracture. The causes of fracture in the alumina and zirconia restorations were different in each case.
CRIS-Team Scopus Importer:2023-01-23

Fractographic analysis of lithium silicate crown failures during sintering - Lohbauer, Ulrich; Wendler, Michael; Rapp, Doreen; Belli, Renan (SAGE Open Medical Case Reports, 2019)
The two-step production process of glass-ceramic dental restorations involves a computer-aided design/computer-aided machining step followed by a crystallization firing for the final material properties to be achieved. Certain firing parameters are believed to trigger spontaneous fracture of crowns during the cooling process. In this study, cooling fractures have been reproducibly observed and investigated using fractography combined with material (glass transition temperature) and process (cooling rate) characterization. Stress distribution was visualized using birefringence measurements. Fractographic observations revealed fracture starting at the intaglio side of the crowns specifically at contact points with the support firing pins. Further analysis showed that a fast cooling rate was applied during the glass transition region. Thermal stresses were concentrated around the firing pin supports and released the fracture. To prevent such fractures, a slow cooling protocol below the glass transition temperature is our recommendation to dental technicians. Furthermore, the use of planar firing pad or paste supports is advised over the use of point contact supports.
CRIS-Team WoS Importer:2019-04-04

Fractography of clinical failures of indirect resin composite endocrown and overlay restorations - Saratti, Carlo M.; Rocca, Giovanni T.; Durual, Stéphane; Lohbauer, Ulrich; Ferracane, Jack L.; Scherrer, Susanne S. (Dental Materials, 2021)
Objectives: Compare failure modes and fracture origins using fractography on recovered clinically fractured parts of indirect resin composite endocrowns and overlay restorations on endodontically treated teeth (ETT). Methods: Four endocrowns (3 molars, 1 premolar) and one overlay (molar) adhesively luted on ETT were recovered after fracturing during function. The time in service ranged between 4 and 48 months. The composite materials were (i) CAD/CAM LAVA Ultimate (N = 1), (ii) Premise Indirect (N = 2), and (iii) Colombus (N = 2). Fractography was performed by means of digital microscopy and SEM. Occlusal surfaces were checked for signs of fatigue degradation and contact wear. Cuspal plane angles were measured from profiles obtained from 3D digital microscope images with respect to the horizontal plane of the occlusal central crown groove. Results: All five cases showed a wedge-opening mode I fracture, splitting the crown and tooth in two parts through the crown's central groove. Classic brittle fracture features (arrest lines, twist and wake hackle) were easily identified on the fracture surfaces. Multiple origins were located along the central groove in conjunction with the presence of fatigue cracks. Contact wear surfaces showed pitting and cracking. Cuspal plane angles were around 30–35°, except a 50° palatal cusp slope for the Lava Ultimate overlay. Significance: Fractography on clinical fractures of resin composites was enlightening. Occlusal surface fatigue degradation from cyclic loading, mode I fracture from applied mastication forces on cuspal planes, and stress concentration within the crown's central groove, indicate limitations of use of these materials for endocrowns in posterior teeth.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Clinical; Composite; Crown; Fatigue; Fractography; Fracture; Mode I; Restoration; Wear

Fractography of clinically fractured, implant-supported dental computer-aided design and computer-aided manufacturing crowns - Lohbauer, Ulrich; Belli, Renan; Cune, Marco S.; Schepke, Ulf (SAGE Open Medical Case Reports, 2017)
Today, a substantial part of the dental crown production uses computer-aided design and computer-aided manufacturing (CAD/CAM) technology. A recent step in restorative dentistry is the replacement of natural tooth structure with pre-polymerized and machined resin-based methacrylic polymers. Recently, a new CAD/CAM composite was launched for the crown indication in the load-bearing area, but the clinical reality forced the manufacturer to withdraw this specific indication. In parallel, a randomized clinical trial of CAD/CAM composite crowns luted on zirconia implant abutments revealed a high incidence of failure within the first year of service. Fractured crowns of this clinical trial were retrieved and submitted to a fractographic examination. The aim of the case series presented in this article was to identify failure reasons for a new type of CAD/CAM composite crown material (Lava Ultimate; 3M Oral Care, St. Paul, Minnesota, USA) via fractographic examinations and analytical assessment of luting surfaces and water absorption behavior. As a result, the debonding of the composite crowns from the zirconia implant abutments was identified as the central reason for failure. The adhesive interface was found the weakest link. A lack of silica at the zirconia surface certainly has compromised the bonding potential of the adhesive system from the beginning. Additionally, the hydrolytic stress released from swelling of the resin-based crown (water absorption) and transfer to the luting interface further added to the interfacial stress and most probably contributed to a great extend to the debonding failure.
EVALuna2:24703

Fracture anisotropy in texturized lithium disilicate glass-ceramics - Belli, Renan; Wendler, Michael; Cicconi, Maria Rita; de Ligny, Dominique; Petschelt, Anselm; Werbach, Katharina; Peterlik, Herwig; Lohbauer, Ulrich (Journal of Non-Crystalline Solids, 2018)
Lithium disilicate glass-ceramics show great potential in the fabrication of anisotropic structures due to their high-strength needle-form crystalline phase subjective to processing-induced alignment. Here we explore this strategy by focusing on the mechanistic aspects of fracture. Through different variations of the fracture toughness test we demonstrate the effect of bulk crystal orientation on fracture energy, toughening mechanisms, crystal size and aspect ratio. Using the anisotropic Poisson's ratio of the Li2Si2O5 crystal phase obtained by Resonant Ultrasound Spectroscopy, we apply the new geometry factor developed by Strobl et al. to provide a more accurate insight into the anisotropic crack propagation behavior in LS2 glass-ceramics. Raman spectra and X-Ray Diffraction patterns are resolved for the Li2Si2O5 phase aligned at plane parallel, anti-plane and random orientations.We show that Li2Si2O5 crystallites oriented perpendicular to the crack growth plane tended to induce large scale crack deflection unless the crack was forced into a straight path, thereby promoting crystallite fracture, increased K-Ic-values and accentuated R-curve behavior. Crystal aspect ratio and residual stresses in the glass have been identified as important influencing factors on crack growth behavior and toughening mechanisms.
Keywords: Lithium disilicate; Fracture toughness; Anisotropy; Crystal alignment

Fracture of a veneered-ZrO2 dental prosthesis from an inner thermal crack - Lohbauer, Ulrich; Belli, Renan; Arnetzl, Gerwin; Scherrer, Susanne S.; Quinn, George D. (Case Studies in Engineering Failure Analysis, 2014)
Here we describe the fractographic analysis of a veneer-ZrO2 single-unit dental prosthesis that fractured in a shell-like manner. Analysis of the retrieved fragment revealed that the crack originated in the bulk of the veneer from a thermal flaw located between two layers of the veneering material. Using the measured flaw plane we showed that the conditions of loading at fracture were complex and probably involved important tangential components.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Dental ceramics; Dental fractography; Dental prosthesis; Fracture; Thermal crack; Zirconia

Fracture Rates and Lifetime Estimations of CAD/CAM All-ceramic Restorations - Belli, Renan; Petschelt, Anselm; Hofner, Benjamin; Hajto, J.; Scherrer, S. S.; Lohbauer, Ulrich (Journal of Dental Research, 2016)
The gathering of clinical data on fractures of dental restorations through prospective clinical trials is a labor- and time-consuming enterprise. Here, we propose an unconventional approach for collecting large datasets, from which clinical information on indirect restorations can be retrospectively analyzed. The authors accessed the database of an industry-scale machining center in Germany and obtained information on 34,911 computer-aided design (CAD)/computer-aided manufacturing (CAM) all-ceramic posterior restorations. The fractures of bridges, crowns, onlays, and inlays fabricated from different all-ceramic systems over a period of 3.5 y were reported by dentists and entered in the database. Survival analyses and estimations of future life revealed differences in performance among ZrO2-based restorations and lithium disilicate and leucite-reinforced glass-ceramics.
EVALuna2:5537

Fracture toughness and cyclic fatigue resistance of resin composites with different filler size distributions - Ornaghi, Barbara P.; Meier, Marcia M.; Lohbauer, Ulrich; Braga, Roberto R. (Dental Materials, 2014)
To verify the influence of filler size distributions on fracture toughness (KIc), initial fracture strength (IFS) and cyclic fatigue resistance (CFR) of experimental resin composites.Four composites were prepared with same inorganic content (78 wt%), in which 67 wt% was constituted by glass particles with d50 of 0.5; 0.9; 1.2; 1.9 ?m KIc of the composites was determined by the single-edge notched beam (SENB) method. To evaluate the IFS and the CFR a biaxial bending test configuration was used. The CFR was determined under cyclic loading for 10(5) cycles using the 'staircase' approach. The fracture surfaces of IFS and CFR specimens were analyzed under scanning electron microscope (SEM).There was a positive linear correlation between d50 vs. KIc and statistical difference was found only between C0.5 (1.24±0.10 MPa m0.5) and C1.9 (1.41±0.17 MPa m0.5). There were no statistical differences among IFS means, which ranged from 155.4±18.8 MPa (C0.9) to 170.7±23.1 MPa (C1.2). C0.5 (93.0±18.6a MPa) showed the highest and C0.9 the lowest CFR (82.5±8.0c MPa). There was no correlation between CFR with d50 values or with KIc means. SEM images showed the morphology with brittle fracture patterns for the surfaces of IFS specimens and a more smooth fracture surface for CFR specimens.Resin composites showed different failure mechanisms for quasi-static and fatigue loading. For KIc and IFS, composites with larger filler size distributions showed better results due to crack deflection; while under cyclic loading, viscous behavior was predominant and composites with smaller particles showed higher fatigue resistance.
EVALuna2:24660

Fracture toughness mode mixity at the connectors of monolithic 3Y-TZP and LS2 dental bridge constructs - Belli, Renan; Wendler, Michael; Zorzin, José Ignacio; da Silva, Lucas Hian; Petschelt, Anselm; Lohbauer, Ulrich (Journal of the European Ceramic Society, 2015)
Most dental ceramics are produced from partially crystallized glass. Even though these materials are hard, they are extremely susceptible to damage, especially due to the glass phase content. A strategy for strengthening these materials makes use of their microstructure to form reinforcing sites within the structural design. Such approach has potential for application with lithium disilicate (LS2) glass-ceramics, which contain needle-form Li2Si2O5 crystals that deflect oncoming cracks. By press injection of the glass melt through specifically oriented injection channels, crystals are aligned in patterns that lead to high mechanical anisotropy. Here we apply this approach in the context of monolithic dental bridges simulated by beams under 3-point bending. Notches at different distances from the midspan play the role of connectors, and the mixed-mode fracture toughness is measured at varying positions for a LS2 and a 3Y-TZP material. A strong anisotropic fracture behavior is obtained with the LS2 glass-ceramic through local crystal alignment, leading to fracture energies higher than for the isotropic 3Y-TZP ceramic. Further, the anisotropic nature of the LS2 microstructure is successfully reproduced in dental bridge geometries, validating the use of bending beams for the study of the mechanical behavior of ceramic dental bridges.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Dental bridges; Fracture toughness; Lithium disilicate; Mixed-mode loading; Zirconia

Fracture toughness of 3Y-TZP ceramic measured by the Chevron-Notch Beam method: A round-robin study - Begand, Sabine; Spintzyk, Sebastian; Geis-Gerstorfer, Jürgen; Bourauel, Christoph; Keilig, Ludger; Lohbauer, Ulrich; Worpenberg, Christin; Greuling, Andreas; Adjiski, Ranko; Jandt, Klaus D.; Lümkemann, Nina; Stawarczyk, Bogna; et al. (Dental Materials, 2022)
Objective: This interlaboratory round robin test investigated the robustness of the Chevron-Notch Beam (CNB) test method and the effect of the processing and testing variations on the fracture toughness of a dental 3Y-TZP ceramic. Methods: The round robin test was performed precisely following the procedures recommended in ISO 24370:2005 and applied on a commercial 3Y-TZP ceramic (product information). A total of 335 test specimens with dimensions 3×4 x 45 mm³ was equally distributed among 10 participating laboratories of varying experience in fracture toughness testing. A standard operating procedure was defined with either narrow processing tolerances or alternative (wider) processing tolerances (as proposed in ISO 24370). Fracture toughness data (series 2) was analyzed using one way ANOVA followed by post hoc Tukey HSD test and 95% Confidence Intervals (CI) were computed (p < 0.05). A further, preceding round-robin (series 1) test was conducted with - more possible variations of test conditions regarding CNB notch processing and storage conditions. Those results are summarized in the supplement and discussed with the actual ISO 24370 test. Results: Fracture toughness of the 3Y-TZP ceramic material, summarized over all laboratories was measured to KIc = 4.48 ± 0.11 MPam0.5 for the standard processing tolerance and KIc = 4.55 ± 0.31 MPam0.5 for the alternative tolerance. The results revealed a significant influence of cutting offset and notch geometry on KIc when using CNB method. The test medium also has a significant influence on KIc in terms of reduced fracture toughness under the influence of water. With defined testing conditions the number of valid tests and reduced standard deviation increased. In case of strictly following such standard operation procedures, KIc can be determined with high reliability. There is no difference between the involved laboratories, but significant influence of cutting offset on KIC was observed. Significance: The CNB method is suitable method for determination of KIc on fine-grained ceramics such as 3Y-TZP ceramic. By using tighter tolerances for processing and testing, i.e. closely following the ISO 24370 procedure, a highly-precise evaluation of fracture toughness with low data variation is achievable. The information of the storage medium should always be reported along with the data. CNB fracture toughness testing is an alternative method compared to Single-edge V-notch beam (SEVNB), especially for fine-grained ceramics.
CRIS-Team Scopus Importer:2022-07-01
Keywords: 3Y-TZP; Fracture toughness; Interlaboratory test; ISO 6872; Zirconia

Fracture toughness of dental incremental composite-composite interfaces at elevated temperatures - Maier, Eva; Loumprinis, Nikolaos; Belli, Renan; Petschelt, Anselm; Eliades, George; Lohbauer, Ulrich (Journal of the Mechanical Behavior of Biomedical Materials, 2021)
The aim of the present laboratory study was to mechanically characterize the interface between two dental resin-based composite (RBC) increments, and to investigate if elevated temperatures have an influence on the quality of the interface mimicking clinical filling procedure. Four RBCs (CLEARFIL MAJESTY™ Posterior, Kuraray (CMP)/Filtek™ Supreme XTE, 3M (FSX)/Grandio®SO, VOCO (GSO)/VisCalor® bulk, VOCO (VCB)) were tested with a fracture toughness test using Chevron notched beams (KI,CNB) at 23, 37 and 54 °C. KI,CNB specimens (3 × 4x25mm) with a V-shaped notch at the incremental interface were loaded until failure in a 4-point bending set-up. Failure modes were characterized using light microscopy, microstructural interface was analyzed using SEM. Statistical analysis was performed using Kolmogorov-Smirnoff test, two-way ANOVA and Tukey Post-Hoc test (p = 0.05). Mean KI,CNB ranged between 0.73 ±0.14 MPam0.5 (VCB, 23 °C) and 1.11 ± 0.11 MPam0.5 (FSX, 23 °C). The tested conventional highly filled RBCs presented fracture toughness at the incremental interface comparable to the cohesive strength of the bulk materials. VCB showed reduced interfacial fracture toughness at 23 and 37 °C, but performed well at elevated temperature of 54 °C.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Chevron notch beam; Fracture toughness; Increment; Interface; Resin-based composite; Temperature

Fracture toughness of GIC—A mechanistic approach on the nanoscale - Brandt, B; Durst, Karsten; Belli, Renan; Göken, Mathias; Lohbauer, Ulrich (Dental Materials, 2010)
Objectives: To investigate the fracture toughness KIc of a dental glassionomer (GI) cement in terms of terms of different storage intervals and to correlate the development of macroscopic data with findings on the nanoscale. Materials and methods: Bars with dimensions of 25 mm × 2 mm × 2 mm were produced out of a model GI cement (Schott/Evonik, Germany) and stored for 24 h, 7 d, and 21 d in water of 37 °C. Sharp notches were cut into the bars using a diamond wheel saw blade and a razor blade. Fracture toughness (n = 15) was measured using the SENB (single-edge-notched-bending) method. The actual notch depth for each specimen was measured after fracture under a light microscope. A Nano Indenter (G200, Agilent Tech., USA) was used to observe the elastic modulus and local hardness on the nanoscale. Therefore, flat specimens were produced, surface polished using the lapping technique, and stored as described above. Local mechanical properties were measured on glass particles and matrix of the set cement. Load-control (LCM) and Continuous Stiffness (CSM) measurements were performed. Results: An increasing fracture toughness was measured with extended storage times. The KIc increased from 0.22 MPa m0.5 after 24 h up to 0.24 MPa m0.5 (7 d) and finally to 0.27 MPa m0.5 after 21 d. The elastic modulus of the GI composite increased from 12.2 GPa (7 d) up to 16.1 GPa after 21 d. Hardness increased from 0.27 GPa (7 d) up to 0.43 GPa after 21 d. The glass particles showed an elastic modulus of 65.5 GPa and a hardness of 0.69 GPa. Conclusions: Mechanical properties on the nanoscale reflect the macroscopic data without any disturbing influence from material inhomogeneities, porosity, etc. Over time, the elastic modulus showed a higher increase compared to the macroscopic fracture toughness measurements. The material performance was found to be determined by the matrix behaviour. On the nanoscale, a viscoplastic response of the matrix component could be proved. Nanoindentation is a very useful technique for improving the macroscopic behaviour of a GI cement and suitable for localizing the weakest link in the composite structur

Fracture toughness testing of biomedical ceramic-based materials using beams, plates and discs - Belli, Renan; Wendler, Michael; Petschelt, Anselm; Lube, Tanja; Lohbauer, Ulrich (Journal of the European Ceramic Society, 2018)
The testing of fracture toughness becomes problematic when only limited amount of material is available that hinders the production of typical beam specimens to be tested in bending. Here we explore fracture toughness testing methodologies that allow for small discs and plates having surface cracks to be tested in biaxial flexure using the Ball-on-3-balls (B3B) set-up, or sawed notches as in the Compact Tension geometry. The B3B-K-Ic test has shown to be versatile and account for a very small overestimation of the K-Ic-value in the order of 0.8-1.25% due to in-plane crack mispositioning, and a maximum of 4% if a worst-case scenario of additional out-of-plane mispositioning is assumed. The geometrical factor in the standard SCF method, derived by Newman and Raju, resulted in an overestimation of similar to 8% of the K-Ic-value compared to the new calculation by Strobl et al. for materials with Poisson's ratio < 0.3.
EVALuna2:35488

Fracture Toughness Testing of Dental Restoratives: a Critical Evaluation - Belli, Renan; Zorzin, José Ignacio; Lohbauer, Ulrich (Current Oral Health Reports, 2018)
Purpose of Review: We intend by this short critical review to highlight important aspects regarding the mechanical testing of fracture toughness. The final aim is to increase the awareness to the test sensitivity, ultimately increasing the quality and reliability of reported testing results. Recent Findings: In a well-intended attempt to facilitate testing procedures or provide alternatives for testing material interfaces, authors are resorting to adaptation of testing methodologies without proper theoretical and experimental validation. The assumption of validity in such cases endangers the perpetration of testing strategies that are not safeguarded by sound theoretical bases. The use of improper statistical treatments based on extreme-value distributions further aggravates this scenario. Summary: We supply here some directions for authors concerning method selection, interpretation of data scatter, statistical treatment, and possibilities for test validation.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Dental restorative materials; Fracture toughness; Mechanical properties; Testing

Glass science behind lithium silicate glass-ceramics - Lohbauer, Ulrich; Fabris, Débora Cristina Niero; Lubauer, Julia; Abdelmaseh, Samuel; Cicconi, Maria Rita; Hurle, Katrin; de Ligny, Dominique; Götz-Neunhoeffer, Friedlinde; Belli, Renan (Dental Materials, 2024)
Objectives: Lithium silicate-based glass ceramics have evolved as a paramount restorative material in restorative and prosthetic dentistry, exhibiting outstanding esthetic and mechanical performance. Along with subtractive machining techniques, this material class has conquered the market and satisfied the patients’ needs for a long-lasting, excellent, and metal-free alternative for single tooth replacements and even smaller bridgework. Despite the popularity, not much is known about the material chemistry, microstructure and terminal behaviour. Methods: This article combines a set of own experimental data with extensive review of data from literature and other resources. Starting at manufacturer claims on unique selling propositions, properties, and microstructural features, the aim is to validate those claims, based on glass science. Deep knowledge is mandatory for understanding the microstructure evolution during the glass ceramic process. Results: Fundamental glass characteristics have been addressed, leading to formation of time-temperature-transformation (TTT) diagrams, which are the basis for kinetic description of the glass ceramic process. Nucleation and crystallization kinetics are outlined in this contribution as well as analytical methods to describe the crystalline fraction and composition qualitatively and quantitatively. In relation to microstructure, the mechanical performance of lithium silicate-based glass ceramics has been investigated with focus on fracture strength versus fracture toughness as relevant clinical predictors. Conclusion: Fracture toughness has been found to be a stronger link to initially outlined manufacturer claims, and to more precisely match ISO recommendations for clinical indications.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Clinical indication; Crystallization; Flexural strength; Fracture toughness; Glass ceramic; Lithium silicate; Nucleation; Residual stress

Grasping the Lithium hype: Insights into modern dental Lithium Silicate glass-ceramics - Lubauer, Julia; Belli, Renan; Peterlik, Herwig; Hurle, Katrin; Lohbauer, Ulrich (Dental Materials, 2022)
Objectives: Lithium-based glass-ceramics are currently dominating the landscape of dental restorative ceramic materials, with new products taking the market by storm in the last years. Though, the difference among all these new and old products is not readily accessible for the practitioner, who faces the dilemma of reaching a blind choice or trusting manufacturers' marketing brochures. To add confusion, new compositions tend to wear material terminologies inherited from vanguard dental lithium disilicates, disregarding accuracy. Here we aim to characterize such materials for their microstructure, crystalline fraction, glass chemistry and mechanical properties. Methods: Eleven commercial dental lithium-based glass ceramics were evaluated: IPS e.max (R) CAD, IPS e.max (R) Press, Celtra (R) Duo, Suprinity (R) PC, InitialTM LiSi Press, InitialTM LiSi Block, Amber (R) Mill, Amber (R) Press, N!CE (R), Obsidian (R) and CEREC TesseraTM. The chemical composition of their base glasses was measured by X-Ray Fluorescence Spectroscopy (XRF) and Inductive Coupled Plasma Optical Emission Spectroscopy (ICPOES), as well as the composition of their residual glass by subtracting the oxides bound in the crystallized fraction, characterized by X-Ray Diffraction (XRD) and Rietveld refinement, and quantified accurately using the G-factor method (QXRD). The crystallization behavior is revealed by differential scanning calorimetry (DSC) curves. Elastic constants are provided from Resonant Ultrasound Spectroscopy (RUS) and the fracture toughness measured by the Ball-on-Three-Balls method (B3B- K Ic). The microstructure is revealed by fieldemission scanning electron microscopy (FE-SEM). Results: The base glasses showed a wide range of SiO2 /Li2O ratios, from 1.5 to 3.0, with the degree of depolymerization dropping from 1/2 to 2/3 of the initial connectivity. Materials contained Li2SiO3+Li3PO4, Li2SiO3+Li3PO4+Li2Si2O5, Li2Si2O5+Li3PO4+ Cristobalite and/or Quartz and Li2Si2O5+Li3 PO4+LiAlSi2O6, in crystallinity degrees from 45 to 80 vol%. Crystalline phases could be traced to their crystallization peaks on the DSC curves. Pressable materials and IPS e.max (R) CAD were the only material showing micrometric phases, with N!CE (R) and InitialTM LiSi Block showing solely nanometric crystals, with the rest presenting a mixture of submicrometric and nanometric particles. Fracture toughness from 1.45 to 2.30 MPa root m were measured, with the linear correlation to crystalline fraction breaking down for submicrometric and nanometric crystal phases. Significance: Dental lithium-based silicate glass-ceramics cannot be all put in the same bag, as differences exist in chemical composition, microstructure, crystallinity and mechanical properties. Pressable materials still perform better mechanically than CAM/CAM blocks, which loose resistance to fracture when crystal phases enter the submicrometric and na-nometric range (c) 2021 The Academy of Dental Materials. Published by Elsevier Inc. All rights reserved.
CRIS-Team WoS Importer:2022-03-04

Hydroxylation of dental zirconia surfaces: Characterization and bonding potential - Lohbauer, Ulrich; Zipperle, Marita; Rischka, Klaus; Petschelt, Anselm; Müller, Frank (Journal of Esthetic and Restorative Dentistry, 2012)
CRIS-Team Scopus Importer:2023-01-23

Hygroscopic expansion of self-adhesive resin cements and the integrity of all-ceramic crowns - Kirsten, Magdalena; Matta, Ragai Edward; Belli, Renan; Lohbauer, Ulrich; Wichmann, Manfred; Petschelt, Anselm; Zorzin, José Ignacio (Dental Materials, 2018)
OBJECTIVE: Low pH neutralization and subsequent remnant hydrophilicity can lead to hygroscopic expansion of self-adhesive resin cements (SARCs) after water storage. The aim of this in vitro study was to investigate the effects of hygroscopic expansion of SARCs, used as luting and partial core build-up material, on integrity and cement gap thickness increase of all-ceramic CAD/CAM crowns. METHODS: Human third molars (n=48) were prepared and anatomical all-ceramic CAD/CAM crowns were manufactured (VITABLOCS Mark II, VITA Zahnfabrik). Crowns internal surfaces were HF etched and silanized. The prepared teeth with their respective crowns were divided into 6 groups (n=8). In groups 1, 3 and 5 the coronal dentin was removed to simulate a partial core build-up. Groups 1 and 2 were luted with iCEM (Heraeus Kulzer), 3 and 4 with RelyX Unicem 2 Automix (3M), 5 and 6 with Variolink Esthetic DC (Ivoclar Vivadent). All specimens were dual cured and stored in distilled water at 37°C. Crown integrity was controlled at baseline and in regular intervals until 180 days. Cement gap thickness was measured using an optical 3D scanner (ATOS Triple scan, GOM) at baseline and after 180 days. Crown integrity was statistically analysed using Kaplan-Meier survival analysis and cement gap thickness increase using two-way ANOVA (α=0.05). RESULTS: After 180 days storage, crack formation was observed in all specimens of group 1 (mean survival time of 85.5 days), in one specimen of group 2 and in two specimens of group 4. Two-way ANOVA analysis revealed a statistically significant interaction between material type and build-up on cement gap size increase for iCEM. SIGNIFICANCE: Within the limits of this study, the application of SARCs with low pH neutralization as partial build-up material under CAD/CAM crowns is not recommended for clinical use.
EVALuna2:34637

Influence of air-polishing devices and abrasives on root dentin-an in vitro confocal laser scanning microscope study - Pelka, Matthias; Trautmann, Siegfried; Petschelt, Anselm; Lohbauer, Ulrich (Quintessence International, 2010)
Objective: To assess the influence of air-polishing devices and various abrasives on flat root surfaces. Method and Materials: A total of 168 natural teeth were embedded in polyurethane resin and treated with airborne-particle abrasion using two air-polishing devices (Prophyflex 3, KaVo; EMS Handy, EMS), four abrasives (Airflow powder, EMS; Cleaning powder, KaVo; ClinPro powder, 3M ESPE; and ProphyPearls, KaVo), and three treatment times (5, 10, and 20 seconds). Defects were quantified using a confocal laser scanning microscope. Results: The Prophyflex device clearly generated deeper substance defects compared to the EMS device, regardless of abrasive used (Kruskal-Wallis, P = .004). ProphyPearls abrasive caused the deepest defects with both devices. ClinPro powder produced the least amount of defects. Defect depths increased significantly for all abrasives with increasing treatment times (Kruskal-Wallis, P = .01), and all abrasives except ClinPro powder caused substantial volume loss. Conclusion: The abrasiveness of air-polishing powders differs depending on the polishing device used. ProphyPearls caused more substance loss than ClinPro powder. © 2010 by Quintessence Publishing Co Inc.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Airborne-particle abrasion; Glycine powder; Nahco3; Prophypearls; Root defects; Root dentin

Influence of Simulated Oral Conditions on Different Pretreatment Methods for the Repair of Glass-Ceramic Restorations - Höller, Benedikt; Belli, Renan; Petschelt, Anselm; Lohbauer, Ulrich; Zorzin, José Ignacio (Journal of Adhesive Dentistry, 2022)
Purpose: The present study investigated the influence of simulated intraoral conditions (increased temperature and humidity) on two different surface pretreatment methods to repair a lithium-disilicate glass-ceramic (LDS).Materials and Methods: A total of 540 rectangular lithium-disilicate glass-ceramic bars were manufactured (3×7×9 mm; IPS e.max CAD, Ivoclar Vivadent). Further specimen preparation was performed in an incubator with controlled relative humidity (RH) and temperature to simulate three different environmental settings: laboratory conditions (LC, n = 180, 23°C, 50% RH), rubber-dam conditions (RC, n = 180, 30°C, 50% RH) or oral conditions (OC, n=180, 32°C, 95±5% RH). One-third of the bars under each condition (n=60) were grit blasted (GBL) with alumina (35 μm at 1 bar pressure for 10 s and a working distance of 4±1cm) and primed (60 s, Monobond Plus, Ivoclar Vivadent). Another third (n=60) were pretreated with a self-etching glass-ceramic primer (MEP, Monobond Etch & Prime, Ivoclar Vivadent). One group without surface pretreatment (n=60, NoPT) served as a control. All pre treated surfaces were coated with Heliobond (Ivoclar Vivadent). Two bars from the same pretreatment method were luted perpendicular to each other with a resin composite to form a square adhesion area of 9 mm2(TetricEvo Ceram, Ivoclar Vivadent), and light cured for 20 s on each side (1200 mW/cm2, Bluephase 20i, Ivoclar Vivadent). All specimens were stored for 24 h in distilled water at 37°C. Half of the specimens from each environmental set ting and pretreatment method (n=15) were thermocycled (TC, 5000 cycles, 5/55°C, 30-s dwell time), and tensile bond strength (TBS) testing was performed for all groups using an x-bar rope-assisted set-up. Data were statisti cally analyzed using two-way ANOVA (α=0.05) with Bonferroni adjustment.Results Regardless of the environmental and storage conditions (24 h or TC), MEP showed a significantly higher mean TBS than GBL. A decrease in TBS was recorded in specimens under OC compared to RC and LC for both pre treatment methods independent of the storage condition. No significant difference in mean TBS was found be tween RC and LC within the MEP pretreatment group for the 24 h stored and thermocycled specimens. For all MEPs and GBLs, TC reduced the mean TBS in all environmental conditions. The NoPT groups showed no adhesion regardless of environmental or storage conditions.Conclusions: Increased temperature and high humidity significantly reduced TBS. However, MEP was less sensitive to environmental influences than GBL, which makes it a promising candidate for intraoral ceramic repair. These findings suggest that clinical intraoral repair of lithium-disilicate glass-ceramics should be performed using a rub ber-dam, primarily when using GBL.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Grit blasting; Lithium-disilicate ceramic; Self-etching glass-ceramic primer; Silanization; Tensile bond strength; Thermocycling

Inner marginal strength of CAD/CAM materials is not affected by machining protocol - Lubauer, Julia; Belli, Renan; Schünemann, Fernanda H.; Matta, Ragai; Wichmann, Manfred; Wartzack, Sandro; Völkl, Harald; Petschelt, Anselm; Lohbauer, Ulrich (Biomaterial Investigations in Dentistry, 2021)
Purpose Here we aimed to compare two machining strategies regarding the marginal strength of CAD/CAM materials using a hoop-strength test in model sphero-cylindrical dental crowns, coupled with finite element analysis. Materials and Methods Five CAD/CAM materials indicated for single posterior crowns were selected, including a lithium disilicate (IPS e.max® CAD), a lithium (di)silicate (Suprinity® PC), a polymer-infiltrated ceramic scaffold (Enamic®), and two indirect resin composites (Grandio® Blocs and Lava™ Ultimate). A sphero-cylindrical model crown was built on CAD Software onto a geometrical abutment and machined using a Cerec MC XL system according to the two available protocols: rough-fast and fine-slow. Specimens were fractured using a novel hoop-strength test and analyzed using the finite element method to obtain the inner marginal strength. Data were evaluated using Weibull statistics. Results Machining strategy did not affect the marginal strength of any restorative material tested here. Ceramic materials showed a higher density of chippings in the outer margin, but this did not reduce inner marginal strength. IPS e.max® CAD showed the statistically highest marginal strength, and Enamic® and Lava™ Ultimate were the lowest. Grandio® Blocs showed higher performance than Suprinity® PC. Conclusions The rough-fast machining strategy available in Cerec MC XL does not degrade the marginal strength of the evaluated CAD/CAD materials when compared to its fine-fast machining strategy. Depending on the material, resin composites have the potential to perform better than some glass-ceramic materials.
Keywords: CAD/CAM; strength; finite element

Instantiations of Multiscale Kinship in Pressing‐Defect Distributions in Yttria‐Stabilized Zirconias by Powder Partitioning - Pereira, Raíssa Monteiro; Lohbauer, Ulrich; Schulbert, Christian; Göken, Mathias; Wurmshuber, Michael; Campos, Tiago Bastos Moreira; Thim, Gilmar Patrocínio; Mieller, Björn; Belli, Renan (Advanced Engineering Materials, 2024)
Modern dry pressing of ceramic powders using spray-dried granulates cannot avoid the occurrence of defects related to persisting inter- and intra-granulate interstitial voids. These constitute the parent defect size population limiting the application of polycrystalline ceramics in high-stress conditions. The mitigation of such defects could widen the range of application in technical and biomedical engineering, reduce the safety range for design, and extend the lifetime of components. Herein, the Weibull size-effect on strength in size-partitioned Yttria-stabilized zirconias (YSZ) feedstocks is used to explore the viability of changing the density distribution of granulate sizes as an effective strategy to obtain a denser particle packing that could reduce the size distribution of strength-limiting pressing defects. In a direct assessment of critical defect size using multiscale strength testing with a dataset of ≈1300 values, the success of such an approach in increasing the strength reliability for small volume components is demonstrated, along with its ultimate failure in altering the defect size distribution in sintered YSZ ceramics across several length scales. Finally, it is shown that granule morphology (spherical or dimpled) fails to affect the defect density and size distribution in YSZ ceramics.<br
Keywords: powder processing; pressing defects; strength; Weibull statistics; zirconia ceramics

Intricacies involving the evaluation of fracture toughness obtained by the surface-crack-in-flexure method - Lubauer, Julia; Lohbauer, Ulrich; Henrich, Martina; Munz, Maximilian; Lube, Tanja; Belli, Renan (Journal of the American Ceramic Society, 2022)
Among the several methods available for the measurement of the fracture toughness (KIc), the surface-crack-in-flexure (SCF) has the advantages of being based on an easy-to-produce short (application relevant) crack size of defined geometry with a naturally sharp crack tip. The production of ready-to-test cracked specimens is fast and uncomplicated, rendering accurate results with low scatter. However efficient and reliable, the procedural steps for the obtainment of a valid crack need revisions, especially on aspects concerning the polishing depth, the removal of lateral cracks, the obtainment of an appropriate crack geometry, and the use of adequate solutions for the geometry factor. In this study we attend to these issues by systematically polishing a large number of specimens of two ceramic materials having very distinct subsurface Knoop crack systems to assess the effect of remnants of lateral cracks. By evaluating the geometry factor of the median precrack along the entire crack front, we provide valid ranges for the crack geometry regarding the crack-surface intersection angle as resulting from the polishing depth, extending the applicability of the Strobl et al. solution to shallow cracks in detriment of the Newman and Raju formula that is poised to overestimations of KIc of up to 10%. Our results debunk the belief that lateral cracks affect the obtained KIc, but demonstrate the necessity of a minimum polishing depth for the attainment of valid crack geometries.
CRIS-Team Scopus Importer:2022-08-12
Keywords: fracture toughness; Knoop indentation; lateral cracks; lithium disilicate; silicon nitride; stress intensity factor; surface-crack-in-flexure

In vitro lifetime of zirconium dioxide-based crowns veneered using Rapid Layer Technology - Riedel, Christopher; Wendler, Michael; Belli, Renan; Petschelt, Anselm; Lohbauer, Ulrich (European Journal of Oral Sciences, 2019)
Rapid Layer Technology (RLT) uses computer-aided design/computer-aided manufacturing (CAD/CAM) to manufacture a veneer layer that is adhesively bonded to the zirconia framework, avoiding firing steps during the fabrication process and thus preventing build-up of residual stresses. This work studied, using sliding contact fatigue, the in vitro lifetime of restorations produced using RLT compared with restorations produced using conventional veneering techniques. Zirconia copings were veneered with a conventional hand-layering method (VM9) using a fast (n = 16) or a slow (n = 16) cooling protocol, or with RLT. For the latter, the veneers were CAD/CAM fabricated using a feldspathic reinforced-glass (Vitablocs Mark II; n = 16) or a polymer-infiltrated reinforced-glass network (Enamic; n = 16) and adhesively bonded to the zirconia frameworks. Crowns thus obtained were submitted to sliding contact fatigue against a steatite indenter in a chewing simulator until failure. A Kaplan-Meier survival analysis was conducted. None of the hand-layered restorations survived after a 2 x 10(6)-cycle interval, whereas no fractures in the RLT groups were observed. Vitablocs Mark II veneers survived for a longer testing period (3.5 x 10(6) cycles) than their Enamic counterparts (2.5 x 10(6) cycles) owing to their superior wear behavior. The RLT represents an efficient method to veneer zirconia frameworks by reducing processing steps and, more importantly, increasing the lifetime of the restorations.
CRIS-Team WoS Importer:2019-03-26

In vitro wear gap formation of self-adhesive resin cements: A CLSM evaluation - Belli, Renan; Pelka, Matthias; Petschelt, Anselm; Lohbauer, Ulrich (Journal of Dentistry, 2009)
Objectives: To evaluate the depth of wear gaps of new self-adhesive cements after toothbrush abrasion and ACTA wear test. Methods: Luting spaces (325 ± 25 μm width, 2 mm depth) were produced in Empress 2 ceramic blocks with a diamond saw to obtain flat substrate segments for toothbrush abrasion (n = 24) and ACTA wear (n = 27). After etching and silanization, the slits were filled with 8 self-adhesive cements, 2 conventional resin cements and 1 flowable composite, stored for 2 weeks in distilled water at 37 °C and planished to the cement level. Toothbrush abrasion was carried out in a toothbrush simulator (Willytec, Germany) for 20,000 cycles (load 1 N) using an abrasive slurry based on a commercial toothpaste (Elmex, Gaba, Germany, RDA = 77). The ACTA wear experiment was performed following the ACTA protocol in millet seed slurry for 400,000 cycles (Willytec). The gap replicas were measured for vertical wear loss under a confocal laser scanning microscope (CLSM). The data were analyzed using one-way ANOVA and a mod-LSD test at p < 0.05. Results: Toothbrush wear values were lower than the ones obtained for the ACTA wear test for all cements. In the toothbrush test Bifix SE, Clearfil SA, SmartCem 2, G-Cem and Maxcem Elite obtained the highest values together with Grandio Flow. Grandio Flow and AllCem showed to be the most resistant to the ACTA wear test, while SpeedCem the least resistant. No correlation was found between the two wear test experiments. Conclusion: Self-adhesive cements have good wear resistance to toothbrush abrasion but most of them wear more rapidly under higher loads in the ACTA test than conventional resin cements and flowable composites. © 2009 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-01-23
Keywords: ACTA; Cement; Gap; Self-adhesive; Toothbrush; Wear

In vivo shell-like fractures of veneered-ZrO2 fixed dental prostheses - Belli, Renan; Scherrer, Susanne S.; Reich, Sven; Petschelt, Anselm; Lohbauer, Ulrich (Case Studies in Engineering Failure Analysis, 2014)
Fractographic analyses are performed in two fixed dental prosthetic reconstructions made of ZrO2 frameworks covered by a veneering ceramic that fractured during function in the mouth. Processing histories, material properties, recovered broken parts and replicas of the fracture surface were used, along with fractographic markings to determine fracture origins and cause of failure. A shell-like fracture pattern was found common for both cases, although different factors were identified to be involved in each fracture event. Internal thermal residual stresses and occlusal surface defects from localized contact overloading were found to precipitate the fracture in Case 1, whereas extreme occlusal surface damage from sliding chewing contact was determinant in the fracture of Case 2. The interface between the veneering ceramic and the ZrO2 framework was unaffected by the fractures.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Contact damage; Dental ceramics; Dental fractography; Dental prosthesis; Glass-ceramic; Zirconia

Leucite-reinforced glass ceramic inlays luted with self-adhesive resin cement: A 2-year in vivo study - Taschner, Michael; Kraemer, Norbert; Lohbauer, Ulrich; Pelka, Matthias; Breschi, Lorenzo; Petschelt, Anselm; Frankenberger, Roland (Dental Materials, 2012)
Objectives: Aim of the present prospective controlled clinical study was to compare the clinical performances of two different cementation procedures to lute IPS Empress inlays and onlays. Methods: Eighty-three IPS Empress restorations (70 class-II inlays, 13 onlays/47 premolars, 36 molars) were placed in 30 patients (19 females/11 males, mean age = 39 years). Two cementation procedures were tested: group 1: forty-three restorations were luted with a self-adhesive resin cement (RelyX Unicem, RX, 3M ESPE); group 2: forty restorations were luted with an etch-and-rinse multistep adhesive (Syntac Classic, Ivoclar-Vivadent) and Variolink II low (SV, Ivoclar-Vivadent). All restorations were evaluated after 2 weeks (baseline = 1st recall = R1, n = 83), 6 months (R2, n = 83), 1 year (R3, n = 82), and 2 years (R4, n = 82) by two independent blinded calibrated examiners using modified USPHS criteria. Results: From R1 to R4, one failure occurred in the SV group (at R2) due to marginal enamel chipping. After 2 years of clinical service (R4), better marginal and tooth integrity (p < 0.05) was found in group 2 (SV) compared to the use of the self-adhesive cement (RX, group 1), while no differences were found for all remaining investigated criteria (p > 0.05). The absence of enamel in proximal boxes (10% with no enamel and 51% of the restorations with less than 0.5 mm enamel width at the bottom of the proximal box) did not affect marginal performance (p > 0.05). Significance: The self-adhesive resin cement RelyX Unicem showed clinical outcomes similar to a conventional multi-step cementation procedure after 2 years of clinical service for most of the tested criteria. © 2011 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Ceramic; Clinical trials; Inlay; Resin cement; Self-adhesive

Long-term stability of aerophilic metallic surfaces underwater - Tesler, Alexander; Kolle, Stefan; Prado, Lucia; Thievessen, Ingo; Böhringer, David; Backholm, Matilda; Karunakaran, Bhuvaneshwari; Nurmi, Heikki A.; Latikka, Mika; Fischer, Lena; Stafslien, Shane; Cenev, Zoran M.; et al. (Nature Materials, 2023)
Aerophilic surfaces immersed underwater trap films of air known as plastrons. Plastrons have typically been considered impractical for underwater engineering applications due to their metastable performance. Here, we describe aerophilic titanium alloy (Ti) surfaces with extended plastron lifetimes that are conserved for months underwater. Long-term stability is achieved by the formation of highly rough hierarchically structured surfaces via electrochemical anodization combined with a low-surface-energy coating produced by a fluorinated surfactant. Aerophilic Ti surfaces drastically reduce blood adhesion and, when submerged in water, prevent adhesion of bacteria and marine organisms such as barnacles and mussels. Overall, we demonstrate a general strategy to achieve the long-term stability of plastrons on aerophilic surfaces for previously unattainable underwater applications.
CRIS-Team Scopus Importer:2023-09-29

Low-temperature degradation increases the cyclic fatigue resistance of 3Y-TZP in bending. - Belli, Renan; Loher, Claudia; Petschelt, Anselm; Cicconi, Maria Rita; de Ligny, Dominique; Anglada, Marc; Lohbauer, Ulrich (Dental Materials, 2020)
OBJECTIVE: Due to past failures of orthopedic 3Y-TZP femoral implants linked to accelerated tetragonal-to-monoclinic phase transformation (t → m), the susceptibility to 'low-temperature degradation' or 'ageing' of 3Y-TZP has been advertised as detrimental to its long-term structural stability. However, no systematic mechanistic experiments on the fatigue resistance of aged 3Y-TZP under cyclic loading can support such statement. In this study, we aim to clarify this issue. METHODS: Here we evaluate the subcritical crack growth behavior of 3Y-TZP under cyclic loading after 0-50 h of accelerated ageing in an autoclave at 134 °C. The same 3Y-TZP sintered at two different temperatures (1450 °C or 1650 °C) allows for the comparison of materials containing grains with different susceptibilities to transformation. The volume fraction of surface transformed grains was measured using Raman spectroscopy, and the depth of the transformed surface layer from trenches milled with a Focus-Ion Beam. The fracture toughness before and after ageing was determined using the Chevron-notch Beam method. The quasi-static flexural strength was measured in dry conditions and the cyclic lifetime in water at 10 Hz and R-ratio = 0.3 in 4-point-bending at different applied stresses. The fatigue parameter n was derived from 3 different methods, namely SN curves, crack velocity plots and Weibull distributions. RESULTS: The progression of transformation showed linear kinetics with higher rates for the 3Y-TZP sintered at 1650 °C. Accelerated transformation induced severe crack formation within the transformed layer with parallel orientation to the surface plane, which supposedly behaved as the critical crack size population governing fracture. The stress intensity factor within the transformed layer was increased due to compressive stresses. Consequently, the fatigue parameter n increased consistently from 5 to 50 h of ageing, regardless of the derivation method, suggesting an increased resistance against crack growth during cyclic loading in bending. SIGNIFICANCE: Our results do not support the long suggested negative clinical implications of LTD regarding mechanical performance, to the contrary, LTD seems to increase the resistance against subcritical crack growth in a humid environment in bending.
EVALuna2:382963

Low-temperature degradation increases the cyclic fatigue resistance of 3Y-TZP in bending - Belli, Renan; Loher, Claudia; Petschelt, Anselm; Cicconi, Maria Rita; de Ligny, Dominique; Anglada, Marc; Lohbauer, Ulrich (Dental Materials, 2020)
Objective: Due to past failures of orthopedic 3Y-TZP femoral implants linked to accelerated tetragonal-to-monoclinic phase transformation (t → m), the susceptibility to ‘low-temperature degradation’ or ‘ageing’ of 3Y-TZP has been advertised as detrimental to its long-term structural stability. However, no systematic mechanistic experiments on the fatigue resistance of aged 3Y-TZP under cyclic loading can support such statement. In this study, we aim to clarify this issue. Methods: Here we evaluate the subcritical crack growth behavior of 3Y-TZP under cyclic loading after 0–50 h of accelerated ageing in an autoclave at 134 °C. The same 3Y-TZP sintered at two different temperatures (1450 °C or 1650 °C) allows for the comparison of materials containing grains with different susceptibilities to transformation. The volume fraction of surface transformed grains was measured using Raman spectroscopy, and the depth of the transformed surface layer from trenches milled with a Focus-Ion Beam. The fracture toughness before and after ageing was determined using the Chevron-notch Beam method. The quasi-static flexural strength was measured in dry conditions and the cyclic lifetime in water at 10 Hz and R-ratio = 0.3 in 4-point-bending at different applied stresses. The fatigue parameter n was derived from 3 different methods, namely S[sbnd]N curves, crack velocity plots and Weibull distributions. Results: The progression of transformation showed linear kinetics with higher rates for the 3Y-TZP sintered at 1650 °C. Accelerated transformation induced severe crack formation within the transformed layer with parallel orientation to the surface plane, which supposedly behaved as the critical crack size population governing fracture. The stress intensity factor within the transformed layer was increased due to compressive stresses. Consequently, the fatigue parameter n increased consistently from 5 to 50 h of ageing, regardless of the derivation method, suggesting an increased resistance against crack growth during cyclic loading in bending. Significance: Our results do not support the long suggested negative clinical implications of LTD regarding mechanical performance, to the contrary, LTD seems to increase the resistance against subcritical crack growth in a humid environment in bending.
CRIS-Team Scopus Importer:2020-06-09
Keywords: Ageing; Dental zirconia; Mechanical properties; Monoclinic; Subcritical crack growth

Measurement of cement thickness under lithium disilicate crowns using an impression material technique - Reich, Sven; Uhlen, Sophia; Gozdowski, Stephan; Lohbauer, Ulrich (Clinical Oral Investigations, 2011)
According to the literature, marginal gaps below 120 μm are recommended for conventionally cemented crown restorations. Therefore, the null hypothesis tested was as follows: the upper bound of the 95% confidence interval of the marginal accuracy of chair-side generated lithium disilicate crowns lies below 120 μm. Prior to definite insertion, the accuracy of 20 lithium disilicate crowns (e. max CAD LT) was evaluated by a replica technique. A light-body silicone was used to document the gap between crown and abutment. The thickness of the light-body silicone layer was examined under microscope (MM40, Nikon Corp., Tokyo, Japan; magnification, ×50) at four different landmarks (LM): LM1 = marginal discrepancy, LM2 = mid-axial discrepancy of the inner crown surface, LM3 = axio-occlusal discrepancy, and LM4 = mid-occlusal discrepancy. At LM1, the mean marginal discrepancy revealed 100 μm (SD, ±61 μm); the median was 81 μm. The lower bound of the 95% confidence interval was 90 μm, and the upper bound was 110 μm. The means of internal gaps at LM2, LM3, and LM4 showed 148 μm (SD, ±61 μm), 227 μm (SD, ±83 μm), and 284 μm (SD, ±95 μm), respectively. The lower bounds of the 95% confidence interval revealed values between 137 μm (LM2) and 269 μm (LM4). The upper bounds were between 158 μm (LM2) and 300 μm (LM4). The null hypothesis was not rejected. Within the limits of the study, the chair-side generated lithium disilicate crowns exhibited a sufficient clinical accuracy. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Accuracy; Ceramics; Chair-side; Clinical trial; Crown; Dental materials; Lithium disilicate; Marginal gap

Measurement of Tooth Wear by Means of Digital Impressions: An In-Vitro Evaluation of Three Intraoral Scanning Systems - Kuehne, Christina; Lohbauer, Ulrich; Raith, Stefan; Reich, Sven (Applied Sciences, 2021)
This in-vitro study aimed to investigate whether intraoral scanners (IOS) are suitable for wear measurement compared to optical profilometry (WLP). A zirconia cast representing the teeth (24-28) was fabricated. It was digitized six times using three different intraoral scanners, Cerec Omnicam AC (OC), Trios 3 (Tr3), and True Definition (TD). The scans were conducted at baseline (t0) and at three different stages of simulated wear (t1-t3), each at one wear-facet on FDI 26 and FDI 27. WLP was used as a reference method. Within each acquisition system, the maximum wear at each facet was analyzed by superimposing the STL data of t0 with t1-t3. A power analysis was performed (G*Power), and the Wilcoxon-signed-rank-test was used to evaluate whether there were statistically significant differences between the groups (Bonferroni corrected) (alpha = 0.05). At wear-facet FDI 27, differences from +4% t1 TD up to +19% t2 OC, corresponding to a metric value of 8 mu m and 45 mu m, were measured. At FDI 26 deviations between -2% t1 Tr3, and +10% OC and Tr3, were observed. Considering some limitations, the IOS are a promising alternative to wear measurement based on WLP due to its simple application to capture surface changes in a reasonable and quick way.
CRIS-Team WoS Importer:2021-06-25

Mechanical and hydrolytic degradation of an Ormocer®-based Bis-GMA-free resin composite - Klauer, Elena; Belli, Renan; Petschelt, Anselm; Lohbauer, Ulrich (Clinical Oral Investigations, 2018)
OBJECTIVES: The aim of the study was to evaluate the mechanical stability of bisphenol A-glycidyl methacrylate (Bis-GMA) and Ormocer-based resin composites before and after water absorption and to examine water saturation. MATERIAL AND METHODS: Disc-shaped specimens of the Bis-GMA (Grandio SO, Voco) and the Ormocer-based (Admira Fusion, Voco) dental resin composites were produced, stored in water, and weighed after pre-determined times to measure the absorbed water. Bend bars were produced and stored for 24 h in dry conditions as well as in distilled water for 14 days or 60 days at 37 °C. The initial flexural strength (FS) under quasi-static loading and flexural fatigue strength (FFS) under cyclic loading were determined under 4-point bending. Fracture toughness (KIc) of both composites was measured using the single-edge-V-notch-beam (SEVNB) technique after the same storage conditions under 3-point bending. RESULTS: Within the first 14 days, storage conditions did not affect the initial FS of Grandio SO, while a significant drop in initial FS was observed for Admira Fusion after 2 weeks in water and most of the water was absorbed within this time. FFS for the Bis-GMA composite was not reduced before 2 months in water, whereas for the Ormocer®-based composite, there has been a significant decrease in strength after cyclic fatigue already at 2 weeks of water storage. KIc of Admira Fusion decreased significantly after both storage periods, while KIc of Grandio SO decreased only significantly after 2 weeks of water storage. CONCLUSION: All mechanical properties of the Bis-GMA composite were superior to those of the Ormocer®-based material, except water sorption. CLINICAL SIGNIFICANCE: Water storage seems to have a much more pronounced effect on the mechanical properties of Ormocer®-based dental composites in comparison to Bis-GMA-based composites.
EVALuna2:34642

Mechanical degradation of contemporary CAD/CAM resin composite materials after water ageing - Wendler, Michael; Stenger, Anja; Ripper, Julian; Priewich, Eva; Belli, Renan; Lohbauer, Ulrich (Dental Materials, 2021)
Objective: The aim of the present study was to assess the effect of water storage on the quasi-static properties and cyclic fatigue behavior of four contemporary CAD/CAM resin composite materials. Methods: The CAD/CAM resin composites Grandio Blocs, LavaTM Ultimate, CerasmartTM and Brilliant Crios, as well as the direct resin composite Grandio SO, were evaluated. Rectangular plates were cut from the blocks or fabricated using a silicon mold to obtain specimens for fracture toughness (KIc, n = 10), biaxial strength (σ0, n = 30) and cyclic fatigue testing (n = 30). Half of the specimens was stored for 24 h in dry conditions and the other half was aged for 60 days in distilled water at 37 °C. KIc was determined using the Compact-Tension (C(T)) method and σ0 and cyclic fatigue were tested using the Ball-on-Three-Balls assembly. Additional disc-shaped specimens (n = 5) were produced to obtain water sorption curves of the materials. Weibull statistics and two-way ANOVA with Tukey's post-hoc test were used for data assessment. Results: The highest water sorption was observed for LavaTM Ultimate (42.6 μg/mm3), whereas Grandio SO displayed the lowest uptake (14 μg/mm3). A statistically significant drop in KIc and σ0 was measured for all materials after water storage, except for the σ0 of CerasmartTM. Water ageing had a dissimilar effect on the cyclic fatigue behavior, increasing the slow crack growth susceptibility of LavaTM Ultimate, but decreasing it for CerasmartTM and Brilliant Crios. Significance: Contemporary CAD/CAM resin composites are susceptible to water driven degradative processes, although differences in filler content and resin matrix constitution play an important role in how it impacts their mechanical properties.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Biaxial strength; CAD/CAM; Cyclic fatigue; Fracture toughness; Hydrolytic degradation; Resin composite; Water sorption

Mechanical fatigue degradation of ceramics versus resin composites for dental restorations - Belli, Renan; Geinzer, Eva; Muschweck, Anna; Petschelt, Anselm; Lohbauer, Ulrich (Dental Materials, 2014)
For posterior partial restorations an overlap of indication exists where either ceramic or resin-based composite materials can be successfully applied. The aim of this study was to compare the fatigue resistance of modern dental ceramic materials versus dental resin composites in order to address such conflicts.Bar specimens of five ceramic materials and resin composites were produced according to ISO 4049 and stored for 14 days in distilled water at 37°C. The following ceramic materials were selected for testing: a high-strength zirconium dioxide (e.max ZirCAD, Ivoclar), a machinable lithium disilicate (e.max CAD, Ivoclar), a pressable lithium disilicate ceramic (e-max Press, Ivoclar), a fluorapatite-based glass-ceramic (e.max Ceram, Ivoclar), and a machinable color-graded feldspathic porcelain (Trilux Forte, Vita). The composite materials selected were: an indirect machinable composite (Lava Ultimate, 3M ESPE) and four direct composites with varying filler nature (Clearfil Majesty Posterior, Kuraray; GrandioSO, Voco; Tetric EvoCeram, Ivoclar-Vivadent; and CeramX Duo, Dentsply). Fifteen specimens were tested in water for initial strength (?in) in 4-point bending. Using the same test set-up, the residual flexural fatigue strength (?ff) was determined using the staircase approach after 10(4) cycles at 0.5 Hz (n=25). Weibull parameters ?0 and m were calculated for the ?in specimens, whereas the ?ff and strength loss in percentage were obtained from the fatigue experiment.The zirconium oxide ceramic showed the highest ?in and ?ff (768 and 440 MPa, respectively). Although both lithium disilicate ceramics were similar in the static test, the pressable version showed a significantly higher fatigue resistance after cyclic loading. Both the fluorapatite-based and the feldspathic porcelain showed equivalent initial and cyclic fatigue properties. From the composites, the highest filled direct material Clearfil Majesty Posterior showed superior fatigue performance. From all materials, e.max Press and Clearfil Majesty Posterior showed the lowest strength loss (29.6% and 32%, respectively), whereas the other materials lost between 41% and 62% of their flexural strength after cyclic loading.Dental ceramics and resin composite materials show equivalent fatigue strength degradation at loads around 0.5?in values. Apart from the zirconium oxide and the lithium disilicate ceramics, resin composites generally showed better ?ff after 10,000 cycles than the fluorapatite glass-ceramic and the feldspathic porcelain. Resin composite restorations may be used as an equivalent alternative to glass-rich-ceramic inlays regarding mechanical performance.
EVALuna2:24664

Microstructure of veneered zirconia after surface treatments: A TEM study - Grigore, Alexandra; Spallek, Stefanie; Petschelt, Anselm; Butz, Benjamin; Spiecker, Erdmann; Lohbauer, Ulrich (Dental Materials, 2013)
Signcance. Regardless of the treatment protocol and produced roughness, the veneering ceramic perfectly sealed the zirconia surface. XRD showed an increased amount of monoclinic phase on the surface treated zirconia. However after thermal treatment, the monoclinic phase was re-transformed into the tetragonal polymorph. TEM/SAED analysis has found indication for a greater extend of the monoclinic transformation into the bulk zirconia compared to the treatment related defective zone depth. (C) 2013 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Y-TZP; X-ray diffraction; Martensitic transformation; Sandblasting; Bur drilling; Annealing

Mixed-mode fracture toughness of texturized LS2 glass-ceramics using the three-point bending with eccentric notch test - Belli, Renan; Wendler, Michael; Petschelt, Anselm; Lohbauer, Ulrich (Dental Materials, 2017)
Here we use the 3-point bending with eccentric notch test (3-PBEN) to investigate the fracture behavior of a pressable and a CAD/CAM lithium disilicate (LS2) glass-ceramics under combined mode-I and mode-II loading. The effect of the bulk texturization in the beams of the pressable LS2 is made visible through the fracture trajectory following the most energetically favorable path dictated by the crystallite alignment. The CAD/CAM LS2 shows an isotropic fracture mode but increasing fracture energy with mode-II contribution, similar to the pressable variant.
EVALuna2:24691

New approaches in bonding to glass-ceramic: Self-etch glass-ceramic primer and universal adhesives - Maier, Eva; Bordihn, Vivien; Belli, Renan; Taschner, Michael; Petschelt, Anselm; Lohbauer, Ulrich; Zorzin, José Ignacio (Journal of Adhesive Dentistry, 2019)
Purpose: To investigate the tensile bond strength of silane-containing universal adhesives and self-etch glass-ceramic primer to lithium disilicate glass ceramics (LS2). Materials and Methods: 960 rectangular LS2 bars (7 mm x 3 mm x 9 mm, IPS e.max CAD, Ivoclar Vivadent) were manufactured and divided into 4 groups (n = 240). Group 1 was etched with 5% hydrofluoric acid (HF) for 20 s (VITA Ceramics Etch, Vita Zahnfabrik), group 2 was etched with 5% HF for 20 s and silanized (ESPE Sil, 3M Oral Care), group 3 was pre-treated with a self-etching glass-ceramic primer (Monobond Etch & Prime, Ivoclar Vivadent, and group 4 received no pre-treatment. Three universal adhesives (iBOND Universal, Heraeus Kulzer; Scotchbond Universal Adhesive, 3M Oral Care; Futurabond U, Voco) were applied to the differently pre-treated surfaces, with Heliobond (Ivoclar Vivadent) serving as control. The bars from each group were paired and luted perpendicularly, forming a square bonded area of 9 mm2, using Variolink II (Ivoclar Vivadent) with a constant pressure of 10 N, followed by light curing (40 s at 800 mW/cm2, Elipar Trilight, 3M Oral Care). The resulting specimens were stored for 24 h at 37°C in distilled water. Half of the specimens of each group were submitted to tensile bond strength testing, the other half were thermocycled ([TC] 5000 cycles, 5°C/55°C, 30-s dwell time) before testing. Data were analyzed using three-way ANOVA (α = 0.05). Results: Group 2 (HF etched and silanized) and group 3 (self-etching glass-ceramic primer) reached significantly higher mean bond strengths than did groups 1 (only HF etched) and 4 (no pre-treatment). Conclusion: Additional silanization of HF-etched LS2 statistically signficantly improved the tensile bond strength of the silane-containing universal adhesive (Scotchbond Universal). The self-etching glass-ceramic primer Monobond Etch & Prime achieved mean bond strengths that did not differ significantly from HF-etched and silanized specimens.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Lithium disilicate ceramic; Self-etch glass ceramic primer; Silanization; Tensile bond strength; Universal adhesive

Nucleation mechanisms in a SiO2-Li2O-P2O5-ZrO2 biomedical glass-ceramic: Insights on crystallisation, residual glasses and Zr4+ structural environment - Cicconi, Maria Rita; Belli, Renan; Brehl, Martin; Lubauer, Julia; Hayakawa, T.; Kimura, K.; Hirota, T.; Usui, K.; Kohara, S.; Onodera, Y.; Lohbauer, Ulrich; Hayashi, K.; et al. (Journal of the European Ceramic Society, 2022)
In manufacturing reliable glass-ceramics, bulk chemistry and appropriate thermal treatments are critical points. To better understand the influence of nucleation parameters on the crystallisation behaviour and mechanical properties of multicomponent glass-ceramics, we studied the effects of time and temperature on phase stabilisation, the evolution of the crystal phases and physical properties of a Zr-rich lithium-silicate having a SiO2/Li2O molar ratio < 2. Here, we also provide insights into the structural environment of Zr4+ at the early stage of nucleation by Anomalous X-ray Scattering (AXS). By reverse-engineering a commercial material through remelting and sequential thermal treatments, we observed the strong effect of the nucleation temperature on the final mineral assemblage and of the volume fractions of the lithium-disilicate phase on the fracture toughness (KIc). Indeed, the KIc value was increased from ∼0.8 MPa.m½ in the pristine glass up to ∼ 2 MPa.m½, if compared to the original commercial material exhibiting a KIc value of 1.6 MPa.m½. Furthermore, the synthesis of residual glasses at different stages of the thermal treatments allowed us to observe the changes in the glass network structure and properties. AXS was used to extract the contribution exclusively coming from Zr for different nucleation steps. The differential pair distribution functions ΔZrg(r) show two distinct peaks at ∼2.10 Å and 3.44 Å, respectively associated with Zr-O and Zr-Zr/Zr-Si correlations with the formation of edge sharing in addition to corner sharing polyhedra. It was discerned the occurrence of (sub)nano-sized clusters enriched in Zr. These local clusters do not show changes during the different thermal treatments, either for higher temperatures or longer times. No Zr phases are stabilised in the crystallised materials, suggesting that these clusters do not evolve above the critical nucleus size. All evidence points to a highly heterogeneous environment and the coexistence of three structural regions i) (sub)nano Zr-clusters, ii) P enriched μ-areas, iii) residual silicate glass. The evolution and spatial distribution of these units influence the final properties.
CRIS-Team Scopus Importer:2022-01-21
Keywords: AXS; Raman; Residual glasses; Structure; Toughness; Zr

On the assignment of quartz-like LiAlSi2O6 - SiO2 solid solutions in dental lithium silicate glass-ceramics: Virgilite, high quartz, low quartz or stuffed quartz derivatives? - Hurle, Katrin; Lubauer, Julia; Belli, Renan; Lohbauer, Ulrich (Dental Materials, 2022)
Objectives: Here we aim to provide a background on X-Ray Diffraction analysis of quartz-like crystal structures with varying amounts of Al3+ and Li+ substitution, existing confusions on their nomenclature and its implications for novel lithium silicate glass-ceramics. Methods: We reviewed the literature dealing with modifications of the quartz crystal structure and their stuffed LiAlSi2O6 derivates, LiAlSi2O6 – SiO2 solid solutions, the terminology of such phases and criteria used to define the structure known as virgilite. Based on this information, we attempted to allocate the quartz-like phases found in CEREC TesseraTM, InitialTM LiSi Block and Amber® Mill in the range of LiAlO2 - SiO2 solid solutions. For this purpose, their lattice parameters obtained from Rietveld refinement were compared with the lattice parameters of members of the corresponding solid solutions with defined SiO2 molar fraction found in the literature. Results: Based on the lattice parameters available for low quartz, high quartz and its stuffed derivatives, including LiAlSi2O6 and the mineral virgilite, a plot of the a- and c-parameters vs. the mol% SiO2 related to LiAlO2 was constructed with the literature data and the data found for the three dental lithium silicates. As per the definitions of virgilite as either LixAlxSi3-xO6, with 0.5 < x < 1 or especially as members of the LiAlSi2O6 – SiO2 solid-solution series with more than 50 mol% LiAlSi2O6, the crystal structures in CEREC TesseraTM, InitialTM LiSi Block and Amber® Mill failed to fall within the ranges of mol% SiO2 confined for virgilite. Significance: Based on available literature and definitions, the quartz-like phases found in the three dental lithium silicates should be addressed as stuffed (probably low) quartz solid solutions instead of “virgilite”. However determined by mineralogical practices, the term “virgilite” for parts of the LiAlSi2O6 – SiO2 solid solution is ambiguous and can be considered as arbitrary.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Crystal; Glass-ceramics; Lithium silicate; Quartz; Virgilite; X-ray diffraction

On the robustness of the Single-Edge-Precracked-Beam (SEPB) method for fracture toughness testing of ceramic materials - Schellenberger, Anja; Belli, Renan; Karsten, Jürgen; Lohbauer, Ulrich (Engineering Fracture Mechanics, 2023)
The Single-Edge-Precracked-Beam (SEPB) method for the testing of fracture toughness (KIc) of ceramic materials is a variation of the Single-Edge-Cracked-Beam (SEPB) method for the test of metallic materials that creates a sharp precrack not by fatigue, but by a “bridge indentation” technique that induces a crack to pop-in under compression loading. This precrack is sharp and overcomes the issue of blunt notch-root radii resulting from the Single-Edge-V-Notched-Beam (SEVNB) method, which overestimates the KIc of ceramics with submicrometric microstructures. However, the difficulties in obtaining a valid precrack and measurement make of the SEPB a low-yield, time- and cost-intensive method. Here we evaluate the SEPB method using large datasets of two fine dental grade ceramics to assess the sensitivity of the validity criteria in ISO 15732 and ASTM C 1421 and the effect of their violations in the obtained KIc. We compile datasets including or excluding validity criteria and combine those of the two standards to establish their effect on the mean and scatter of the data. We discuss the appropriateness of the validity ranges and of some criteria as a whole, while arguing for tightening the criterion precrack frontline asymmetry and for the dropping of criteria regulating the extent of stable crack extension.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Ceramics; Fracture mechanics; Fracture toughness; Lithium disilicate; Single-Edge-Precracked-Beam; Zirconia

Optical profilometry versus intraoral (handheld) scanning - Hartkamp, O.; Peters, F.; Bothung, H.; Lohbauer, Ulrich; Reich, S. (International Journal of Computerized Dentistry, 2017)
The aim of this study was to evaluate the difference in maximum height loss values obtained from datasets based on optical profilometry and intraoral scanning. Additionally, two analysis applications were tested with respect to their correspondence.To obtain baseline data, the occlusal surface of a metal phantom tooth was scanned by optical profilometry [WLP] and an intraoral scanner [IOS]. Then, wear was simulated at two locations of the tooth, three times each ([wear1], [wear2], and [wear3]), and the surface was captured after each status of wear, applying [WLP] and [IOS]. The maximum vertical height loss was evaluated by comparing the 3D datasets of [WLP] and [IOS] at [wear1], [wear2], and [wear3] with the baseline data of [WLP] and [IOS], respectively. For this purpose, two commercially available applications, Geomagic Qualify and Oracheck, were used.Apart from one outlier of 16% difference between the data obtained from [WLP] and [IOS], the maximum difference was 12.6%, which was equal to a metrical value of 15 µm. For the corresponding values, which were calculated with Geomagic Qualify and Oracheck at identical wear facets, maximum differences between +7% and -6.7% were obtained.According to this in vitro study, the wear measurement on the basis of [IOS] seems to be a cost-effective, quick, and easily applicable tool for clinical screening purposes, with an acceptable reliability. With respect to the minor variations between each other, the Geomagic Qualify and Oracheck measurement applications are equivalent.
EVALuna2:24696

Optische profilometrie versus handgeführtes scannen: Eine in-vitro-machbarkeitsstudie zur vertikalen verschleißmessung [Optical profilometry versus intraoral (handheld) scanning: In vitro feasibility study of vertical wear measurement] - Hartkamp, Oliver; Peters, Florian; Bothung, Hannes; Lohbauer, Ulrich; Reich, Sven (International Journal of Computerized Dentistry, 2017)
Aim: The aim of this study was to evaluate the difference in maximum height loss values obtained from datasets based on optical profilometry and intraoral scanning. Additionally, two analysis applications were tested with respect to their correspondence. Materials and methods: To obtain baseline data, the occlusal surface of a metal phantom tooth was scanned by optical profilometry [WLP] and an intraoral scanner [IOS]. Then, wear was simulated at two locations of the tooth, three times each ([wear1], [wear2], and [wear3]), and the surface was captured after each status of wear, applying [WLP] and [IOS]. The maximum vertical height loss was evaluated by comparing the 3D datasets of [WLP] and [IOS] at [wear1], [wear2], and [wear3] with the baseline data of [WLP] and [IOS], respectively. For this purpose, two commercially available applications, Geomagic Qualify and Oracheck, were used. Results: Apart from one outlier of 16% difference between the data obtained from [WLP] and [IOS], the maximum difference was 12.6%, which was equal to a metrical value of 15 μm. For the corresponding values, which were calculated with Geomagic Qualify and Oracheck at identical wear facets, maximum differences between +7% and -6.7% were obtained. Conclusions: According to this in vitro study, the wear measurement on the basis of [IOS] seems to be a cost-effective, quick, and easily applicable tool for clinical screening purposes, with an acceptable reliability. With respect to the minor variations between each other, the Geomagic Qualify and Oracheck measurement applications are equivalent.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Analysis; Digital; Impression; In vitro; Intraoral; Profilometry; Wear

Phase characterization of lithium silicate biomedical glass-ceramics produced by two-stage crystallization - Hurle, Katrin; Belli, Renan; Götz-Neunhoeffer, Friedlinde; Lohbauer, Ulrich (Journal of Non-Crystalline Solids, 2019)
A commercially available lithium (di)silicate glass-ceramic used for dental prostheses was characterized with respect to its quantitative phase composition and crystallinity. For analysis of quantitative phase content, X-ray diffraction (XRD) was used combined with the G-factor method, an external standard technique. Samples of the material were analyzed in the pre-crystallized state and after final crystallization heat-treatment in order to characterize the changes occurring during the final crystallization stage. The bulk chemical composition of the commercial blocks, matching the composition of the precursor glass, was determined by a combination of X-ray Fluorescence (XRF) and Inductively Coupled Plasma - Optical Emission Spectroscopy (ICP-OES) analysis.
CRIS-Team WoS Importer:2019-04-04

PH neutralization and influence on mechanical strength in self-adhesive resin luting agents - Zorzin, José Ignacio; Petschelt, Anselm; Ebert, Johannes; Lohbauer, Ulrich (Dental Materials, 2012)
Objective: The aim of this study was to evaluate if pH-neutralization behavior of self-adhesive resin cements has an influence on their mechanical properties. Methods: pH-neutralization, water sorption, solubility and flexural strength of G-Cem Automix (GCA), G CEM Capsules (GCC), Maxcem Elite (MCE), RelyX Unicem Clicker (RXC), RelyX Unicem Maxicap (RXM), RelyX Unicem 2 (RX2), and Speed-Cem (SPC) were tested in self-curing mode. Specimen's pH-values were recorded up to 24 h with a pH-electrode. Water sorption (WS) and solubility (SO) were measured. Flexural strength (FS) was evaluated before and after thermocycling (TC) and fracture surfaces analyzed under SEM. Results: RX2 (pH 24 5.89), RXC (pH 24 5.49) and SPC (pH 24 5.42) showed highest 24 h pH-values, followed by GCA (pH 24 5.34). Capsulated products and MCE (pH 24 3.90) reached lower pH-values. GCC (75.78 μg/mm 3) showed the highest WS followed by MX (69.64 μg/mm 3), RXM (64.76 μg/mm 3), GCA (25.86 μg/mm 3) and SPC (30.42 μg/mm 3). Capsulated products RXM (56.58 μg/mm 3) and GCC (30.94 μg/mm 3) presented the highest SO, GCA (4.06 μg/mm 3) and SPC (4.26 μg/mm 3) revealed the lowest. GCA (114.03 MPa) had the highest initial FS followed by SPC (79.81 MPa), RXM (41.61 MPa) the lowest. FS of all materials decreased significantly after TC except for RXC (44.65 MPa) and RX2 (65.92 MPa). FS of GCC (16.47 MPa) and MCE (28.21 MPa) decayed the most. A highly linear correlation was observed between percentage decrease of FS after TC and 24 h pH-values (R 2 = 0.861). Significance: Within the limits of this study pH-neutralization behavior has an influence on mechanical stability. When using self-adhesive resin luting agents, automix-syringe products with improved pH-neutralization behavior should be favored. © 2012 Academy of Dental Materials.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Dental cement; Flexural strength; Luting agent; Mechanical stability; pH; Physical behavior; Self-adhesive; Water solubility; Water sorption

Pitfalls of determining the elastic properties of stabilized zirconia with indentation methods - Werbach, K.; Hummel, S.; Ebner, C.; Lohbauer, Ulrich; Peterlik, H. (Ceramics International, 2019)
Indentation methods have become popular for determining Young's modulus of materials. Though for most materials this method has been successfully applied, significant errors in the results can occur if materials respond unfavorably to standard indentation parameters. This paper presents an investigation of the effects of microindentation on yttria-stabilized zirconia compared to bulk properties obtained from resonant ultrasound spectroscopy. We not only observed different results for each method, but also a significant change of Young's modulus with indentation depth. Analysis of the microhardness indents with Raman spectroscopy revealed an indentation-induced tetragonal to monoclinic phase transformation in the material. This example shows that it is important to consider the effect of high stresses in indentation methods, as they could severely influence the determination of the material's parameters.
CRIS-Team WoS Importer:2019-04-23

Practical and theoretical considerations on the fracture toughness testing of dental restorative materials - Belli, Renan; Wendler, Michael; Zorzin, José Ignacio; Lohbauer, Ulrich (Dental Materials, 2018)
An important tool in materials research, development and characterization regarding mechanical performance is the testing of fracture toughness. A high level of accuracy in executing this sort of test is necessary, with strict requirements given in extensive testing standard documents. Proficiency in quality specimen fabrication and test requires practice and a solid theoretical background, oftentimes overlooked in the dental community.In this review we go through some fundamentals of the fracture mechanics concepts that are relevant to the understanding of fracture toughness testing, and draw attention to critical aspects of practical nature that must be fulfilled for validity and accuracy in results. We describe our experience with some testing methodologies for CAD/CAM materials and discuss advantages and shortcomings of different tests in terms of errors in testing the applicability of the concept of fracture toughness as a single-value material-specific property.
EVALuna2:24705

Preparation and filling of small oval root canals: influence of file system and sealer. - Eichelsdoerfer, Katharina; Buettner, Katharina; Lohbauer, Ulrich; Petschelt, Anselm; Metzger, Zvi; Ebert, Johannes (Quintessence International, 2022)
OBJECTIVE: To carry out a morphometric analysis of small oval root canals prepared with different instruments (part 1) and filled with different sealers (part 2). METHOD AND MATERIALS: Ninety extracted mandibular incisors with small oval root canals were instrumented with Self-Adjusting File (n = 45), XP-endo Finisher (n = 15), GentleFile (n = 15), or Reciproc (n = 15). All groups of part 1 were filled with AH Plus (n = 15 each). For part 2 (including group Self-Adjusting File/AH Plus) teeth instrumented with Self-Adjusting File were additionally filled with GuttaFlow Bioseal (n = 15) or Total Fill BC sealer (n = 15). All sealers were placed with a lentulo and filled with master point and additional points. Serial cuts were made at 1-mm intervals up to 10 mm. Total root canal area, percentage of gutta-percha filled area (PGFA), sealer, voids, and debris were evaluated using interactive image analysis software. RESULTS: Preparation with Reciproc caused significantly wider canals than with Self-Adjusting File, GentleFile, or XP-endo Finisher, but also resulted in the greatest PGFA and lowest percentage of sealer (P ≤ .05). Following XP-endo Finisher, the significantly greatest percentage of debris (30%) was found 1 mm from the apex (P ≤ .05). Regarding different sealers, only minor differences were found (GuttaFlow Bioseal: less percentage of sealer at 2 and 3 mm levels [P ≤ .05]). CONCLUSION: Within the limits of this study Reciproc caused the greatest substance loss, but also the most favorable PGFA. The apical debris accumulation with XP-endo Finisher needs further investigation. The sealers under investigation performed equally well.
EVALuna2:512599

R-curve behavior of a short-fiber reinforced resin composite after water storage - Tiu, Janine; Belli, Renan; Lohbauer, Ulrich (Journal of the Mechanical Behavior of Biomedical Materials, 2020)
As a supplement to our investigation into R-curves in a short-fiber reinforced dental resin composite, we investigate the effects of 2-months water storage. Water is known to degrade the siloxane bonds linking matrix and fillers, which has been suggested to decrease the fracture toughness in conventional resin composites. However, fiber-reinforced systems seem to be less affected as the toughness is dependent on fiber bridging, which is only effective if a weaker interfacial bond between fiber and matrix is present.
CRIS-Team Scopus Importer:2020-02-21

Reducing fractures in diamond-milled lithium metasilicate/disilicate glass-ceramics (LMGC/LDGC) by ultrasonic vibration-assisted machining - Juri, Afifah Z.; Lei, Xiangtian; Dudley, James; Lohbauer, Ulrich; De Souza, Grace M.; Nakanishi, Yoshitaka; Yin, Ling (Journal of the Mechanical Behavior of Biomedical Materials, 2025)
Digital CAD/CAM milling of aesthetic glass-ceramics in dental restorations induces extensive surface damage to the materials, jeopardising the quality of the restorations. This study aimed to reduce fractures in lithium metasilicate and disilicate glass-ceramics (LMGC and LDGC) induced by novel ultrasonic vibration-assisted machining for improved surface quality. Ultrasonic vibration-assisted machining of LMGC and LDGC was performed using a digital high-speed ultrasonic milling machine. Machining-induced surface fractures were quantitatively assessed in terms of 3D surface height, spatial, and hybrid parameters as a function of vibration amplitudes using a 3D white light profilometer. Damage morphologies were examined using scanning electron microscopy (SEM). Machining-induced surface fractures significantly depended on material microstructures, mechanical properties associated with brittleness and machinability indices, and ultrasonic machining vibration amplitudes. Higher brittleness indexed LMGC produced more surface damage than LDGC. Thus, LMGC surfaces had significantly higher 3D surface height, spatial, and hybrid parameters than LDGC, except texture aspect ratios. Brittle fracture dominated all material removal but ultrasonic machining at an optimized vibration amplitude of 3 μm promoted localized ductile deformation in LMGC and LDGC, and significantly improved the surface quality. Ultrasonic vibration-assisted machining at the optimized vibration amplitude enabled the surface quality improvement for both LMGC and LDGC. Further, one-step (direct) machining of LDGC can be approached for rapid high-quality ceramic restorations, replacing the two-step procedure for LMGC and saving the fabrication time.
CRIS-Team Scopus Importer:2025-05-09
Keywords: Damage morphology; Glass-ceramics; Material removal mechanisms; Surface roughness; Ultrasonic vibration-assisted machining

Relationships between fracture toughness, Y2O3 fraction and phases content in modern dental Yttria-doped zirconias - Belli, Renan; Hurle, Katrin; Schürrlein, Jana; Petschelt, Anselm; Werbach, Katharina; Peterlik, Herwig; Rabe, Torsten; Mieller, Björn; Lohbauer, Ulrich (Journal of the European Ceramic Society, 2021)
The relationship between fracture toughness and Yttria content in modern zirconia ceramics was revised. For that purpose, we evaluated here 10 modern Y2O3-stabilized zirconia (YSZ) materials currently used in biomedical applications, namely prosthetic and implant dentistry. The most relevant range between 2-5 mol% Y2O3 was addressed by selecting from conventional opaque 3 mol% YSZ up to more translucent compositions (4−5 mol% YSZs). A technical 2YSZ was used to extend the range of our evaluation. The bulk mol% Y2O3 concentration was measured by X-Ray Fluorescence Spectroscopy. Phase quantification by Rietveld refinement considered two tetragonal phases or an additional cubic phase. A first-account of the fracture toughness (KIc) of the pre-sintered blocks is given, which amounted to 0.4 – 0.7 MPa√m. In the fully-densified state, an inverse power-law behavior was obtained between KIc and bulk mol% Y2O3 content, whether using only our measurements or including literature data, challenging some established relationships. A linear relationship between KIc and the fraction of the transformable t-phase was established within the range of 30–70 vol%.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Dental; Fracture toughness; Power-law; X-ray-diffraction; Yttria; Zirconia

Removal of Radioactively Marked Calcium Hydroxide from the Root Canal: Influence of Volume of Irrigation and Activation - Zorzin, José Ignacio; Wiessner, Jessica; Wiessner, Thomas; Lohbauer, Ulrich; Petschelt, Anselm; Ebert, Johannes (Journal of Endodontics, 2016)
The purpose of this study was to evaluate the amount of calcium hydroxide (Ca[OH]2) removed by irrigation with different volumes and activation methods.One hundred thirty extracted straight, single-rooted human teeth were instrumented to size 45/.04. One hundred twenty teeth were filled with radioactively marked Ca(OH)2 and a gutta-percha point; 10 teeth with only gutta-percha served as a negative control. All specimens were stored in saline solution (7 days at 35°C). After storage, teeth were randomly divided into 12 groups (n = 10). The gutta-percha was taken out, and Ca(OH)2 was removed either by irrigation with different volumes (0 mL, 0.5 mL, 1 mL, 2 mL, 4 mL, or 8 mL) or mechanical activation with a 2- or 4-mL volume using a file (Instr) (FlexMaster size 45/.04; VDW, Munich, Germany), a brush (CanalBrush [CB]; Coltène/Whaledent, Langenau, Germany), or passive ultrasonic irrigation (PUI, smooth wire). Irrigation was performed by alternating 40% citric acid and 3% sodium hypochlorite. Residual Ca(OH)2 was measured by scintillation and expressed as a percentage of the original Ca(OH)2.Increasing the irrigation volume led to a significant decrease (P < .05) of residual Ca(OH)2 (0 mL [98.5%], 0.5 mL [21.7%], 1 mL [16.5%], 2 mL [12.9%], 4 mL [8.7%], 8 mL [5.0%], and negative control [0.0%]). Activation led to less residual Ca(OH)2 (2 mL Instr [12.0%], 2 mL CB [11.7%], 2 mL PUI [9.1%], 4 mL Instr [8.5%], 4 mL CB [7.4%], and 4 mL PUI [6.2%]), with significant differences according to the PUI (P < .05).No irrigation procedure was able to remove Ca(OH)2 completely. PUI was the most effective activation method. However, irrigation with an 8-mL volume was the most effective.
EVALuna2:24681

Repair bond strength of aged resin composite after different surface and bonding treatments - Wendler, Michael; Belli, Renan; Panzer, Reinhard; Skibbe, Daniel; Petschelt, Anselm; Lohbauer, Ulrich (Materials, 2016)
The aim of this study was to compare the effect of different mechanical surface treatments and chemical bonding protocols on the tensile bond strength (TBS) of aged composite. Bar specimens were produced using a nanohybrid resin composite and aged in distilled water for 30 days. Different surface treatments (diamond bur, phosphoric acid, silane, and sandblasting with Al2O3 or CoJet Sand), as well as bonding protocols (Primer/Adhesive) were used prior to application of the repair composite. TBS of the specimens was measured and the results were analyzed using analysis of variance (ANOVA) and the Student-Newman-Keuls test (α = 0.05). Mechanically treated surfaces were characterized under SEM and by profilometry. The effect of water aging on the degree of conversion was measured by means of FTIR-ATR spectroscopy. An important increase in the degree of conversion was observed after aging. No significant differences in TBS were observed among the mechanical surface treatments, despite variations in surface roughness profiles. Phosphoric acid etching significantly improved repair bond strength values. The cohesive TBS of the material was only reached using resin bonding agents. Application of an intermediate bonding system plays a key role in achieving reliable repair bond strengths, whereas the kind of mechanical surface treatment appears to play a secondary role.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Aged resin composite; Bonding agent; Resin composite repair; Surface treatment; Tensile bond strength

Reply to Quinn GD, Salem JA, Swab JJ. Comment On: Lubauer J, Lohbauer U, Henrich M, Munz M, Lube T, Belli R. Intricacies involving the evaluation of fracture toughness obtained by the surface-crack-in-flexure method. J Am Ceram Soc. 2022;105(12):7582-7599. - Belli, Renan; Lubauer, Julia; Lohbauer, Ulrich; Henrich, Martina; Munz, Maximilian; Lube, Tanja (Journal of the American Ceramic Society, 2023)
CRIS-Team Scopus Importer:2023-06-30

Report on fractures of trilayered all-ceramic fixed dental prostheses - Belli, Renan; Scherrer, Susanne S.; Lohbauer, Ulrich (Case Studies in Engineering Failure Analysis, 2016)
Three cases of trilayered fixed dental prostheses fractured in vivo are fractographically analyzed to identify causes of failure. In all cases fractures initiated from a preexistent crack/defect in the zirconia framework produced previous to the fusion firing of a lithium disilicate veneering ceramic. In two cases zirconia framework pre-cracks were found to have been infiltrated with the intermediate fusion glass that diffused therein during sintering. This report highlights the susceptibility of zirconia to grinding damage and its role in limiting the lifetime of zirconia-based fixed dental prostheses.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Crowns; Dental bridges; Dental ceramic; Fractography; Fracture; Trilayers; Zirconia

Resistance-curve envelopes for dental lithium disilicate glass-ceramics - Lubauer, Julia; Ast, Johannes; Göken, Mathias; Merle, Benoit; Lohbauer, Ulrich; Belli, Renan (Journal of the European Ceramic Society, 2022)
Recent investigations on the mechanics of dental lithium disilicates have gathered mounting evidences of a probable R-curve behavior. Here we use an indirect approach to obtain the contours of the R-curve using the relationship between strength and initial crack size obtained from quasi-static fracture toughness tests. The tangent condition formed by the multiple K I,appl (ai,j) curves give a smoothened polygonal envelope for the R-curves. The R-curves obtained this way were extended toward an initial value at the onset of stable crack extension, obtained hereusing a microcantilever specimen featuring a sharp notch produced by focused-ion-beam milling. The presence of an R-curve effect was confirmed for the three evaluated lithium disilicates, being more pronounced for the injection-molded material having an oriented elongated Li2Si2O5 microstructural architecture, with crystal fraction playing an important role for low-aspect ratio randomly-oriented microstructures.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Dental ceramics; Focused ion beam milling; Fracture toughness; Lithium silicate; Micro-scale; R-curve

Rising R-curves in particulate/fiber-reinforced resin composite layered systems - Tiu, Janine; Belli, Renan; Lohbauer, Ulrich (Journal of the Mechanical Behavior of Biomedical Materials, 2020)
Background: An anisotropic fracture behavior has already been successfully induced in a condensable resin composite by reinforcement with discontinuous glass fibers, developing a steep rise in the fracture resistance curve. There is still the need for developing such concepts further, by evaluating the behavior of layered structures that attempt to replicate the natural gradient structure of enamel and dentin. Methods: Monolithic and bilayer specimens of a flowable short-fiber particulate-reinforced composite (SFPRC) material (GC Corp.) and a commercial flowable particulate-reinforced composite (PRC) (Essentia HiFlo, GC Corp.) were produced with the fibers aligned perpendicular or randomly oriented to the plane of crack propagation. Pre-cracked specimens were tested in 3-point bending using the single-edge-V-notch-beam method with accurate displacement tracking recordrecord. Controlled crack growth experiments were conducted at progressive crack extension intervals to build R-curves using linear-elastic and elastic-plastic fracture mechanics. Results: We demonstrate firsthand the development of R-curves in resin composite bilayers, with crack arrest at the interface and a steep rise in crack resistance with subsequent drop within the SFPRC layer. Crack deflection and fiber bridging were found to contribute to a higher rise in the R-curves for specimens with aligned fibers; still, randomly oriented fibers showed significant R-curve development, especially at short range intervals. An increase in the vol% of fibers and a decrease in the Young's modulus contributed to a higher overall performance of the flowable vs. the condensable SFPRF materials. Conclusions: SFPRC materials show an up to 5-fold improvement in the fracture resistance over conventional PRCs, and show the potential to be used to build gradient structures by varying the fiber alignment and fibers parameters (length and packing).
CRIS-Team Scopus Importer:2019-11-29
Keywords: Dental; Fracture toughness; Glass fiber; R-curve; Resin composite; Restorative materials

Self-adhesive resin cements: adhesive performance to indirect restorative ceramics - Zorzin, José Ignacio; Belli, Renan; Wagner, Anna; Petschelt, Anselm; Lohbauer, Ulrich (Journal of Adhesive Dentistry, 2014)
To evaluate the bonding performance of self-adhesive resin cements to zirconia and lithium disilicate in self- and dual-curing modes before and after thermocycling.Rectangular bars (3 mm high, 3 mm wide, 9 mm long) were manufactured from zirconia (Vita In-Ceram YZ for inLab, VITA) and lithium disilicate blocks (IPS e.max Press, Ivoclar Vivadent) (n=240 per material). Zirconia bars were sandblasted (35 ?m Al2O3, 1.5 bar pressure). Lithium disilicate bars were HF etched (20 s, IPS Ceramic Etching Gel, Ivoclar Vivadent) and silanized with ESPE Sil (3M ESPE). Forty bars of zirconia were luted in twos perpendicular to each other as were 40 bars of lithium disilicate using RelyX Unicem Automix 2 (3M ESPE), G-Cem LinkAce (GC Europe) or Maxcem Elite (Kerr) in self- or dual-curing mode. Half of the specimens from each material were submitted to tensile bond strength (TBS) testing after 24-h storage in distilled water at 37°C, and half underwent TBS testing after thermocycling (5000 cycles, 5°C/55°C, 30-s dwell time). Bond strength values for each bonding substrate were analyzed using one-way ANOVA (Student-Newman- Keuls, ?=0.05).On zirconia, dual-curing resulted in significantly (p<0.05) higher tensile bond strengths compared to self-curing, with the exception of RelyX Unicem 2 after thermocycling. Thermocycling significantly (p<0.05) reduced the tensile bond strength of Maxcem Elite to zirconia in both curing modes. The TBS of self-adhesive cements to lithium disilicate showed no significant (p>0.05) difference between the different curing modes and after thermocycling.For most of the investigated self-adhesive cements, bond strengths to zirconia were increased by dual curing; this was not true for lithium disilicate. For luting on zirconia with self-adhesive cements, dual curing is strongly recommended in clinical situations.
EVALuna2:24671

Self-adhesive resin cements: pH-neutralization, hydrophilicity, and hygroscopic expansion stress - Rödel, Lena; Bednarzig, Vera; Belli, Renan; Petschelt, Anselm; Lohbauer, Ulrich; Zorzin, José Ignacio (Clinical Oral Investigations, 2016)
The objective of the study was to investigate the relationship between pH-neutralization, hydrophilicity, and free hygroscopic expansion stress of self-adhesive resin cements (SARCs) after storage in artificial saliva.The SARCs RelyX Unicem Automix 2 (RX2, 3 M ESPE), iCEM (iCEM, Heraeus) and Maxcem Elite (MCE, Kerr) were under investigation in this study. Cylinders (height × diameter, 6 × 4mm) were prepared from each material and stored in artificial saliva (7d at 37 °C). Cylinder height was measured at baseline and after 7 days. After storage, the compression modulus was measured to calculate the free hygroscopic expansion stress. For pH-neutralization and hydrophilicity assessment, disks (height × diameter, 1 × 1.5 mm) were prepared, covered with electrolyte, and monitored over 24 h at 37 °C. Hydrophilicity was assessed using the static sessile drop technique at baseline and at different time intervals up to 24 h. Data were analyzed using one-way ANOVA and post hoc Student-Newman-Keuls test (S-N-K, ? = 0.05).After 24 h, RX2 (pH24h 4.68) had a significantly higher (p < 0.05) pH-value than MCE (pH24h 4.2) and iCEM (pH24h 3.23). iCEM showed the significantly highest hydrophilicity (p < 0.05) after 24 h (?24h 85.02°), while MCE resulted lower (?24h 113.01°) in comparison with RX2 (?24h 108.11°). The resulting hygroscopic expansion stress of iCEM (29.15 MPa) was significantly higher (p < 0.05) compared to RX2 (14.5 MPa) and MCE (21.02 MPa).The material with lowest pH-neutralization capacity displayed higher hydrophilicity after 24 h and higher hygroscopic expansion stress after 7 days compared to those with high pH-neutralization.Remnant hydrophilicity due to low pH-neutralization of SARCs could lead to cement interface stress build-up and long-term failure of silicate ceramic restorations.
EVALuna2:24695

Simulationsbasierte Generierung von Präparationsrichtlinien für Zahn-Inlays im kaubelasteten Seitenzahnbereich - Klein, Daniel; Grimme, Tobias; Tremmel, Stephan; Petschelt, Anselm; Lohbauer, Ulrich; Wartzack, Sandro (ANSYS Conference & CADFEM User's Meeting 2012, 2012)
Caries is the major dental disease and the main reason for tooth extractions as clinical investigations show. Fortunately in many cases the carious lesion can be removed without extracting the whole tooth and replaced by a restoration, e.g. inlays. However, the lifetime of inlays is limited. Besides the inlay material the geomtery of the inlay can have a significant impact on the durability of an inlay. The aim of this paper is to show how the impact of the inlay geometry on the durability can be observed with the help of simulation and some common guidelines for dental restaurations are monitored.
Keywords: Simulation; Medizintechnik

Sliding contact wear and subsurface damage of CAD/CAM materials against zirconia - Wendler, M.; Kaizer, M. R.; Belli, Renan; Lohbauer, Ulrich; Zhang, Y. (Dental Materials, 2020)
Objective: Most previous work conducted on the wear behavior of dental materials has focused on wear rates and surface damage. There is, however, scarce information regarding the subsurface damage arising from sliding contact fatigue. The aim of this study was to elucidate the wear mechanisms and the subsurface damage generated during sliding contact fatigue in 5 contemporary CAD/CAM materials against a zirconia indenter. Methods: Forty discs (Ø12 mm, 1.55 mm thick) were cut out of IPS e.max CAD (e.CAD), Suprinity PC (SUP), Enamic (ENA), Vitablocs Mark II (VMII) and Lava Ultimate (LU) blocks and mirror polished. After cementation onto a dentin-like composite, off-axis mouth-motion cycling was conducted with a spherical zirconia indenter (r = 3.18 mm) in water (200 N load, 2 Hz frequency) for 5 different cycling periods (102, 103, 104, 105, 106 cycles, n = 8). Analysis of the wear scars was conducted using light-microscopy, scanning-electron-microscopy and optical profilometry. Subsurface damage was assessed using sagittal and transverse sections of the samples. Results: Fatigue wear mechanisms predominated in glassy materials (e.CAD, SUP, VMII), accompanied by extensive subsurface damage, whereas abrasive wear mechanisms were responsible for the large wear craters in the resin composite (LU) with an absolute absence of subsurface fracture. A combination of both mechanisms was observed in the polymer-infiltrated reinforced-glass (ENA), displaying large wear craters and severe subsurface damage. Significance: Well-controlled laboratory simulation can identify wear and subsurface damage susceptibility of various classes of restorative materials. Both wear and subsurface fracture are determining factors for the long-term success of restorations.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Composites; Dental ceramics; Sliding contact; Wear mechanism; Wear rate

Slow progression of dentin bond degradation during one-year water storage under simulated pulpal pressure - Belli, Renan; Sartori, Neimar; Peruchi, Lais Dalmagro; Guimaraes, Jackeline Coutinho; Araujo, Elito; Monteiro, Sylvio; Baratieri, Luiz Narciso; Lohbauer, Ulrich (Journal of Dentistry, 2010)
Objectives: To evaluate the dentin bond durability of simplified adhesives after one-year (1 y) under water storage and simulated pulpal pressure. Methods: Class I cavities were prepared in sixty human third molars with the pulpal wall located in mid-coronal dentin. The roots were cut off to expose the pulpal chamber, and the teeth were assembled in a pulpal pressure simulator device. A two-step etch-and-rinse adhesive (Single Bond 2/SB), a two-step self-etch adhesive (Clearfil SE Bond/CSE), a three-step self-etch adhesive (Adper Scotchbond SE/SSE) and three all-in-one adhesives (Adper Easy Bond/EB, Clearfil S3 Bond/S3 and Adhese One/AO) were applied according to manufacturers instructions. No enamel pre-etching was used for the self-etch systems. The cavities were filled with a composite (Z250, 3M ESPE) in four to five horizontal increments and individually cured. Immediately after the final cure, pulpal pressure was set to 15 cm H2O. After 24 h and 1 y under simulate pulpal pressure the teeth were cut following a 'nontrimming' microtensile test technique (n = 30) and tested in tension. Kruskall-Wallis and post hoc multiple comparisons were used at α = 0.05. Weibull statistics was applied to SB, CSE and EB. Fractographic analysis of debonded specimens was performed using scanning electron microscopy. Results: At 24 h and 1 y periods, SB showed higher bond strength means than all the others adhesives tested. CSE was not statistically different from EB at 24 h and from EB and SB at 1 y. EB showed bond strength statistically higher than the other three self-etch adhesives, which were not statistically different from each other at 24 h. AO showed significantly lower bond strength than all tested materials after 1 y. For all adhesives the mean bond strength at 1 y were not statistically different from the values measured at 24 h (p > 0.05). Shifts in failure mode patterns and Weibull modulus decrease indicate some degree of bond degradation after the 1 y storage period. Conclusion: One-year of simulated pulpal pressure did not affect dentin bond strength of simplified adhesives in Class I restorations. Signs of degradation were only revealed by fractographic analysis and reliability parameters. © 2010 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Adhesive; Bond; Degradation; Dentin; Durability; One-step; Pulpal pressure; Self-etch; Simulated

Spatial distribution of residual stresses in glass-ZrO2 sphero-cylindrical bilayers - Wendler, Michael; Belli, Renan; Petschelt, Anselm; Lohbauer, Ulrich (Journal of the Mechanical Behavior of Biomedical Materials, 2016)
Residual stresses arising from inhomogeneous cooling after sintering have shown to play a preponderant role in the higher incidence of chippings observed for glass-zirconia dental prostheses. Still, current descriptions of their nature and distribution have failed to reconcile with clinical findings. Therefore, an axisymmetric sphero-cylindrical bilayer model was used in this study to determine the effect of the cooling rate on the final spatial distribution of residual stresses. Zirconia frameworks with two different radii (1.6 and 3.2mm) were CAD/CAM fabricated. Subsequent glass overlays with two different thickness ratios (1:1 and 2:1) were generated and heat pressed onto the zirconia substrates. The obtained structures were submitted to a last firing process and fast- (45°C/s) or slow-cooled (0.5°C/s) to room temperature. Unbonded bilayers were produced by firing glass overlays onto boron nitride coated zirconia. Thin sagittal and transversal sections were obtained from the specimens to assess residual stress distribution by means of light birefringence. The applied cooling rates did not affect distribution or magnitude of radial residual stresses (sagittal sections), whereas increased hoop stress magnitudes were measured (transversal sections) in fast-cooled specimens. A distinct stress nature was observed for the hoop stress component of unbonded overlays after fast cooling. Interaction between stress components seems to govern the final stress distribution, highlighting the importance of a multiaxial assessment of this problem in three-dimensional structures.
EVALuna2:24683

Speed-sintering and the mechanical properties of 3–5 mol% Y2O3-stabilized zirconias - Lubauer, Julia; Schuenemann, Fernanda Haverroth; Belli, Renan; Lohbauer, Ulrich (Odontology, 2023)
Ever faster workflows for the fabrication of all-ceramic restorations are of high economic interest. For that purpose, sintering protocols have been optimized for use in modern sintering furnaces, the so-called speed-sintering. However, conventional furnaces are still the most widely used equipment to sinter zirconia restorations. In this in-vitro study, we evaluated the feasibility of a speed-sintering protocol using a conventional sintering furnace to sinter different dental zirconias (stabilized with 3 mol% up to 5.4 mol% Y2O3) in comparison to a conventional sintering program. The properties evaluated were Young’s modulus, Poisson’s ratio, density, biaxial flexural strength, and fracture toughness. We show here that despite differences being dependent on material, the physical and mechanical properties of speed-sintered zirconia are comparable to those obtained by the conventional sintering.
CRIS-Team Scopus Importer:2023-03-10
Keywords: Flexural strength; Mechanical tests; Yttria-stabilized tetragonal zirconia

Strength and wear resistance of a dental glass-ionomer cement with a novel nanofilled resin coating - Lohbauer, Ulrich; Krämer, Norbert; Siedschlag, Gustavo; Schubert, Edward W.; Lauerer, Brigitte; Müller, Frank A.; Petschelt, Anselm; Ebert, Johannes (American Journal of Dentistry, 2011)
To evaluate the influence of different resin coating protocols on the fracture strength and wear resistance of a commercial glass-ionomer cement (GIC). Methods: A new restorative concept [Equia (GC Europe)] has been introduced as a system application consisting of a condensable GIC (Fuji LX GP Extra) and a novel nanofilled resin coating material (G-Coat Plus). Four-point fracture strength (FS, 2 × 2 × 25 mm, 14-day storage, distilled water, 37°C) were produced and measured from three experimental protocols: no coating GIC (Group 1), GIC coating before water contamination (Group 2), GIC coating after water contamination (Group 3). The strength data were analyzed using Weibull statistics. Three-body wear resistance (Group 1 vs. Group 2) was measured after each 10,000 wear cycles up to a total of 200,000 cycles using the ACTA method. GIC microstructure and interfaces between GIC and coating materials were investigated under SEM and CLSM. Results: The highest FS of 26.1 MPa and the most homogenous behavior (m = 7.7) has been observed in Group 2. The coated and uncoated GIC showed similar wear resistance until 90,000 cycles. After 200,000 wear cycles, the coated version showed significantly higher wear rate (ANOVA, P< 0.05). The coating protocol has been shown to determine the GIC fracture strength. Coating after water contamination and air drying is leading to surface crack formation thus significantly reducing the FS. The resin coating showed a proper sealing of GIC surface porosities and cracks. In terms of wear, the coating did not improve the wear resistance of the underlying cement as similar or higher wear rates have been measured for Group 1 versus Group 2.
CRIS-Team Scopus Importer:2023-01-23

Strengthening of dental adhesives via particle reinforcement - Belli, Renan; Kreppel, Stefan; Petschelt, Anselm; Hornberger, Helga; Boccaccini, Aldo R.; Lohbauer, Ulrich (Journal of the Mechanical Behavior of Biomedical Materials, 2014)
The bond between methacrylic polymer adhesives and dental restoratives is not perfect and may fail either in the short or in the long term. This study aims to evaluate the effects of particle incorporation in a self-etch model adhesive on mechanical and physical properties that are relevant during application and service. Filled adhesives containing 5, 10, 15 or 25. wt% glass fillers were compared to their unfilled counterpart in terms of water sorption and solubility; viscosity and dynamic viscosity during polymerization were recorded using rheological measurements and compared to FTIR analysis of the real-time degree of cure. Elastic modulus and ultimate tensile strength measurements were performed in uniaxial tension; the energy to fracture was used to calculate the fracture toughness of the adhesives. Finally, the experimental adhesives were applied on dentin substrate to test the bond strength using the microtensile test. Results showed that the incorporation of 5-10. wt% nanofiller to self-etching dental adhesives is efficient in accelerating the polymerization reaction and increasing the degree of cure without compromising the film viscosity for good wettability or water sorption and solubility. Fillers increased the elastic modulus, tensile strength and fracture toughness to a plateau between 5 and 15. wt% filler concentration, and despite the tendency to form agglomerations, active crack pinning/deflection toughening mechanisms have been observed. The bond strength between resin composite and dentin was also improved when adhesives with up to 10. wt% fillers were used, with no additional improvements with further packing. The use of fillers to reinforce dental adhesives may therefore be of great practical benefit by improving curing and mechanical properties. © 2014 Elsevier Ltd.
Keywords: Adhesives; Bond strength; Dentin; Elasticity; Nanoparticles

Subcritical crack growth and in vitro lifetime prediction of resin composites with different filler distributions - Ornaghi, Barbara P.; Meier, Marcia M.; Rosa, Vinicius; Cesar, Paulo F.; Lohbauer, Ulrich; Braga, Roberto R. (Dental Materials, 2012)
Objectives: Verify the influence of different filler distributions on the subcritical crack growth (SCG) susceptibility, Weibull parameters (m and σ 0) and longevity estimated by the strength-probability-time (SPT) diagram of experimental resin composites. Methods: Four composites were prepared, each one containing 59 vol% of glass powder with different filler sizes (d 50 = 0.5; 0.9; 1.2 and 1.9 μm) and distributions. Granulometric analyses of glass powders were done by a laser diffraction particle size analyzer (Sald-7001, Shimadzu, USA). SCG parameters (n and σ f0) were determined by dynamic fatigue (10 -2 to 10 2 MPa/s) using a biaxial flexural device (12 × 1.2 mm; n = 10). Twenty extra specimens of each composite were tested at 10 0 MPa/s to determine m and σ 0. Specimens were stored in water at 37 °C for 24 h. Fracture surfaces were analyzed under SEM. Results: In general, the composites with broader filler distribution (C0.5 and C1.9) presented better results in terms of SCG susceptibility and longevity. C0.5 and C1.9 presented higher n values (respectively, 31.2 ± 6.2 a and 34.7 ± 7.4 a). C1.2 (166.42 ± 0.01 a) showed the highest and C0.5 (158.40 ± 0.02 d) the lowest σ f0 value (in MPa). Weibull parameters did not vary significantly (m: 6.6 to 10.6 and σ 0:170.6 to 176.4 MPa). Predicted reductions in failure stress (P f = 5%) for a lifetime of 10 years were approximately 45% for C0.5 and C1.9 and 65% for C0.9 and C1.2. Crack propagation occurred through the polymeric matrix around the fillers and all the fracture surfaces showed brittle fracture features. Significance: Composites with broader granulometric distribution showed higher resistance to SCG and, consequently, higher longevity in vitro. © 2012 Academy of Dental Materials.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Dynamic fatigue; Fractography; Resin composites; Strength-probability-time diagram; Subcritical crack growth; Weibull analysis

Subcritical crack growth behavior and life data analysis of two types of dental Y-TZP ceramics - Mitov, Gergo; Gessner, Janina; Lohbauer, Ulrich; Woll, Karsten; Muecklich, Frank; Pospiech, Peter (Dental Materials, 2011)
Objectives: The aim of this study was to evaluate the mechanical properties and the subcritical crack growth behavior of a presintered dental Y-TZP (Kavo Everest ZS) and a hot isostatic pressed Y-TZP (Kavo Everest ZH) and to perform life data analysis. Methods: For each material 150 bending bars were produced. The initial fracture strength was determined in a four-point bending test. The subcritical crack growth parameters n and A were determined in a dynamic fatigue method at four decreasing loading rates from 110 MPa/s to 0.11 MPa/s in distilled water at 38 °C. For each loading rate Weibull statistics were performed and the Weibull moduli m and characteristic strengths σ0 were calculated. Using these data, strength-fracture probability-life time (SPT) predictions were derived for 1 day, 1 year, 5 years and 10 years, based on a static crack growth mechanism. Results: The "hipped" Y-TZP ceramic exhibited a higher initial strength (σc = 1618.18), characteristic strength (σ0 = 837.15) and fracture toughness (KIC = 4.52 MPa/m1/2) than the pre-sintered ceramic (σc = 1431, σ0 = 745.46 and KIC = 3.17 MPa/m1/2, respectively). Fatigue parameters, n and A, were 28.5 and 7.97 × 10-24 for Everest ZH and 30.15 and 5.47 × 10-20 for Everest ZS. The predicted fracture stress at 5% failure probability for a lifetime of 10 years was 259.34 MPa for Everest ZH and 263.2 MPa for Everest ZS. Conclusions: Although the "hipped" Y-TZP showed favorable initial mechanical properties, no significant difference could be found in the susceptibility of both ceramics to subcritical crack growth and their long-term strength. © 2011 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Dynamic fatigue; Lifetime analysis; SPT diagram; Subcritical crack growth; Zirconia ceramic

Surface characteristics of zirconia-based posterior restorations: Clinical and scanning electron microscopic analysis - Schmitt, Johannes; Wichmann, Manfred; Karl, Matthias; Gölner, Matthias; Lohbauer, Ulrich; Holst, Stefan (Journal (Canadian Dental Association), 2011)
Aim: The aim of this prospective clinical trial was to evaluate the performance of zirconiabased all-ceramic posterior fi xed partial dentures (FPDs) after 4 years of clinical use. Materials and Methods: Fifteen patients who needed 3- or 4-unit posterior FPDs were enrolled in the study. One manufacturer fabricated all restorations, following established clinical protocols and using computer-aided design/computer-aided manufacturing technology and one veneering material. Survival and success were evaluated clinically. Impressions were taken immediately after defi nitive cementation and after 48 months. Gold-coated epoxy replicas of the restorations were analyzed with scanning electron microscopy (SEM). Surface alterations were also evaluated clinically. Results: After 48 months, the survival rate for the FPDs was 100%. Three restorations exhibited minor chipping, for a fracture rate of 20% after 4 years. Thirty (59%) of the 51 individual restoration units revealed clinically rough occlusal surfaces, a fi nding that was confi rmed by SEM. Conclusion: The placement of 3- and 4-unit zirconia-based posterior FPDs can be considered a reliable treatment modality for medium-term clinical use. However, surface alterations of the veneering ceramics were observed after 4 years and are of notable clinical concern.
CRIS-Team Scopus Importer:2023-01-23

Tailoring of physical properties in highly filled experimental nanohybrid resin composites - Pick, Barbara; Pelka, Matthias; Belli, Renan; Braga, Roberto R.; Lohbauer, Ulrich (Dental Materials, 2011)
Objectives: To assess the elastic modulus (EM), volumetric shrinkage (VS), and polymerization shrinkage stress (PSS) of experimental highly filled nanohybrid composites as a function of matrix composition, filler distribution, and density. Methods: One regular viscosity nanohybrid composite (Grandio, VOCO, Germany) and one flowable nanohybrid composite (Grandio Flow, VOCO) were tested as references along with six highly filled experimental nanohybrid composites (four Bis-GMA-based, one UDMA-based, and one Ormocer®-based). The experimental composites varied in filler size and density. EM values were obtained from the "three-point bending" load-displacement curve. VS was calculated with Archimedes' buoyancy principle. PSS was determined in 1-mm thick specimens placed between two (poly)methyl methacrylate rods (Ø = 6 mm) attached to an universal testing machine. Data were analyzed using oneway ANOVA, Tukey's test (α = 0.05), and linear regression analyses. Results: The flowable composite exhibited the highest VS and PSS but lowest EM. The PSS was significantly lower with Ormocer. The EM was significantly higher among experimental composites with highest filler levels. No significant differences were found between all other experimental composites regarding VS and PSS. Filler density and size did not influence EM, VS, or PSS. Significance: Neither the filler configuration nor matrix composition in the investigated materials significantly influenced composite shrinkage and mechanical properties. The highest filled experimental composite seemed to increase EM by keeping VS and PSS low; however, matrix composition seemed to be the determinant factor for shrinkage and stress development. The Ormocer, with reduced PSS, deserves further investigation. Filler size and density did not influence the tested parameters. © 2011 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Elastic modulus; Nanoparticles; Polymerization shrinkage; Resin composite; Shrinkage stress

Temperature changes affect the rheological properties of a silicone-based and an epoxy resin-based root canal sealers - de Freitas, Jéssica Vavavassori; Ebert, Johannes; Mazzi-Chaves, Jardel Francisco; Tomazinho, Flávia Sens Fagundes; Sousa-Neto, Manoel Damião de; Lohbauer, Ulrich; Baratto-Filho, Flares (Australian Endodontic Journal, 2020)
To evaluate temperature changes on the rheological properties (setting time and complex viscosity (η*)) of GuttaFlow Bioseal (GFB) and AH Plus Jet (AHPJ). Rheological measurements were performed in oscillating mode at the strain amplitude and angular frequency of 0.01% and 10 rad s−1, respectively. Each sealer (n = 5) was tested running a temperature ramp (rapid increase to 80°C, 1 min constantly at 80°C, and slower decrease to 37°C). Control groups (n = 5) were tested at a constant temperature of 37°C. Kolmogorov–Smirnov and one-way ANOVA (P < 0.05) statistical tests were performed. The temperature ramp reduced setting time of GFB (24.85 to 4.45 min) (P < 0.05), but did not alter that of AHPJ (P > 0.05). GFB exhibited an increased η*, whereas the AHPJ η* was decreased when heated (P < 0.05). Rheological properties of sealers were negatively affected by temperature changes.
CRIS-Team Scopus Importer:2020-08-07
Keywords: dimethylpolysiloxanes; epoxy resin-based root canal sealer; rheology; root canal obturation; temperature

Tensile and bending fatigue of the adhesive interface to dentin - Belli, Renan; Baratieri, Luiz Narciso; Braem, Marc; Petschelt, Anselm; Lohbauer, Ulrich (Dental Materials, 2010)
Objectives: The aim of this study was to evaluate the fatigue limits of the dentin-composite interfaces established either with an etch-and-rinse or an one-step self-etch adhesive systems under tensile and bending configurations. Methods: Flat specimens (1.2 mm × 5 mm × 35 mm) were prepared using a plexiglass mold where dentin sections from human third molars were bonded to a resin composite, exhibiting the interface centrally located. Syntac Classic and G-Bond were used as adhesives and applied according to the manufacturer's instructions. The fluorochrome Rhodamine B was added to the adhesives to allow for fractographic evaluation. Tensile strength was measured in an universal testing machine and the bending strength (n = 15) in a Flex machine (Flex, University of Antwerp, Belgium), respectively. Tensile (TFL) and bending fatigue limits (BFL) (n = 25) were determined under wet conditions for 104 cycles following a staircase approach. Interface morphology and fracture mechanisms were observed using light, confocal laser scanning and scanning electron microscopy. Statistical analysis was performed using three-way ANOVA (mod LSD test, p < 0.05). Results: Tensile and bending characteristic strengths at 63.2% failure probability for Syntac were 23.8 MPa and 71.5 MPa, and 24.7 MPa and 72.3 MPa for G-Bond, respectively. Regarding the applied methods, no significant differences were detected between adhesives. However, fatigue limits for G-Bond (TFL = 5.9 MPa; BFL = 36.2 MPa) were significantly reduced when compared to Syntac (TFL = 12.6 MPa; BFL = 49.7 MPa). Fracture modes of Syntac were generally of adhesive nature, between the adhesive resin and dentin, while G-Bond showed fracture planes involving the adhesive-dentin interface and the adhesive resin. Significance: Cyclic loading under tensile and bending configurations led to a significant strength degradation, with a more pronounced fatigue limit decrease for G-Bond. The greater decrease in fracture strength was observed in the tensile configuration. © 2010 Academy of Dental Materials.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Adhesive interface; CLSM; Cyclic fatigue; Dentin bonding; Flexural strength; Fracture; Tensile strength

The breakdown of the Weibull behavior in dental zirconias - Belli, Renan; Lohbauer, Ulrich (Journal of the American Ceramic Society, 2021)
Here we attend to the controversy of the use of Weibull statistics for describing the strength distribution of dental brittle materials. Our approach is purely experimental by means of testing for the strength size effect, a requirement for Weibull materials. Zirconia materials of five important dental manufacturers were selected, each represented by two compositions, being one a 3 mol% Y2O3-stabilized zirconia, and the other being a "translucent" zirconia with 4 or 5 mol% stabilizer content. Specimens of increasing sizes were fractured, whether by using a biaxial flexure test in plates or a uniaxial bending test in beams, thereby sampling different ranges of effective surfaces and volumes. A systematic deviation from the Weibull behavior over the range of 1-40 mm(2) effective surface was demonstrated, regardless of manufacturer and Y2O3 content in the powder. Extensive testing using a wider range of specimen sizes narrowed down the threshold for the breakdown of the defect size distribution from the parent population to be located between 10 and 20 mm(2) effective surface. A comparable behavior was confirmed for the partly sintered white-bodies, with similar defect morphology to the fully sintered analogs, indicating a defect size distribution stemming from the pressing steps of manufacture. The defect shape related to open particle aggregate junctions, pointing to an association of their size distribution to that of the distribution of aggregate sizes in the source powders.
CRIS-Team WoS Importer:2021-06-11

The effect of air-polishing abrasives on wear of direct restoration materials and sealants - Pelka, Matthias; Altmaier, Katharina; Petschelt, Anselm; Lohbauer, Ulrich (Journal of the American Dental Association, 2010)
Background. Air-polishing devices (APDs) effectively remove supragingival staining. However, the use of APDs on restorative surfaces may result in clinically relevant surface damage and material loss. Methods. The authors made plane specimens (N = 180) of dental restorative materials (Tetric EvoCeram [Ivoclar Vivadent, Schaan, Liechtenstein], Tetric Flow [Ivoclar Vivadent ], Grandio Flow [VOCO, Cuxhaven, Germany], Admira Seal (VOCO], Grandio Seal [VOCO]) and Ionofil Molar [VOCO]). The authors treated the specimens with standardized air abrasion, using three abrasives (Acclean Air Preventive Powder [Henry Schein, Langen, Germany], AirFlow Prophylaxis Powder [EMS, Nyon, Switzerland] and ClinPro Prophy Powder [3M ESPE, Seefeld, Germany]) for 10 seconds each. The authors used profilometric scanning to quantify defect depth and volume loss. Results. The abrasive ClinPro Prophy Powder produced the smallest defect depth and volume loss. Tetric EvoCeram experienced the smallest defect depth, whereas the flowable composites showed the greatest defect depths and volume losses. Sealants showed defects comparable with those the authors found in the glass ionomer, which were significantly smaller than those found in flowable composites. Conclusions. Air polishing of sealants and restorative materials always results in substance loss and surface damage. The sealants performed better in terms of abrasion resistance than did the flowable composites tested. Among the air-polishing abrasives, ClinPro Prophy Powder caused the least abrasive damage. Clinical Implications. Clinicians should use low-abrasion powder for frequent cleaning of discolored restorations with APDs to avoid excessive abrasion of restorative materials.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Air abrasion; Dental prophylaxis; Dental restoration wear; Dental sealants; Restorative material

The effect of resin composite pre-heating on monomer conversion and polymerization shrinkage - Lohbauer, Ulrich; Zinelis, Spiros; Rahiotis, Christos; Petschelt, Anselm; Eliades, George (Dental Materials, 2009)
Objectives: To determine monomer conversion and polymerization shrinkage of a resin composite after different pre-heating procedures and storage intervals. Methods: For a commercial resin-based composite the immediate (5 min) and final (24 h) degree of conversion was measured on top and bottom surfaces utilizing FTIR spectroscopy. Composite pre-heating temperatures were selected between 10 and 68 °C. Polymerization shrinkage was measured according to Archimedes' principles of buoyancy after 5 min at respective pre-heating temperatures and after 24 h dark and wet storage at 37 °C. Intra-cavity temperature development was monitored using a K-type thermocouple. Results: No significant increase in immediate as well as in final degree of conversion were measured from composite pre-heating at 68 °C compared to 54 and 39 °C. Linear correlations were detected immediately after photo-polymerization and on the top surface after 24 h storage. Polymerization shrinkage as a function of pre-heating temperatures exhibited a linear correlation after 5 min, but no statistically different behavior after 24 h. Significance: Pre-heating of resin composites does not increase degree of conversion over time. It can be clinically beneficial, due to a superior marginal adaptation. This advantageous effect of reduced material paste viscosity has to be clinically addressed, since temperature rapidly drops to the physiological level upon removal from the pre-heating device. © 2008 Academy of Dental Materials.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Curing temperature; Monomer conversion; Polymerization shrinkage; Pre-heating; Resin composite

The effect of six years of water storage on resin composite bonding to human dentin - Frankenberger, R.; Strobel, W. O.; Lohbauer, Ulrich; Krämer, N.; Petschelt, Anselm (Journal of Esthetic and Restorative Dentistry, 2009)
Objective: The purpose of this study was to evaluate the effects of water storage for up to 6 years on the push-out bond strength and marginal adaptation of dentin adhesives. Materials and Methods: Disks of 2-mm thickness were cut from the mid-coronal level of 360 extracted human third molars. A 2.3-diameter cylindrical cavity was prepared in the center of each disk. The dentin disks were embedded in an extrusion device using a temporary restorative material. They were assigned to eight groups of 45 for treatment with various adhesives. The adhesives used in the study were Syntac Classic (Ivoclar Vivadent, Schaan, Liechtenstein) with and without phosphoric acid etching, A.R.T. Bond (Coltène, Alstätten, Switzerland) with and without etching, Scotchbond Multi-Purpose (3M ESPE, St. Paul, MN, USA), EBS (3M ESPE, Seefeld, Germany), Prime & Bond 2.0 (Dentsply DeTrey, Konstanz, Germany), and Syntac Single-Component (Ivoclar Vivadent). Prime & Bond and Syntac Single-Component are both two-step etch-and-rinse systems that deliver primer and bonding agent simultaneously. The others include separate primer and bonding agent steps. After adhesive application, the cavities were restored with composite. The specimens were polished to 600 grit and stored in distilled water at 37C for 1 day, 90 days, or 6 years. After storage,the specimens were thermocycled and then subjected to push-out testing. Using a universal testing machine, this was accomplished by applying a rod to the composite until failure. Failure was defined as the loss of 30% of the maximum push-out force. Push-out bond strength was determined by calc ulating the quotient of maximum load and adhesion area. Impressions of the 6-year specimens were made after 1 and 90 days, and 1, 2, 3, 4, 5, and 6 years. Epoxy replicas were made and sputter-coated with gold. The restoration margins were analyzed using scanning electron microscopy at 200¥ magnification). A quantitative analysis of gap-free margins versus margins with gaps or irregularities was made using an image analysis system. Margin quality was expressed as the percentage of gap-free margins relative to the entire marginal length. Results: At 1 day, mean bond strengths ranged from 26.3 MPa for Prime & Bond 2.0 to 33.8 MPa for A.R.T. with etching. After 90 days of water storage, the mean bond strength of all adhesives remained constant. However, at 6 years, the bond strength of every adhesive had declined significantly. The loss of bond strength was more pronounced for the onebottle systems than for the three-step systems. In general, the marginal quality of the three-step systems was better than that of the two-step systems. Margins began to deteriorate more rapidly with the simpler systems and stabilized at approximately 50% continuous, gap-free margins. For the more complex systems, the gap-free margin percentage was approximately 80%.Conclusions: Etch-and-rinse multistep adhesives provide higher bond strengths and better marginal adaptation than two-step systems over 6 years of storage in water. © 2009, Wiley Periodials, inc..
CRIS-Team Scopus Importer:2023-01-23

The influence of particle size on the mechanical properties of dental glass ionomer cements - Brandt, Bjoern; Lohbauer, Ulrich; Göken, Mathias; Durst, Karsten (Advanced Engineering Materials, 2010)
WW1::860

The mechanical behavior of the material-tissue and material-material interface in dental reconstructions - Ferracane, J. L.; Lohbauer, Ulrich; Palin, W. M. (International Journal of Adhesion and Adhesives, 2016)
In dental and craniofacial sciences, frequently the goal is to replace lost or damaged natural tissue with synthetic materials. For ideal function, these replacement materials must strongly bond to the existing tissue, but they also must form a hermetic seal that eliminates the passage of microorganisms and fluids that would lead to further tissue destruction or weakening of the interface or the individual materials, compromising the final outcome. Therefore, the study of interfaces is crucial, and the manner in which they can be tested to predict the likelihood of success is of great interest to the field. Because a variety of materials and material combinations are used for the repair or replacement of oral and craniofacial tissues, numerous types of material interfaces exist. A complete discussion of this important topic requires an examination of all of them. In this review article, the three different types of interfaces are treated separately. First, the interface between the tooth tissue and restorative material is explored, specifically by considering resin-based materials such as dental adhesives and composite, and the manner in which they interact with dentin and enamel. Second, the interaction between these same resin-based materials and other structures, such as oxide ceramic dental crowns, are explored, because these tooth replacement materials are typically fixed to the remaining tooth structure through the use of resin-based adhesives and cements, or repaired intraorally with similar materials. Finally, the interface between different synthetic materials, such as metals and ceramics, with dental porcelain used as an esthetic veneering material is addressed.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Bond strength test; Dental adhesion; Dental ceramics; Interface; Resin cement; Veneering ceramics; Zirconia

The Mechanical Performance of a Novel Self-Adhesive Restorative Material - Lohbauer, Ulrich; Belli, Renan (Journal of Adhesive Dentistry, 2020)
Purpose: The development of a novel material requires a comprehensive pre-clinical assessment of clinical longevity before any market release. This study aimed to investigate the mechanical performance of a novel self-adhesive restorative material (ASAR MP4).
CRIS-Team WoS Importer:2020-03-06

The potential of novel primers and universal adhesives to bond to zirconia - Amaral, Marina; Belli, Renan; Cesar, Paulo Francisco; Valandro, Luiz Felipe; Petschelt, Anselm; Lohbauer, Ulrich (Journal of Dentistry, 2014)
To investigate the adhesive potential of novel zirconia primers and universal adhesives to surface-treated zirconia substrates.Zirconia bars were manufactured (3.0mm×3.0mm×9.0mm) and treated as follows: no treatment (C); air abrasion with 35?m alumina particles (S); air abrasion with 30?m silica particles using one of two systems (Rocatec or SilJet) and; glazing (G). Groups C and S were subsequentially treated with one of the following primers or adhesives: ZP (Z-Prime Plus), AZ (AZ Primer); MP (Monobond Plus); SU (ScotchBond Universal) and; EA (an Experimental Adhesive). Groups Rocatec and SilJet were silanized prior to cementation. Samples form group G were further etched and silanized. Bars were cemented (Multilink) onto bars of a silicate-based ceramic (3.0mm×3.0mm×9.0mm) at 90° angle, thermocycled (2.500 cycles, 5-55°C, 30s dwell time), and tested in tensile strength test. Failure analysis was performed on fractured specimens to measure the bonding area and crack origin.Specimens from group C did not survive thermocycling, while CMP, CSU and CEA groups survived thermocycling but rendered low values of bond strength. All primers presented a better bond performance after air abrasion with Al2O3 particles. SilJet was similar to Rocatec, both presenting the best bond strength results, along with SMP, SSU and CEA. G promoted intermediate bond strength values. Failure mode was predominately adhesive on zirconia surface combined to cohesive of the luting agent.Universal adhesives (MP, SU, EA) may be a considerable alternative for bonding to zirconia, but air abrasion is still previously required. Air abrasion with silica particles followed by silane application also presented high bond strength values.
EVALuna2:24656

Thermal-induced residual stresses affect the fractographic patterns of zirconia-veneer dental prostheses - Belli, Renan; Petschelt, Anselm; Lohbauer, Ulrich (Journal of the Mechanical Behavior of Biomedical Materials, 2013)
Veneer fractures in dental zirconia-veneer prostheses are more frequent clinically than in conventional metal-ceramic systems. This is thought to be due to the increased residual stresses generated within the veneer during fabrication when zirconia is the infrastructure material. This investigation aimed to analyze the fractographic features of fractured zirconia-veneer dental crowns submitted to a load-to-failure test and to a more clinically relevant in vitro chewing simulation fatigue test. As-sintered and sandblasted zirconia copings were veneered with glass-ceramic with different coefficients of thermal expansion and cooled following two cooling rates, creating, this way, different levels of stresses within the veneer. Crowns with different thermal mismatch combinations and different cooling rates were hypothesized to present particular fracture patterns. A careful examination of >1000 scanning electron microscopy images of the fracture surfaces was conducted in search of characteristic fractographic markings of fracture mechanisms connected to the stress state of the veneer. Distinctive structural features could be observed between groups veneered with the two different glass-ceramics and between fractured crowns under static and cyclic loading. The presence/absence of residual stresses zones within the veneer have shown to play the major role in the fracture pattern of zirconia-veneer dental prostheses. For the fatigue crowns, the zirconia core was never exposed, either for sandblasted and as-sintered groups. © 2013 Elsevier Ltd.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Cooling rate; Fractography; Thermal mismatch; Thermal stress; Veneer; Zirconia

Thermal-induced residual stresses affect the lifetime of zirconia-veneer crowns - Belli, Renan; Frankenberger, Roland; Appelt, Andreas; Schmitt, Johannes; Baratieri, Luiz N.; Greil, Peter; Lohbauer, Ulrich (Dental Materials, 2013)
Objectives: The purposes of this study were to investigate the effects of thermal residual stresses on the reliability and lifetime of zirconia-veneer crowns. Methods: One hundred and twenty eight second upper premolar zirconia-veneer crowns were manufactured for testing the initial strength (n = 64) and under cyclic fatigue (n = 64). Zirconia copings (YZ Cubes, VITA Zahnfabrik, CTE: alphac = 10.5 ppm/°C) were milled using a Cerec3 InLab (Sirona) machine and sintered to a final thickness of 0.7 mm. Sixty-four copings were sandblasted with 105 μm alumina particles (15 s, 3 cm distance, 45° angle, 0.4 MPa pressure) in order to trigger a tetragonalmonoclinic transformation and to produce a rough surface. The copings were veneered using two different porcelains (VM9, VITA Zahnfabrik, CTE: alphaVM9 = 9.1 ppm/°C, Lava Ceram, 3M ESPE, CTE: alphaLava = 10.2 ppm/°C) so to result in crowns with either high thermal mismatch (+1.4 ppm/°C with VM9) and low thermal mismatch (+0.3 ppm/°C with Lava Ceram). The porcelains were applied by the same operator and fired (VITA Vacumat 4000) according to the firing schedules defined by the manufacturers to a final thickness of 1.4 mm (total crown thickness = 2.1 mm, core/veneer ratio = 0.5). After the last glaze firing the crowns were cooled following a fast (600 °C/min) or a slow (30 °C/min) cooling protocol. The glazed crowns were submitted to a sliding-motion (0.7 mm lateral movement) cyclic fatigue in a chewing simulator (SD Mechatronik) under 20 kg (∼200 N load) weight until failure (chipping) (n = 16). The other half of the crowns were subjected to a compressive loading test in an universal testing machine (Instron model 4240) until failure at a cross-head speed of 0.75 mm/min (n = 16). The failure probability for initial strength and cyclic fatigue was performed using a Weibull distribution approach at a scale factor of n = 16. Results: The compressive strength test showed a low sensitivity to detect reliability variations regarding thermal stresses created within the veneer layer of tested crowns. For cyclic fatigue, slow cooling resulted in statistically higher cycles to failure only for the crowns that presented a high thermal mismatch between core and veneer (VM9 group). Comparisons between veneers with high or low thermal mismatches showed statistically higher sigma0 for Lava Ceram-veneered crowns only when the groups were fast-cooled. Significance: Minimizing the thermal residual stresses within the veneer through the use of a veneer with a closer CTE to the zirconia delays the failure of zirconia-veneer crowns. Slow-cooling increases the lifetime of crowns presenting large differences in CTE between the zirconia core and the veneering porcelain. © 2012 Academy of Dental Materials.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Compression test; Cooling rate; Fatigue; Reliability; Thermal mismatch; Thermal stress; Veneer; Zirconia

Thickness influence of veneering composites on fiber-reinforced systems. - Tiu, Janine; Belli, Renan; Lohbauer, Ulrich (Dental Materials, 2021)
OBJECTIVE: Short fiber reinforced composites (SFRC) require a veneering layer of conventional composite when used as restorations in the oral environment. The current study investigates the toughening effects during the path of a preexisting crack propagating through the bilayer system as it confronts the interface, through the attempted alignment of fibers and matrix-fiber interactions in the SFRC, and the distance it travels in the SFRC. METHODS: Bilayer systems of SFRC and conventional composite were produced with aligned fibers perpendicular to load direction. Single-edge-notched bend (SENB) specimens (25 × 5 × 2.5 mm3) with pre-crack length (a) to width (W) ratios (a/W = 0.2-0.8) were produced and tested in 3-point bending configuration until complete fracture. The specific work of fracture (we) was deduced from calculating the area under the load-displacement curves. Fiber alignment was digitally evaluated from images taken from the top and side planes of the specimen. RESULTS: The toughness of the bilayer system is optimal when maximum SFRC thickness is used. EWF methods showed toughness and increasing nonessential work of fracture scaling with ligament length. A longer distance is accompanied by a higher distribution of aligned fibers bridging behind the crack wake, reducing crack driving forces at the crack tip. SIGNIFICANCE: SFRC materials provide increasing toughening potential with increasing thickness, and have the ability to be more anisotropic than other composite materials. Clinically, the layer must have a conventional composite cover layer, but which thickness does not affect toughness potential. Therefore the thickness of the conventional composite can be dictated by wear behavior.
EVALuna2:465659

Toughening by revitrification of Li2SiO3 crystals in Obsidian® dental glass-ceramic - Lubauer, Julia; Hurle, Katrin; Cicconi, Maria Rita; Petschelt, Anselm; Peterlik, Herwig; Lohbauer, Ulrich; Belli, Renan (Journal of the Mechanical Behavior of Biomedical Materials, 2021)
As a predominantly lithium-metasilicate-containing glass-ceramic, Obsidian® (Glidewell Laboratories, USA) has a peculiar composition and microstructure among other dental lithium silicates, warranting an evaluation of the crystallization process to establish relationships between microstructural evolution and mechanical properties. Blocks of the pre-crystallized material were processed into slices measuring 12 × 12 × 1.5 mm3 and subjected to the mandatory crystallization firing by interruption the heating ramp at temperatures between 700 °C and 820 °C (dwell time between 0 min and 10 min). The crystallization peaks of the base and the pre-crystallized glass were obtained by differential scanning calorimetry (DSC). The coefficient of thermal expansion and the glass transition temperature were derived from differential thermal analysis (DTA). X-ray diffraction (XRD) was performed to quantify and characterize the crystal phase fraction, whose microstructural changes were visualised using FE-SEM. The ball-on-three-balls surface crack in flexure method was used to track the evolution of fracture toughness. The microstructural evolution during crystallization firing was characterized by two regimes of growth: (i) the progressive revitrification (dissolution) of the 5 μm-sized Li2SiO3 polycrystals manifested at the boundaries of nanometric single coherent scattering domains (CSDs); (ii) the non-isothermal period is marked by an Ostwald ripening process characterized by the growth of the single crystalline structures into 0.5 μm polycrystals. The decrease in the crystal fraction of Li2SiO3 crystals from 41 vol.% to 37 vol.% is accompanied by the formation of a small amount of Li3PO4 (6 vol.%), maintaining the total crystal phase fraction mostly constant. The KIc accompanied the reverse trend of crystallinity, departing from 1.63 ± 0.02 MPa√m at the pre-crystallized stage to 1.84 ± 0.06 MPa√m after 10 min at 820 °C in a linear trend. Toughening appeared counter-intuitive in view of the decreasing crystal fraction and size, to rather relate to the relaxation of the residual stresses in the interstitial glass due to the spheroidization of the initially anisotropic, elongated Li2SiO3 crystals into round, nearly equiaxed particles, as let suggest from the disappearance of the extensive microcracking.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Crystallization; Dental; Fracture toughness; Glass-ceramic; Mechanical properties; X-ray Diffraction

Understanding the mechanical behavior of the material-tissue and material-material interface in dental reconstructions - Ferracane, J. L.; Lohbauer, Ulrich; Palin, W. M. (Elsevier Inc., 2016)
A variety of materials and material combinations are used for the repair or replacement of oral and craniofacial tissues, resulting in numerous types of material interfaces. The characterization of these interfaces and their properties is an essential component to understanding the behavior and clinical performance of the final construct. Several of the important interfaces encountered in dental reconstructions, and the exiting methods for testing the properties of these interfaces, are examined in this chapter.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Adhesion; Ceramics; Dental adhesive; Dental composite; Dentin; Enamel; Fatigue; Fracture toughness; Interface; Metals

Vertical root fractures in crowned teeth: A report of 32 cases - Schwarz, Sophie; Lohbauer, Ulrich; Petschelt, Anselm; Pelka, Matthias (Quintessence International, 2012)
Objective: To clarify the mode of root fracture in 32 endodontically treated teeth that resulted in vertical root fracture (VRF) despite the provision of a crown for fracture prevention- Method and Materials: The teeth included in the study underwent root canal treatment and were restored with crowns without the use of an intracanal post. All teeth underwent photo documentation. Clinical signs and symptoms as well as the patients’ ages were recorded. The diameters of the roots and the root canal fillings were measured on radiographs. Fractured roots were investigated using a scanning electron microscope (SEM). Results: The mean patient age was 60.2 years. The VRFs in the group occurred most frequently in the mesial roots of the mandibular first molars. The fracture was predominantly buccolingual. The mean ratio measured between the diameters of the root canal obturations and the outer root surfaces in the radiographs was 33.2%. SEM evaluation showed that most fractures ran from the inner to the outer root surface, and the cracks predominantly ran apical to coronal. Conclusion: Endodontically treated and crowned teeth without root canal posts can develop VRFs. The cracks start at the root canal wall in the apical part of the root and extend toward the outer root surface and coronally. Further investigation is necessary to determine the possible causes and evidence of fracture development. © 2012 by Quintessence Publishing Co Inc.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Apical preparation; Apical sclerosis; Crack development; Root canal treatment; Vertical root fracture

Viscosity and stickiness of dental resin composites at elevated temperatures - Loumprinis, Nikolaos; Maier, Eva; Belli, Renan; Petschelt, Anselm; Eliades, George; Lohbauer, Ulrich (Dental Materials, 2021)
Objective: To investigate the influence of pre-heating different classes of dental resin composites on viscosity and stickiness at five different temperatures. Methods: Six flowable, five conventional packable, and one thermo-viscous bulk-fill resin composites were heated up to 54 °C in a plate-plate rheometer to determine their complex viscosity. Normal force measurements were carried out for the six packable materials to determine the unplugging force and unplugging work (stickiness) over the same temperature range. Data were analyzed using Kolmogorov–Smirnoff test, one-way ANOVA and Tukey Post Hoc test with α = 0.05 as level of significance. Results: At 23 °C packable composites showed viscosity between 6.75 and 19.14 kPa s, while flowable composites presented significantly lower viscosities between 1.31 and 2.20 kPa s. Pre-heating led to a drop of 30–82% in the viscosity of packable materials. The thermo-viscous material dropped to the level of flowables at 45 and 54 °C thus behaving as a packable composite at room temperature with flowable-like viscosity at higher temperatures. No statistically significant differences for viscosity were observed among flowable composites at any temperature. The unplugging force decreased for packable composites, while their unplugging work generally increased at elevated temperature. At 23 °C unplugging force was measured between 7.50 and 19.18 N, while pre-heating up to 54 °C led to values between 2.9 and 6.2 N. Regarding unplugging work at 23 °C the calculated values were between 3.0 and 8.9 × 10−3 J and at 54 °C between 8.8 and 13.0 × 10−3 J. Significance: Pre-heating significantly reduced viscosity of highly viscous resin composites, while no influence was shown for flowable composites. In general stickiness, measured as unplugging work, increased at elevated temperatures. The thermo-viscous material showed low viscosity comparable to flowable composites at 45 and 54 °C, yet its stickiness did not increase significantly compared to the values at 23 °C.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Activation energy; Handling properties; Pre-heating; Resin composite; Rheology; Stickiness; Temperature; Viscosity

Wear and morphology of infiltrated white spot lesions - Belli, Renan; Rahiotis, Christos; Schubert, Edward W.; Baratieri, Luiz N.; Petschelt, Anselm; Lohbauer, Ulrich (Journal of Dentistry, 2011)
Objectives: To evaluate the toothbrush wear resistance of infiltrated artificial white spot lesions following two infiltration strategies, and to assess their ultramorphology. Methods: Flat enamel surfaces from freshly extracted bovine teeth were polished and immersed in a Buskes demineralising solution for 30 days to create incipient caries-like lesions (white spots). Two experimental regions on the surface of each tooth were infiltrated with an infiltrant and a commercial etch-and-rinse adhesive. Toothbrush abrasion was applied for 20,000 cycles. Vertical wear loss of the infiltrated areas was measured after 10,000 and 20,000 cycles against unabraded and abraded enamel using confocal laser scanning microscopy (CLSM; multiple t-tests, α = 0.05). Each lesion's surface and cross-section were evaluated under CLSM and scanning electron microscopy after etching and infiltration to assess ultramorphology. Results: After 20,000 abrasion cycles, a statistically non-significant difference in vertical wear loss was measured for the infiltrant versus the adhesive compared with the original enamel (42.6 ± 20.7 μm vs. 40.4 ± 18.5 μm, p > 0.05). Irregular surface profiles were common for the adhesive-infiltrated group as a result of peeling and blistering of the resin-covering layer. Ultramorphology of the infiltrated lesions revealed different patterns of penetration regarding density and depth. Conclusions: Although both infiltration strategies had equivalent wear resistance to toothbrush abrasion, surface and morphological aspects pointed to improved surface stability and infiltration quality for the infiltrant material. © 2011 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Adhesive; Caries; Caries infiltration; Infiltrant; Ultramorphology; Wear; White spot

Zirconia nanoparticles prepared by laser vaporization as fillers for dental adhesives - Lohbauer, Ulrich; Wagner, Andrea; Belli, Renan; Stoetzel, Christian; Hilpert, Andrea; Kurland, Heinz-Dieter; Grabow, Janet; Mueller, Frank A. (Acta Biomaterialia, 2010)
Zirconia nanoparticles prepared by laser vaporization were incorporated into the primer or into the adhesive of a commercial adhesive system in order to evaluate its effect on bond strength to dentin. Zirconia nanoparticles (20-50 nm) were prepared using a particular laser vaporization technique and incorporated into the primer (P) or into the adhesive (A) of the Adper Scotchbond Multi-Purpose (SBMP) system at 5, 10, 15 and 20 wt.% by means of mechanical mixing (stirring) and ultrasonication. Control (unfilled) and experimental groups (filled) were applied, according to the manufacturer's instructions, onto flat mid-coronal human dentin. Composite crowns were built up, stored in distilled water for 24 h at 37 °C and cut into 0.65 ± 0.05 mm2 beams following a non-trimming microtensile technique. Specimens were fractured in tension using a universal testing machine (Zwick) and examined by scanning electron microscopy for fractographic analysis. Microtensile bond strength (μTBS) data were analyzed using a two-way ANOVA and modified LSD test at α = 0.05. Analysis of the nanofiller distribution and ultramorphological characterization of the interface were performed by transmission electron microscopy (TEM). Zirconia nanoparticle incorporation into the primer or into the adhesive of SBMP significantly increased μTBS to dentin. Filler concentration only affected μTBS significantly in the P group. Statistically significant differences between groups P and A occurred only at 20 wt.% filler content, with a significantly higher μTBS in group P. TEM micrographs revealed nanoparticle deposition on top of a hybrid layer when incorporated into the primer, whereas they remained dispersed through the adhesive layer in group A. Zirconia nanoparticles incorporation into SBMP increased bond strength to dentin by reinforcing the interface adhesive layer. Nanofiller incorporation into the primer solution showed a tendency of increasing bond strength with increasing concentration. At high concentrations (20 wt.%) nanofiller incorporation was more efficient in increasing bond strength if incorporated in the primer solution. Adding nanofillers to the primer and to the adhesive solutions resulted in different particle distributions at the interface. © 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Dentin bonding; Laser vaporization; LAVA; Nanoparticle; Zirconia

Zirconia posterior fixed partial dentures: 5-year clinical results of a prospective clinical trial - Schmitt, Johannes; Goellner, Matthias; Lohbauer, Ulrich; Wichmann, Manfred; Reich, Sven (International Journal of Prosthodontics, 2012)
This study aimed to evaluate three- and four-unit posterior fixed partial dentures (FPDs) with zirconia frameworks after 5 years of function. Of the initial 30 subjects, 25 patients with 25 FPDs were examined after a mean follow-up period of 62.1 months. Five patients were not available for recall visits. Two FPDs failed before the 60-month evaluation because of framework fracture or delamination of the veneering ceramic after endodontic treatment. The 5-year survival rate was 92%. Based on these results, it can be suggested that zirconia frameworks have sufficient mechanical requirements for use in the stress-bearing posterior region. Major fracture of the ceramic veneer could be related to inadequate framework design or bruxism. © 2012 by Quintessence Publishing Co Inc.
CRIS-Team Scopus Importer:2023-01-23